Multi-target antifungal mechanism of cinnamon essential oil against Colletotrichum musae and its effectiveness in preserving harvested banana fruit - Hongpeng Yu; Zizhen Li; Dong He; Kegang Wu; Xianghua Chai; Xuejuan Duan; Qiang An; Shengjian Wei (Postharvest Biology and Technology, 2027)

Drought weakens greenhouse gas sink of global wetlands - Longxin Qiao; Xinxin Wang; Hongyang Chen; Jihua Wu; Xiangming Xiao; Ming Nie; Rui-Ting Ju; Yuhan Zheng; Xi Zhang; Qiang He; Xutong Ru; Lijuan Cui; et al. (Environmental Impact Assessment Review, 2027)

A knowledge-based retrofit priority identification framework of the mineral processing to assist in process improvement - Furong Sun; Dakuo He; Hongying Lin; Qiang Li; Chun Wang; Jiacheng Liu; Duanduan Wang (Minerals Engineering, 2026)

Clear water but contaminated sediment: Heavy metal risks in suspended sediments of the Three Gorges Reservoir, China - Bingyan Li; Jie Wei; Xiubin He; Yuhai Bao; Qiang Tang; Ping Huang; Shengjun Wu; Jinlin Li (Ecohydrology & Hydrobiology, 2026)

Astragaloside IV pretreatment enhances the therapeutic efficacy of bone marrow mesenchymal stem cells in murine fulminant hepatic failure - Ting-Ting Zhao; Wen-Qiang He; Rui-Zhi Shi; Bing-Yu Du; Mei-Mei Lan; Dan Zhou; Xiao-Qin Gao; Min Li; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

Hypoxia-preconditioned bone marrow mesenchymal stem cells alleviate acute liver failure in association with the VEGF/c-Met pathway - Mei-Mei Lan; Rui-Zhi Shi; Zhe-Yu Li; Wen-Jun Qiao; Yong-Juan Guan; Wen-Qiang He; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

Single-blastomere transcriptomics identifies NR5A2-associated metabolic genes during porcine zygotic genome activation - Zihan Li; Fuheng Xie; Yuqing He; Li Ma; Shuang Liang; Qiang Liu (Theriogenology, 2026)

Fabricating highly-dispersed W-O-Si structure via silanols modulation over WOx/SiO2 catalyst enables efficient olefin metathesis - Haoxuan Tan; Jianhao Jiao; Yun Zu; Qiang Li; Yucai Qin; Ye Yang; Kai He; Zhongxing Geng; Lijuan Song (Fuel, 2026)

Rationally tailoring defect levels in Prussian blue analogues for enhanced rubidium adsorption - Gan Li; Wanghai He; Qiang Li; Fei Xu; Jiazheng Qin; Ting Wang; Mingshan Yang; Xin Hu; Dahuan Liu (Desalination, 2026)

Alternating out-of-plane quasi-ordered Mo4VAlC4 MAX phase enables Mo4VC4 o-MXene with enhanced electrocatalytic hydrogen evolution and Li-ion battery performance - Yunxiang Liao; Martin Dahlqvist; Fuwang Hu; He Chong; Zhaohui Chen; Hongyun Guo; Qiang Li; Zhen Ma; Johanna Rosen; Lishan Peng; Qiang Wang; Weibin Cui (Chemical Engineering Journal, 2026)

Machine learning-integrated multi-objective application and optimization framework for sulfur-based reactive filler towards nutrient removal - Jia-Min Xu; Jia-Qiang Lv; Wen-Ke He; Hong-Cheng Wang; Xiang-Li Zeng; Yu-Qi Wang; Wan-Xin Yin; Fang Huang; Gui-Jiao Zhang; Heng Dong; Yanchen Liu; Aijie Wang; et al. (Water Research, 2026)

Principal-stress rotation effects on multi-scale fracturing in deep rock tunnels with staggered structural planes: Physical modelling and DEM simulations - Guo-Qiang Zhu; Liangjie Gu; Changdong Li; Zhongfu Wu; Ben-Guo He; Abbas Taheri (Tunnelling and Underground Space Technology, 2026)

Allelochemicals stimulation (ACS) strategy: Potential for studying allelopathy and discovery of phytotoxins - Dan He; Zhibo Hu; Haishan Cui; Cheng Li; Qiang Wang; Heng Guo; Lan Liu; Jing Li (Phytochemistry, 2026)

Lower crustal modification at the margin of the North China Craton: Multi-proxy geochemical and isotopic imaging constraints from the Late Mesozoic granitoids in Jiaodong Peninsula - Can-Can Wang; Li-Qiang Yang; Xue Gao; Wen-Yan He; Lei Ju; Dong Xie; Long Wang; Shi-Yao Zhai; Wei Yang; Nan Li; Zheng-Jiang Ding; Jun Deng (Journal of Asian Earth Sciences, 2026)

A novel multi-strategy collaborative correction method for LIBS spectral intensity under laser energy fluctuations - Yu Ding; Qiang Tan; Yuhang Wang; Yihua He; Maoyuan Pang; Jinyi Li; Weiye Yu; Jianan Xu; Xiangchu Li; Xinxin Liu (Analytica Chimica Acta, 2026)

Tip funnel-shaped nanochannels sensor for high-flux chloride transport inspired by CLC - Cuiguang Ma; Haifan Zhang; Govindasami Periyasami; Qiang He; Yuechao Liu; Zhihang Zhao; Shuhui Hu; Ehsan Bahojb Noruzi; Jia Li; Liuwei Jiang; Haibing Li (Analytica Chimica Acta, 2026)

Causal inference reveals the dominant role of climate-adaptation coupling in future potato production - Zhihao He; Tengcong Jiang; Lin Zhu; Ning Yao; Yi Li; Hao Feng; De Li Liu; Liang He; Jianqiang He; Qiang Yu (Agricultural Systems, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

G4 dimer-driven trimodal cross-validated immunosensing strategy for accurate CHI3L1 detection toward liver fibrosis diagnosis and drug efficacy evaluation - Lina Lu; Jiaxuan Qiao; Yaran Tao; Bingjun He; Jun Jiao; Mengai Yin; Fuju Dai; Yusheng Li; Lan Xue; Yu Zhu; Ye Huang; Qiang Chen (Chemical Engineering Journal, 2026)

From thermal runaway propagation to inhalation risk: Influence of state of charge on heat transfer and particle emissions in lithium-ion batteries - Yijia He; Qiang Dong; Zhan Wang; Huifeng Li; Chenwei Shang; Long Ma; Ming Fu; Jinlong Zhao; Xiaole Zhang (Process Safety and Environmental Protection, 2026)

Complete genome sequence of a novel Pseudomonas sp. GW-45 isolated from Antarctic Ardley cove showing DMSP degradation capability - Yi-He Zhang; Yong-Qiang Hu; Zuo-Qi Wang; Chun-Yang Li; Ting Hu; Zhong Hu; Yin-Xin Zeng (Marine Genomics, 2026)

Disruption of OsGONST3 reduces grain cadmium accumulation without yield penalty in field-grown rice - Jing Huang; Qiang Zhang; Fang Wei Yu; Ming Qing Liu; Huai Kang Jing; Shen Yun Wang; Hao Yu Wang; Jia Qi Li; Lu Zheng; Hua Shao; Xiao Lin He; Ren Fang Shen; et al. (Journal of Hazardous Materials, 2026)

Cadmium in global topsoil: Spatial distribution, associated factors, and cropland exposure screening - Ruixing Huang; Zhentao Xiao; Chengxue Ma; Jun Ma; Jie Li; Qiang He; Xiaoliu Huangfu (Journal of Hazardous Materials, 2026)

Effects of structural heterogeneity in soil humic acids from distinct river basins on Tl(III) binding-reduction: Kinetics and mechanisms - Hongye Li; Die Hu; Chengxue Ma; Ruixing Huang; Yuheng Huang; Qiang He; Hongxia Liu; Xiaoliu Huangfu (Journal of Hazardous Materials, 2026)

An enhanced and humidity-adaptive chitosan foam triboelectric nanogenerator: Multi-component synergistic design for energy harvesting and sensing applications - Jie Tao; Qiangli Zhao; Jiahao Kang; Min Mao; Qiang Mu; Tao Jiang; Lanjin Wang; Panxu Wang; Xiao Han; Xinhai He; Jianwei Li (Carbohydrate Polymers, 2026)

Influence of Interbedded Soft and Hard Rock on Rock Burst and Microseismic Activities in Deeps: Case Studies - Yue-Mao Zhao; Zheng-Chen Ge; Peng-Xiang Li; Kai Liu; Ben-Guo He; Xing-Dong Zhao; Guo-Qiang Zhu (Rock Mechanics and Rock Engineering, 2026)

Modal damping contributed by infills with horizontal frictional sliding joints in infilled frames under seismic excitations - Chong He; Guo-Qiang Li; Feifei Sun; H.K. Pan (Soil Dynamics and Earthquake Engineering, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Synergy of substrate, plant, and microorganism in constructed wetlands enhances chromogenic substances and nitrogen removal from real chemical tailwater - Yi Liu; Yuling Huang; Chunhua Li; Qiang He; Hong Li (Journal of Water Process Engineering, 2026)

Effects of defatting treatments on flavor components and lipid characteristics in bowl-steamed Tan lamb: A comprehensive investigation based on lipidomics and multi-platform flavor analysis - Wen Wang; Yufeng Duan; Xue Yang; Ruheng Shen; Mengying Liu; Xiaoqin Xi; Li Zhang; Long He; Yuling Qu; Liang Lin; Qiang Cheng (Food Chemistry, 2026)

China could simultaneously increase wheat yield and nitrogen use efficiency under the temperature rise of 1 ℃ through optimal crop managements - Kaiyuan Gong; Shuoqiu Ding; Yadong Luo; Yinghua Zhang; Xiao Wang; Fengying Duan; Xia Li; Liangbing Rong; Zhihao He; Hao Feng; Qiang Yu; Wenbin Zhou; et al. (European Journal of Agronomy, 2026)

Na-rich Na3.2V1.9Fe0.1O2(PO4)2F cathode unlocks high energy density and wide-temperature operation in sodium-ion batteries - Qiang Fu; Qin He; Fangxiang Song; Keliang Wang; Jing Li; Xianquan Ao; Rong Li (Chemical Engineering Journal, 2026)

Membrane-based advanced oxidation processes for water and wastewater treatment: Advances, trade-offs, and challenges - Caihong Liu; Chi Xiong; Hai Liang; Kun Yang; Andreia F. Faria; Liu Yang; Amauri J. Paula; Hongtao Li; Dan Song; Qiang He; Jun Ma (Chemical Engineering Journal, 2026)

Dually enhanced methylcellulose conductive gel with self-healing, stretchability and anti-swelling for wearable microstructured triboelectric nanogenerator - Chenyu Li; Can Yang; Jingting Chen; Zimo Qin; Yue Xiao; Wenjie He; Shuzheng Liu; Gang Qin; Jia Yang; Qiang Chen (Chemical Engineering Journal, 2026)

2-Methoxyestradiol Suppresses Stemness and Epithelial-Mesenchymal Transition in Drug-Resistant Esophageal Squamous Cell Carcinoma by Targeting the Snail Signaling Pathway in Cancer Stem Cells - Jie Yan; Shuhua Han; Keqi Zhang; Linlin Li; Mingjing He; Haoqing Cao; Meiru Zhu; Bingjie Bi; Qiang Xu; Cong Wang (Stem Cell Reviews and Reports, 2026)

Decoding immunotherapy resistance in multiple myeloma: genetic insights and approaches to counter resistance - Huan Li; Qi Xia; Mei Yu; Ying Lv; Jialing Xiao; Xiaoxin Guo; Kai Dong; Yu Zhou; Ling Zhong; Ting Wang; Weijia Wu; Chengzi Gan; et al. (Science China Life Sciences, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Aboveground inputs rather than belowground root drive SOC responses to long term N addition in alpine grassland ecosystems of Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Juejie Yang; Ying Li; Yaoming Li; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; et al. (Agriculture, Ecosystems & Environment, 2026)

Contrasting fates of detritus in mangrove sediments: Microbial trade‐offs between carbon storage and greenhouse gas emissions - Yuxing Hu; Qi Chen; Xiaomeng Wang; Yihua Cai; Guangyi Su; Yunxuan Li; Chen He; Quan Shi; Zekun Zhang; Ding He; Christian Lønborg; Nianzhi Jiao; et al. (Limnology and Oceanography, 2026)
Mangroves are known as important carbon storage hotspots, yet their net climate benefit can be offset by large greenhouse gas emissions. In this study, we conducted a 1‐yr in situ incubation coupled with high‐resolution molecular and microbial analyses to elucidate the fate of two major types of mangrove detritus, including leaves ( Kandelia obovata and Sonneratia apetala ) and macroalgae ( Ulva prolifera ), via microbial metabolism. Approximately 50% of the added organic carbon from both sources was mineralized to CO 2 , while 7.5% (leaves) and 9.7% (macroalgae) were emitted as methane (CH 4 ). Around 33.8% of the leaf‐derived and 2.1% of the macroalgae‐derived organic carbon contributed to longer‐term carbon storage. CH 4 emissions from leaf litter offset approximately 11.1% of the net ecosystem productivity and were positively correlated with molecular formulas assigned to the aliphatic‐like group and with sulfur‐ and phosphorus‐containing molecular formulas. CH 4 production was initially dominated by methylotrophic methanogenesis (mostly Methanolobus ), followed by more diverse pathways associated with Methanosarcina . Our results demonstrate that different types of mangrove detritus have distinct effects on sediment biogeochemistry and greenhouse gas emissions and highlight the need to account for both CO 2 and CH 4 emissions when assessing the climate benefits of mangrove ecosystems.

Interaction Between Carbon and Nitrogen Cycling in the Vanadium Titanium Magnetite Tailings Soil During Pongamia pinnata Remediation - Xiang Liu; Lan Zeng; Xinyi Li; Qiyi Li; Qilu He; Yueyi Li; Yunfu Gu; Quanju Xiang; Ke Zhao; Likou Zou; Menggen Ma; Qiang Chen; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Ginsenosides mitigate multi-organ aging: mechanistic insights from a preclinical systematic review and meta-analysis - Ao Li; Hua-Ze Wu; Die-Yi Chen; Yu-Xin Gao; Xiao-Qiang Xiang; Qing-Hui He; Hong-Yan Ma; Dan Tang (Critical Reviews in Food Science and Nutrition, 2026)

Water-saving and economic benefits of a soil moisture threshold-based irrigation strategy for cotton in Xinjiang under climate change - Bin Chen; Linjia Yao; Yadong Liu; Mohamed Amine Benaly; Changqing Yan; Genghong Wu; Ronghao Guan; Yi Li; Dongyan Zhang; Jie Bai; Qiuxiang Tang; Jianqiang He; et al. (European Journal of Agronomy, 2026)

Mechanistic insights into glufosinate-ammonium (GLA)-Induced brain injury revealed by LC-MS/MS-based metabolomics - Huan-le Ye; Xin-xin Zheng; Mian-mian Li; Zhi-qiang Zhang; Liu-xu Chen; Wen-jing Zhang; Ren Cheng-Han Fan; Guo-xin He; An-cong Xu (Chemico-Biological Interactions, 2026)

Overexpression of β-carotene hydroxylase gene (CiBCH) enhances salt stress tolerance in Arabidopsis thaliana - Ying Sun; Ying Song; Shuaitong Zang; Ruiqing Zhang; Hongyao Li; Qiang Li; Liran Yue; Changle Liu; Miao He (Physiology and Molecular Biology of Plants, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

A Numerical Simulation Study on the Distribution Pattern of the Habitat Suitability Index near the New Eco-Revetment Structure for Grass Carp with Different Life Cycles - Jian Li; Qiang He; Xiaoling Zhang; Pingyi Wang (Fishes, 2026)
Fish are an important criterion for evaluating the quality of river ecosystems, and water flow characteristics may be the main factor affecting the living environment of fish. As the main component of a river, the topography of the bank slope has a significant impact on the characteristics of nearshore water flow. At the same time, eco-revetment structure has the functions of smoothing water flow, maintaining stable bank slopes, and improving river ecology. It can reset the distribution of nearshore water flow and provide a stable living environment for fish. This study focuses on the middle and lower reaches of the Yangtze River as the research area, with the main research object being grass carp. We construct a generalized model based on river morphology and flow characteristics. A new eco-revetment structure is proposed with the main research area of nearshore waters, aiming to improve the flow state of nearshore water and enhance its ecology. A suitability evaluation model for grass carp habitat was constructed based on Large Eddy Simulation and fuzzy mathematics theory, with water flow as the main habitat influencing factor. We study the distribution pattern of suitability for grass carp habitats near nearshore waters. The results indicate that the nitrogen phosphorus ratio near the top of the revetment structure is close to the Redfield value and can be used as a stable foraging area for fish. The flow rate is the dominant factor for the habitat of juvenile grass carp. When there is no vegetation, the suitability of region A is 0–0.4, the suitability of region B is 0.2–0.6, and the area proportion of the high suitability area (0.4–0.6) is maintained at 10–30% with the increase in the flow rate. Region C is not suitable for the long-term survival of juvenile grass carp. When there is vegetation, the suitability of region A ranges from 0 to 0.6, and the proportion of low-suitability areas decreases. The suitability of region B ranges from 0.4 to 0.6, and the proportion of suitable areas is positively correlated with flow velocity. The suitability of region C is consistent with the absence of vegetation. The dominant factors for fish spawning habitat are flow velocity, vorticity, and kinetic energy gradient. The spawning suitability zone (HSI ≥ 0.6) is located between the spanwise structures, with a proportion positively correlated with flow velocity and higher suitability on the deep-water side. The existence of fish has little impact on the habitat. In the juvenile fish habitat area, the proportion of areas suitable for juvenile fish in region A has slightly decreased, and the suitability of region B has increased. In spawning grounds, an HSI ≥ 0.6 accounts for about 5% of the decrease compared to no-fish conditions, and overall can meet the needs of fish habitat, foraging, and spawning. This article provides ideas and foundations for the design of future new eco-revetment structures and a suitability analysis of living environments for fish.

Finite-Time Disturbance Compensation for Hierarchical Formation of Dual AGVs in Smart Ports - Qiang Zhang; Bo Yuan; Li He; Zhengfang Xu; Dudu Guo (Journal of Marine Science and Engineering, 2026)
This paper proposes an integrated formation control framework with a finite-time nonlinear disturbance observer (FT-NDO) for automated guided vehicles (AGVs) operating in port environments, where constrained workspace, narrow formation spacing, and complex external disturbances pose significant challenges. An adaptive leader–follower formation strategy with dynamic inter-vehicle spacing is developed to enhance maneuverability during turning. Within a hierarchical control structure that decouples lateral and longitudinal dynamics, two sliding mode controllers (SMCs) are designed: (a) a lateral SMC that prioritizes heading accuracy, limiting yaw angle error to within ±2°; and (b) a nonsingular terminal SMC (NTSMC) for longitudinal control, improving error convergence speed compared to conventional SMC. An FT-NDO is further incorporated into both control loops to estimate and compensate for external disturbances in real time, achieving a disturbance estimation accuracy of over 95% and significantly attenuating the impact of environmental disturbances. Validation through simulation and physical experiment of a dual-AGV formation in a realistic port scenario demonstrates that the proposed approach restricts formation deviation to 0.015 m and maintains stable operation under various disturbance conditions. This study provides a practical solution for dual-AGV collaborative transportation in spatially constrained and dynamically disturbed environments, with direct implications for improving operational efficiency and safety in port logistics.

Performance evaluation and optimal design of inclined alternating rigid-core high-pressure jet grouting piles slope retaining structure: A case study in Guiyang, China - Junhao Liu; Fei Gan; Gang Zheng; Meilin Li; Licheng Wu; Wei Bao; Yu Ren; Xudong He; Qiang Lou; Hong Wang (Transportation Geotechnics, 2026)

Enhanced antifriction and antiwear performances of steel achieved by porous boron nitride/grease composite triggered self-adaptive confined lubrication - Heng He; Fengli Zhou; He Huang; Songyan Cong; Beiyi Zhang; Weiben Chen; Yibing Lin; Li Qiang; Yuanlie Yu (Journal of Environmental Chemical Engineering, 2026)

Apparent resistivity evaluation method of slurry diffusion-solidification and grouting effect of water-bearing fractured rock mass - Hao Xu; Zhen-zhong Xing; Sheng-quan He; Lian-zhi Yang; Yi Zhu; Da-zhao Song; Yu Zhang; Jin-tao Dang; Qiang Liu; Li-ming Qiu; Ping Wang (Journal of Applied Geophysics, 2026)

Heterostructured carbon anodes with weakly solvating interfaces for fast Na+ transport and low-temperature performance - Xinyu Shao; Fengling Zhang; Ruqiang Yuan; Xin Zhang; Yan He; Chunrong Ma; Qiang Li (Chemical Engineering Journal, 2026)

Dynamic modulation of metal active sites via an oxide overlay strategy for selective furfural transformation - Jiang Wu; Ai-Jun Guo; Li-Ying Xie; Xiao-Qi Zhang; Yi-Qiang Qi; Kai Meng; Xiao-Yu Li; He Liu; Shuang-Long Ma (Chemical Engineering Journal, 2026)

Geomorphological controls on elevational differentiation of sediment 210Pbₑₓ and 137Cs activities in a water-level fluctuation zone - Jinlin Li; Xiubin He; Jie Wei; Qiang Tang; Yuhai Bao; Ping Huang; Shengjun Wu; Xin Gao; Ziqiang Mao (CATENA, 2026)

Soil total nitrogen drives the enhancement of carbon pool stability as the succession progresses in poplar-birch secondary forests - Ge Li; Jiahe Zhou; Qiang Liu; Jiaying He; Zhidong Zhang; Yue Pang; Jing Tian; Qi Zhang; Yuexun Wang (Plant and Soil, 2026)

Research progress on the application of seaweed extracts in fertilizer synergism - Shaochong Li; Haofeng He; Jingyan Chen; Xinyu Guo; Qiang Li; Ming Lu; Hang Su; Fuli Li (Algal Research, 2026)

PCGF1 is a key factor for facilitating dynamic H3K27me3 modification during early lineage specification - Pan Chen; Xuejie Yang; Ruhai Chen; Hanlu Li; Jingwen Ma; Jing Chang; Guangliang Hong; Wei Liu; Xiongzhi Quan; Bin Yin; Lin Hou; Boqin Qiang; et al. (Science Bulletin, 2026)

Improving resilience monitoring in non-stationary systems via a robust data-chunking algorithm - Linhai Cheng; Qiang Tang; Nan Lu; Chi Xu; Babak M.S. Arani; Changjia Li; Yafeng Wang; Xiangyi Li; Phuping Sucharitakul; Shuai Wang; Jie Wei; Junran Li; et al. (Science Bulletin, 2026)

Research on thrust fluctuation and flow field characteristics of pump-jet propulsor in XLUUV's hull wake - Bo Lu; Qiaogao Huang; Han Li; Wei Qiang; Xing He; Xinming Li; Sijie Zheng; Xihui Wang (Ocean Engineering, 2026)

Bioremediation of high concentrations of mercury and nickel in activated sludge by black soldier fly larvae: Accumulation, transformation, and sustainability assessment - Bo Deng; Chong-Yang Ren; Zi-He Ren; Zhi-Jian Zhang; Qiang Li; Qiao-Xia Yuan; He-Ping Zhao (Journal of Hazardous Materials, 2026)

Experimental study on microwave-assisted mechanical fragmentation of simulated vesicular mare basalt - Liang-Xiao Chen; Zheng-Wei Li; Xia-Ting Feng; De-Tian Li; Cheng-Dan He; Xian-Qiang Li; Yong-Jun Wang; Wen-Feng Guo; Jian Ma (International Journal of Rock Mechanics and Mining Sciences, 2026)

Enhanced flavor and biogenic amine safety of salt-reduced Doubanjiang through co-inoculated fermentation with Pediococcus acidilactici and Zygosaccharomyces rouxii - Shenglan Liao; Youming Li; Jiayao Lin; Xiaoyi Wang; Yunhao Lu; Weiqin Deng; Qiang He; Yuanlong Chi; Zhenghong Xu (Food Research International, 2026)

Self-calibrating ultrasensitive biosensing platform based on multifunctional nanocomposites and DNAzyme-assisted CRISPR/Cas12a system for accurate TGF-β1 quantification in liver fibrosis assessment - Lina Lu; Yaran Tao; Jiaxuan Qiao; Bingjun He; Yu Zhu; Fuju Dai; Tong Wang; Zhijie Wang; Xiangrui Wang; Yusheng Li; Jun Jiao; Lan Xue; et al. (Chemical Engineering Journal, 2026)

A study on the prediction and driving mechanisms of typical air pollutant concentrations in the Yunnan Plateau region using machine learning - Yanqiu He; Yingxiang Jiang; Qiang Cao; Zewei Liu; Jiacheng Han; Wencai Li; Zhihong Chen (Atmospheric Environment, 2026)

Deficiency of primate-specific TFDP3 causes male infertility with oligoasthenoteratozoospermia in humans and cynomolgus monkeys - Chunyu Liu; Chaofeng Tu; Peng Li; Huan Wu; Feng Wan; Yong Lu; Shuyan Tang; Xin Li; Kuokuo Li; Jiaxiong Wang; Yang Gao; Xinyan Geng; et al. (Science China Life Sciences, 2026)

A semi-supervised domain adaptation framework with attention-enhanced ResNet50 for LIBS-based soil classification under spectral distribution shift - Yihua He; Yu Ding; Xiangchu Li; Jianan Xu; Qiang Tan; Weiye Yu; Jinyi Li; Maoyuan Pang; Xinxin Liu; Wangping Zhou (Analytica Chimica Acta, 2026)

Correction: Water-soluble platinum(II)-porphyrin based on oxygen response for cell hypoxia imaging - Meng-Yan Chai; Yu-Li Dang; He Qin; Li-Xia Xie; Xin Zheng; Lijie Liu; Guoxing Liu; Yu-Qiang Xiang; Cao-Yuan Niu; Sheng-Qiang Guo (Molecular Diversity, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Petrogenetic difference of Eocene granitic bedrocks controls light and heavy REE enrichment in regolith-hosted deposits, Tengchong terrane, SW China - Qiang Weng; Hai-Jun Yu; Wu-Bin Yang; Wen-Chang Li; He-Cai Niu; Yuan-Can Ying; Yu-Feng Huang (Lithos, 2026)

Pollution characteristics of Litopenaeus vannamei greenhouse effluents and purification performance of a combined flocculation–ecological floating bed system - Shanyuan Xue; Guo Li; Ensheng Zhu; Weizhen Zhang; Jiao Ran; Zhe Li; Yu Zhao; Jingru Hu; Jing Dong; Yingxue Yi; Dan Zhou; Qiang He; et al. (Journal of Environmental Chemical Engineering, 2026)

Short- and medium-chained chlorinated paraffins in soils and sediments in China: Spatiotemporal distributions, ecological risks, and driving mechanisms - Qiang Li; Ying Cao; Liansheng He; Cunfu Gao; Tian Meng; Yafeng Liu; Xiaoxue Liu (Journal of Environmental Sciences, 2026)

Dual-source-driven snowman-shaped PMO@MnO2@C@DMSN-SS31 Janus nanomotors for enhanced deep penetration and restoration of mitochondrial function to modulate the inflammatory microenvironment for cartilage repair - Xiaolei Zhang; Zhihan An; Yichen Zhang; Jinquan Cui; Qiang He; Chuandong Cai; Jianing Liu; Zhentao Man; Wei Li (Chemical Engineering Journal, 2026)

Unlocking the microbial mechanisms in fermented bean products: advances and future directions in multi-omics and machine learning approaches - Li Jiang; Yunhao Lu; Qiang He (Critical Reviews in Food Science and Nutrition, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Experimental and numerical simulation study on drag reduction performance of cross-medium bionic leading-edge propellers - Wenkai Tan; Yujie Liu; Fapeng Zhang; Qing Li; Zehua Xu; Anling Li; Qiang He (Ocean Engineering, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Paleo-Pacific slab break-off revealed by Cretaceous I-type and peralkaline A-type granite associations in the Cathaysia Block, SE China - Ao Li; Wu-Bin Yang; Ning-Bo Li; Shuo Xue; He-Cai Niu; Qiang Shan (Journal of Asian Earth Sciences, 2026)

Unraveling the antibacterial mechanism of eucalyptol against Escherichia coli O157:H7 through transcriptomics and its application in beef broth - Yaluan He; Yilin Wang; Yue He; Han Hu; Yong Hu; Qiang Hua; Yongkang Wu; Dongsheng Li; Zhijie Liu (International Journal of Food Microbiology, 2026)

The microbial response to biodegradable polylactic acid microplastics during anaerobic fermentation of waste activated sludge - Jie Chen; Jinjing Xiang; Maoli Hu; Yafei Zhang; Li Gu; Qiang He; Lin Li (Environmental Research, 2026)

Tailoring microbial communities for medium chain fatty acid production from waste activated sludge: Comparative performance of endogenous vs. exogenous consortia - Dengfei Li; Yuru Wang; Haifeng Qiang; Zhihong Liu; Zhangwei He; Wenzong Liu; Xiuping Yue; Aijuan Zhou (Bioresource Technology, 2026)

Data-driven structure optimization for enhanced hypervelocity in three-stage gas gun - Xiaolong Xin; Ruizhi Zhang; Chengcheng Guo; Zhiguo Li; Qiguang He; Jian Zhang; Qiang Shen; Guoqiang Luo (Advances in Space Research, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Real-Time AE − DIC Analysis and DEM Modeling of Structure-Controlled Rockburst Evolution in Hard Rock Tunnels - Guo-Qiang Zhu; Jialiang Zhou; Liangjie Gu; Shaojun Li; Abbas Taheri; Ben-Guo He (Rock Mechanics and Rock Engineering, 2026)

Application of compact CRISPR/Cas nucleases for citrus genome editing - Yulong Zhu; Jingyu Zhang; Yunqiang Ruan; Tiangang Lei; Shunxin Li; Li Cao; Xiuping Zou; Yongrui He; Qiang Li; Shanchun Chen; Aihong Peng (Transgenic Research, 2026)

Integration of ATAC-seq and RNA-seq reveals a bidirectional regulatory adaptation strategy involving both suppression and activation in the sea cucumber Apostichopus japonicus under hypoxia stress - Xinxi Sui; Xiaohua He; Xiumei Li; Xiaohui Xu; Yanwei Feng; Weijun Wang; Zan Li; Cuiju Cui; Kai Liu; Libo Wang; Jianmin Yang; Qiang Wang; et al. (Aquaculture, 2026)

DEHP induces hepatic fibrosis through STAT3-SLC7A11-ROS axis - Siqin Liang; Zhiliang Xu; Xiaoxiang You; Tinghao Yuan; Jun He; Lei Mao; Anan Jin; Xinwen Zhou; Bo Yi; Ming Li; Qiang Tu; Bin Xu (Toxicology and Applied Pharmacology, 2026)

Complex crystal textures and zoning patterns in the Saillipu potassic rocks (southern Tibet) and petrological implications - Jinsheng Zhou; Qiang Wang; Qiwei Li; Tongyu Huang; Zilong Wang; Pengli He (Lithos, 2026)

Polylactic acid microplastics facilitate nitrogen removal in freshwater sediments by modulating carbon-nitrogen coupling - Bingran Tang; Qinshuang Feng; Qiang He; Jun Li; Hong Li (Journal of Hazardous Materials, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

Enhancing the catalytic performance of ZnZrOx/SAPO-34 bifunctional catalysts through structural modulation - Rui Xiang; Tao Du; He Jia; Yingnan Li; Peng Chen; Qiang Yue; Heming Wang; Yisong Wang (Journal of Environmental Chemical Engineering, 2026)

A study on the impact of meteorological factors on radioactive fallout predictions of nuclear explosions - Feifei Li; Qiang Liu; Wei Liu; Zhaoru He; Ming Yang; Yangchao Li (Journal of Environmental Radioactivity, 2026)

Rock mass discontinuity trace mapping using a voxel-based morphology-topology framework - Jingsong Sima; Qiang Xu; Xiujun Dong; Haoliang Li; Qiulin He; Bo Deng (International Journal of Rock Mechanics and Mining Sciences, 2026)

Unlocking the potential of umami peptides: A comprehensive review of preparation methods, evaluation strategies, health benefits, and taste transduction mechanisms - Jianhua Zhao; Xinyu Li; Lunjie Huang; Hongbin Lin; Qiang He (Food Research International, 2026)

Combination of cold plasma and sonication for efficient carotenoid extraction from Capsicum annuum L.: Optimization, mechanism exploration, and food application - Jinpeng Zhu; Li Jiang; Jianhua Zhao; Yan Xiang; Yingyi Mao; Yunhao Lu; Yumeng Xia; Yuanping Lv; Qiang He (Food Chemistry, 2026)

Migration of dissolved organic matters in riparian soils induced by rainfall: distribution between surface and subsurface runoffs - Chang Liu; Lin Li; Yue Zhi; Yinying Zhu; Teng Hu; Qiang He (Environmental Research, 2026)

Water-soluble platinum(II)-porphyrin based on oxygen response for cell hypoxia imaging - Meng-Yan Chai; Yu-Li Dang; He Qin; Li-Xia Xie; Xin Zheng; Lijie Liu; Guoxing Liu; Yu-Qiang Xiang; Cao-Yuan Niu; Sheng-Qiang Guo (Molecular Diversity, 2026)

Multiscale eco-hydrological zoning in the Yarlung Zangbo River Basin, Qinghai–Tibet Plateau, China - Yanguo Liu; Li Wang; Xiurong He; Jingji Li; Ziqin Wang; Yu Chen; Qiang Zou; Liwei Tan; Mengni He; Xiangjun Pei (Environmental Development, 2026)

Inulin with different degrees of polymerization adopts different strategies to mitigate radiation-induced intestinal injury: focus on intestinal epithelial or T cell homeostasis - Kaihua Ji; Xiaoxiao Jia; Xinran Lu; Dengfeng Zhang; Liqing Du; Jinhan Wang; Yan Wang; Huijuan Song; Ningning He; Chang Xu; Yeqing Gu; Mengmeng Yang; et al. (Carbohydrate Polymers, 2026)

Longitudinal decoupling between sedimentary phosphorus concentrations and sediment sorting in the Three Gorges Reservoir, China - Jinlin Li; Pingsheng He; Xiubin He; Jie Wei; Qiang Tang; Xiaoya Tang; Xin Gao; Ziqiang Mao; Ping Huang; Shengjun Wu (CATENA, 2026)

Sucrose induces simultaneous autolysis attenuation and keratinase production enhancement in Bacillus subtilis WB600 - Yi-Ning He; Dao-Quan Jiao; Ge-Ge Chen; Xiao-Dong Pei; Zhi-Qiang Zhou; Fan Li; Yu-Hui Fang; Cheng-Hua Wang (Bioresource Technology, 2026)

CiPCS regulated by CiMYB4 enhances the tolerance of Chrysanthemum indicum to cadmium stress - Shengyan Chen; Liran Yue; Xiaomei Yang; Bin Xia; Hongyao Li; Bin Chen; Yujia Yang; Ying Sun; Qiang Li; Junxin Yan; Miao He (Plant Cell Reports, 2026)

Supramolecular cucurbit[7]uril@AuNPs self-assembled membranes for impedimetric sensing and selective removal of cationic dyes - Ehsan Bahojb Noruzi; Qiang He; Govindasami Periyasami; Zhihang Zhao; Yuchao Liu; Cuiguang Ma; Haifan Zhang; Jing Cheng; Haibing Li (Analytica Chimica Acta, 2026)

Seasonal variations in greenhouse gas production in coastal sandy sediments - Hao Zheng; Yanqing Feng; Yanshu Wang; Chenqingfeng Gao; Daochao Xing; Zhengyuan Li; Huizhong He; Qiang Liu; Zhengxin Yin; Xianbiao Lin (Marine Pollution Bulletin, 2025)

Iron oxide-mediated enhancement of extracellular electron transfer and symbiosis in consortium of electroactive bacteria and microalgae for wastewater treatment - Pingyin Shu; Li Zhao; Xin Wen; Ziqi Wei; Chaowei Yuan; Huazu Liu; Xiangdong Zhang; Xizi Long; Qiang He; Wei Li (Water Research, 2025)

In-depth exploration of NH3-SCR catalyst improvement research: Sulfur resistance, catalytic activity, and hydrothermal stability - Feng Jiang; Zhejun Li; Fengling Wang; Zhiqing Zhang; Shuwan Cui; Runze Li; Qiang He; Xuhui Yuan; Jie Hu (Journal of Environmental Chemical Engineering, 2025)

Migration mechanisms of leaking hydrogen sulfide in inter-stratified coal-petroleum basins and mitigation with alkali injection - Shun Liang; Hongye Luo; Derek Elsworth; Qiangling Yao; Xuehai Fu; Qiang Wang; Xuehua Li; Weisheng He; Zhi Ma; Guangli Huang; Furong Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Photothermal nanomedicine for glioblastoma: From material design to clinical translation challenges - Chan Li; Hui-Zhe Xu; Xue-Yan Cheng; Xin Yu; Zhi-Qiang Gong; Yi-Jiang He; Ling-Xiao Zhao; Zhan-You Wang (Chemical Engineering Journal, 2025)

Asymmetric actuators via lignin-cellulose nanofibrous composite films with programmable wet-light dual-responsiveness - Qiang Mu; Qiangli Zhao; Min Mao; Yao Liu; Jie Tao; Jiahao Kang; Wei Yong; Xinhai He; Jianhua Ma; Jianwei Li (Carbohydrate Polymers, 2025)

Improvement and Recovery of Intestinal Flora Disorder Caused by Ciprofloxacin Using Lactic Acid Bacteria - Xiumin Su; Li Su; Mengyuan Cao; Yulu Sun; Jinghan Dai; Yuanjie He; Wei Li; Wupeng Ge; Xin Lv; Qiang Zhang; Shenghui Cui; Jia Chen; et al. (Probiotics and Antimicrobial Proteins, 2025)

Alteration of Cecal Microbiota by Antimicrobial Peptides Enhances the Rational and Efficient Utilization of Nutrients in Holstein Bulls - Jinping Shi; Yu Lei; Zemin Li; Li Jia; Pengjia He; Qiang Cheng; Zhao Zhang; Zhaomin Lei (Probiotics and Antimicrobial Proteins, 2025)

Resistivity and Strength Characteristics of Fly Ash under Low-Temperature Freezing Conditions - Yuhang Li; Qiang Sun; Jishi Geng; Xinchao Zheng; He Zhang; Pengda Ma (Geotechnical and Geological Engineering, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Corrigendum to “Dual fronts control partitioned parameterization of light attenuation off a high-turbidity estuary: A partitioned parameterization scheme for the Changjiang Estuary” [Sci. Total Environ. 1003, (2025) 180616] - Zhihao Jiang; Feng Zhou; Hao Zheng; Qicheng Meng; Xiaobo Ni; Shuangyan He; Min Bao; Li Li; Qianjiang Zhang; Qiang Hao; Hongyu Huang; Jianfang Chen (Science of The Total Environment, 2025)

Dual fronts control partitioned parameterization of light attenuation off a highly-turbidity estuary: A partitioned parameterization scheme for the Changjiang Estuary - Zhihao Jiang; Feng Zhou; Hao Zheng; Qicheng Meng; Xiaobo Ni; Shuangyan He; Min Bao; Li Li; Qianjiang Zhang; Qiang Hao; Hongyu Huang; Jianfang Chen (Science of The Total Environment, 2025)

Improvement of RNAi efficiency by delivering of dsRNA formulated with cell-penetrating disulfide polymer in the fall Armyworm, Spodoptera frugiperda - Xu Wu; Wen-Mei Li; Qiang Xu; Xiao-Ping Yi; Da-He Zhang; Ming-Zhe He; Yu-Hong Ren (Journal of Insect Physiology, 2025)

A study on prediction of radioactive fallout based on the WRF-NAQPMS model - Feifei Li; Qiang Liu; Wei Liu; Zhaoru He; Baozhu Ge; Ying Zhang; Nuohang Liu; Yangchao Li; Ming Yang (Journal of Environmental Radioactivity, 2025)

Experimental insights into iron and manganese transformation in soil during groundwater fluctuations - Fei Xu; Peiyue Li; Qiang He; Jing Ning; Xiaofei Li (Journal of Contaminant Hydrology, 2025)

Exploring ancient underground remains using the electrical resistivity method: A case study in Shangqiu, China - Tao Tao; Peng Han; Zhentao Yang; Kaiyan Hu; Qiang Zu; Yihua Zhang; Shuangshuang Li; Yufan Hu; Wen Zhong; Bingbing Han; Ruidong Li; Zhanxiang He (Journal of Applied Geophysics, 2025)

Interactions between raw dark tea chemistry and dominant fungi shape Hei brick tea quality - Yating Guo; Haijing Cui; Xinxin Wang; Haowei Guo; Xinyu Feng; Anran Yan; Yani Pan; Lixin He; Liping Liu; Kexin Zhang; Hua Fang; Hesham R. El-Seedi; et al. (International Journal of Food Microbiology, 2025)

Blending coffee white tea with flower flavor rooibos to mask the burnt flavor - Xinxin Wang; Zhihang Weng; Xinyu Feng; Huichun Ye; Helin Lv; Anran Yan; Yani Pan; Yiliang Wei; Tianyuan Chen; Lixin He; Yunyun Yang; Haowei Guo; et al. (Food Chemistry, 2025)

Integrating transcriptomics and molecular docking to reveal the antibacterial mechanism of cedrol against methicillin-resistant Staphylococcus aureus - Yilin Wang; Yaluan He; Ying Qian; Han Hu; Qiang Hua; Yongkang Wu; Bin Shi; Dongsheng Li; Zhijie Liu (Food Bioscience, 2025)

Sedimentation substantially buries more carbon than nitrogen or phosphorus in the Three Gorges Reservoir, China - Jinlin Li; Xiubin He; Jie Wei; Qiang Tang; Yuhai Bao; Xin Gao; Ziqiang Mao; Xiaoya Tang; Ping Huang; Shengjun Wu (Environmental Research, 2025)

Polyimide porous thermoelectric fibers based on sheath core structure: A new self-powered material for early fire warning and flame retardant protection - Xinbin Ji; Yulong Xiang; Jing Guo; Fucheng Guan; Da Bao; Qiang Yang; Zheng Li; Yihang Zhang; Xin Zhang; Jiahao He (Chemical Engineering Journal, 2025)

Novel recovery of the ability of sulfureted Fe Ti spinel to capture high concentrations of gaseous Hg0 from smelting flue gas by washing: Performance and mechanism - Pengjian Lv; Jialiang Zhou; Yu Bin; Qiang Li; Liutao Zong; Jianghuai He; Haoshuai Wang; Bing Liu; Shijian Yang (Chemical Engineering Journal, 2025)

Plastic optical fiber-driven distributed photocatalysis in NWP-PDA-RGO-TiO₂ filter for simultaneous formaldehyde degradation, particulate removal and bioaerosol inactivation - Yunhe Li; Ruiqing Shen; Weidong He; Qiang Luo; Xiaotong Zhou; Jinshuo Yang; Jingxian Liu (Chemical Engineering Journal, 2025)

Laser-induced ash-deposited silicone rubber surfaces with synergistic micro/nanostructures for enhanced superhydrophobicity and anti-/de-icing performance - Yangyang Jia; Anling Li; Zehua Xu; Kai Qi; Jiankang Zhong; Fapeng Zhang; Qi Guo; Qiang He (Chemical Engineering Journal, 2025)

Synergistic effects of slow-release fertilizer and biochar on crop yield and soil carbon-nitrogen dynamics under reduced nitrogen input - Lianhao Zhao; Wen Yin; Qiang Chai; Pan Li; Zhipeng Guo; Zhilong Fan; Falong Hu; Cai Zhao; Aizhong Yu; Pingxing Wan; Wei He; Hong Fan; et al. (Agriculture, Ecosystems & Environment, 2025)

Glutathione contributes to alleviating hepatic injury via host-microbiome interaction and CAR-dependent pathway - Xuan Xiang; Siwei Liu; Houfu Wang; Chenyu Wang; Wentao Zhou; Heshu Chen; Yanzhong Feng; Xinmiao He; Gang Xu; Qiang Zhao; Tiejun Li; Di Liu; et al. (Science China Life Sciences, 2025)

Unraveling the links between molecular weight and multidimensional dynamics of dissolved organic matter in the runoff from gentle sloping land under rainfall - Guo Chen; Hao Wang; Qiang Zhang; Chao Chang; Fei Wang; Qingwei Zhang; Jian Wang; Yu Pang; Ming Li; Biao Zhu; Ding He (Water Research, 2025)

Adaptive noise cancellation based on CEEMDAN-LMS for pipeline leak location under low SNR - Shuaiyong Li; Qiang Fu; Pei Shen; Zhongfei He (Process Safety and Environmental Protection, 2025)

Rapid self-assembled electroactive biohybrid cathode-driven electron transfer for enhanced uranium bioremediation - Keng-Qiang Zhong; Le-Yi Chen; Meng Li; Xing Chen; Xing Lu; Yu-Chen Yang; Hao-Wen He; Bao-Hua Jing; Hong-Guo Zhang; Jia Yan; Yi-Feng Zhang (Journal of Hazardous Materials, 2025)

Identification and analysis of specialized metabolites, including 1,2-Di-O-Galloyl-(4,6-(S)-Hexahydroxydiphenoyl)-β-d-Glucopyranose, in ancient tea plants from Yunnan, China - Yueqi Wang; Liyuan Wang; Mengdi He; Liubin Wang; Liyun Wu; Zhuozhuo Mao; Yongxin Wang; Qiang Li; Kang Wei (Food Chemistry, 2025)

Hierarchically shortened b-axis ZSM-5 nanosheet endows super catalytic stability for methanol-to-hydrocarbons reaction - Zhan Liu; Ying-Jun He; Zhi-Yi Hu; Jia-Min Lyu; Shen Yu; Yu-Hang Song; Xiao-Qiang Liao; Zhi-Wen Yin; Ming-Hui Sun; Yu-Chun Zhi; Li-Hua Chen; Bao-Lian Su (Chemical Engineering Journal, 2025)

Impaired Synaptic Plasticity Mediated by Decreased GLUT1 in Hippocampal Astrocytes is Involved in Postoperative Cognitive Dysfunction in Elderly Mice - Zi-Yi Li; Qiang Liu; Xiao-Tian Shi; Xin-Hao Jiao; Yue Zhou; Chen Chen; Wei-Feng Wu; Wei Dong; Yong-Kang Qiu; Yi-Qi Liu; Chun-Hui Jin; Ao Sun; et al. (Molecular Neurobiology, 2025)

Design and synthesis of glycyrrhetinic acid glycosides against acute lung injury and pulmonary fibrosis - Wei Li; Jianrong Liu; Tianbo Wu; Xin Qiang; Yijie Peng; Quanyi Zhao; Dian He (Molecular Diversity, 2025)

Silicon supplementation via carriers to enhance diatom competition with cyanobacterial blooms and remediate eutrophic waters - Rui Zhou; Bang Xiao; Li Zhao; Yangyang Tang; Wei Yang; Huazu Liu; Xiangdong Zhang; Chaowei Yuan; Xinqi Wang; Xizi Long; Qiang He; Wei Li (Water Research, 2025)

Study on the temperature field in coal-rock mass and the temporal and spatial evolution of overburden damage in the tar-rich coal pyrolysis zone - He Zhang; Qiang Sun; Jishi Geng; Qingmin Shi; Shengze Xue; Jiyuan Duan; Kexin Yu; Pei Li; Aifang Pan (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Underlying mechanism of asphaltene aggregates disaggregation via hydrogenation at multiple scales - He Bian; Huiming Zhang; Qiang Tong; Honghong Zhang; Renfei Chu; Fang Wang; Lijuan Zhang; Dazhi Li; Zhijie Gao; Zunbin Duan (Fuel, 2025)

Soil organic carbon improvement for mitigating crop yield losses under global warming - Qinsi He; Linchao Li; Yu Shi; Puyu Feng; Ke Liu; Shengwei Zhang; De Li Liu; Zikui Wang; Matthew Tom Harrison; Sien Li; Qiang Yu; Kadambot H.M. Siddique (European Journal of Agronomy, 2025)

Construction of dynamically regulated biomimetic nanochannels inspired by temperature-sensitive proteins for intelligent release of pesticides - Haonan Qu; Jiaxin Quan; Ehsan Bahojb Noruzi; Haifan Zhang; Cuiguang Ma; Qiang He; Yuchao Liu; Zhihang Zhao; Chenyu Su; Haibing Li (Chemical Engineering Journal, 2025)

Engineered macrophage-targeted germacrone-bearing nanosheet achieves synergistic treatment of acute kidney injury through macrophage polarization modulation and oxidative stress alleviation - Yunguang Wang; Shaoting Wang; Qikai Luo; Yourou Zhou; Xingchen Li; Yiwei Shang; HuaiYu Wang; Egor Y. Plotnikov; Xinyu Liao; Wei Feng; Qiang He; Juan Jin (Chemical Engineering Journal, 2025)

Multi-crosslinked network enables robust cellulose/chitosan composite aerogel for triboelectric sensor with humidity adaptivity - Jiahao Kang; Qiangli Zhao; Min Mao; Yugen Wang; Qiang Mu; Jie Tao; Xiaoliang Zhao; Xinhai He; Jianwei Li (Chemical Engineering Journal, 2025)

Photo-thermal synergistic catalytic carbon dioxide reduction on WN-WO3/In2O3 catalyst with controllable product selectivity - Yuhan Lin; Qiang Wang; Tongtong Li; Yi He; Wei Peng; Chuanyi Wang (Chemical Engineering Journal, 2025)

Bimetallic nanoplatform inducing robust cuproptosis to enhance tumor immunotherapy via immunogenic activation and tumor microenvironment reprogramming - Meng Dang; Qiang Li; Xuzhi Shi; Ao He; Xiaoye Li; Zhuo Dai; Jiaxin Rui; Weiqing Ning; Zhaogang Teng; Heng Dong; Yongbin Mou (Chemical Engineering Journal, 2025)

Gradient-functionalized PET filter with side-emitting polymer optical fibers for triplex synergistic air purification: photocatalytic degradation, particulate filtration, and antimicrobial performance - Yunhe Li; Ruiqing Shen; Weidong He; Qiang Luo; Xiaotong Zhou; Jinshuo Yang; Chunyang Wang; Jingxian Liu (Building and Environment, 2025)

MicroRNA- 3135b as a Therapeutic Target and Clinical Biomarker for Stroke: Regulation of the NF-κB/IKKβ Signaling Pathway - Shaobo Liu; Qiang He; NaNa Zhang; Yongbiao Li; Qingshan Liu (Molecular Neurobiology, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Making Restoration Effective for Dynamic Coastal Wetlands - Qiang He; Zu'ang Li; Chris S. Elphick; Yizhou Sun; William J. Sutherland; Nigel G. Taylor; Kerstin Wasson (Global Change Biology, 2025)
To halt and reverse the trends of ecosystem loss and degradation under global change, nations globally are promoting ecosystem restoration. Restoration is particularly crucial to coastal wetlands (including tidal marshes, mangrove forests, and tidal flats), which are among the most important ecosystems on Earth but have been severely depleted and degraded. In this review, we explore the question of how to make restoration more effective for coastal wetlands in light of the often‐overlooked dynamic nature of these transitional ecosystems between land and ocean. Currently, restoration efforts have focused on removing anthropogenic threats, habitat reconstruction, and planting foundation species, often with mixed success and high costs. The challenges largely lie in the abiotic and biotic dynamics of these transitional ecosystems, including (i) fluctuating environmental stresses, (ii) variable trophic and nontrophic species interactions, (iii) changing connectivity with adjacent land, sea, and freshwater systems, and (iv) accelerating climate change, including sea level rise, droughts, and storms. Future restoration should explicitly account for these abiotic and biotic dynamics from threat removal to habitat reconstruction, assisted succession, and post‐restoration management. We highlight novel yet practical measures to enhance success. In the coming decades, bending the curve of coastal wetland loss and degradation globally also requires better understanding of the abiotic and biotic dynamics of these transitional ecosystems prone to change, using this understanding to develop innovative restoration approaches, and applying new approaches to upscale restoration in synergy with socioeconomic development. Critical to these efforts are collaborations among ecologists, policymakers, business investors, restoration practitioners, and the many millions of people dependent on coastal wetlands.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Particulate matter continuum as distinct colonization niches for antibiotic resistome, mobilome and virulence factor genes in wastewater: Insights from full size-fractionated partitioning - Kaifeng Yu; Peng Li; Zhimin Qiang; Ping Chen; Yiliang He (Journal of Hazardous Materials, 2025)

Rainfall-mediated CO2 flux dynamics in the Three Gorges Reservoir: Dominance of enzyme activity over carbon degradation and algal dynamics under dissolved organic carbon inputs - Kaikai Deng; Yixuan Li; Peng Yan; Bin Chen; Guijiao Lin; Qiang He; Jinsong Guo (Journal of Environmental Chemical Engineering, 2025)

A novel multi-dimensional viscoelastic mitigation device: Shake table tests and numerical assessment of precast concrete sandwich wall panel structure - Jia-Xuan He; Zhao-Dong Xu; Zhong-Wei Hu; Lian-Yu Zhang; Qiang-Qiang Li; Yao-Rong Dong; Gabriele Milani (Engineering Structures, 2025)

Rapid plutonium recovery from high-acidity spent fuel solution using quaternary ammonium-functionalized silica resin - Ningchao Zheng; Linxin Zheng; Qiang Wu; Wenlong Li; Xuexiang He; Lifeng Chen; Xiangbiao Yin; Watabe Hiroshi; Yuezhou Wei (Chemical Engineering Journal, 2025)

Effects of nitrogen deposition on temporal stability and resistance of the alpine steppe plant communities on the Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Bing Zhang; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; Ke Zhang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Assessment of Soil Organic and Inorganic Carbon Stocks in Coastal Salt Marshes of China: Key Mechanisms Elucidated - Lele Wu; Zhaoliang Song; Zhineng Xiao; Xinyu Zhang; Lukas Van Zwieten; Laodong Guo; Zimin Li; Xiaomin Yang; Xiangwei Zhao; Yidong Wang; Ding He; Weiqi Wang; et al. (Global Change Biology, 2025)
Coastal salt marsh ecosystems are among the most important blue carbon (C) sinks. However, due to disparate data sources, limited sample sizes, and inconsistent methodologies, large variations exist in blue C stock estimation. Furthermore, studies focus on soil organic carbon (SOC), with minimal attention given to soil inorganic carbon (SIC). We conducted an intensive field survey across 114 sites along approximately 5000 km of China's coastline, investigating all C stock sectors associated with Phragmites australis , Spartina alterniflora , Suaeda salsa , and mudflats to better explore the biogeographical patterns and drivers of SOC and SIC and to estimate regional and national C pools. The results revealed significant spatial heterogeneity in SOC and SIC densities in the top 100 cm of soil, ranging from 20.89 to 246.95 Mg ha −1 and 0 to 249.33 Mg ha −1 , respectively. These densities varied as a function of wetland location, vegetation type, climatic zone, and soil depth. The SOC and SIC content were jointly dependent on soil properties, climatic factors, and vegetation types. Soil available silicon was the most important environmental variable controlling both SOC and SIC. Climatic factors and vegetation types mainly controlled SOC and SIC through their interaction with soil properties. Increased vegetation productivity increased the SOC pool but decreased the SIC pool. Therefore, vegetation restoration in coastal wetlands should target suitable areas, such as soil pH

Impact of different green manure crops or fallow on yield and quality of a Chinese cabbage - Cai Zhao; Li Jin; Hong Fan; Yu Jia; Zhilong Fan; Wen Yin; Aizhong Yu; Falong Hu; Wei He; Qiang Chai (Plant and Soil, 2025)

Juvenile macular degeneration in nonhuman primates generated by germline knockout of ABCA4 gene - Ya Ma; Qiang Lin; Hai-Long He; Yi-Xin Liu; Min Li; Xiao-Hui Zhang; Zi-Bing Jin (Science Bulletin, 2025)

Bombella intestini: A probiotic honeybee(Apis mellifera)gut bacterium - Meng Jie Jin; Andrew B. Barron; Sheng Yang He; Xu Jiang He; Qiang Huang; Li Zhen Zhang; Zi Long Wang; Xiao Bo Wu; Wei Yu Yan; Zhi Jiang Zeng (Journal of Insect Physiology, 2025)

A new approach to color correction and equalization for generating mars global color image mosaics from Tianwen-1 MoRIC images - Xin Ren; Xiaoxia Zhang; Wangli Chen; Wei Yan; Xingguo Zeng; Xu Tan; Xingye Gao; Qiang Fu; Lin Guo; Qing Zhang; Zhaopeng Chen; Guobin Yu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Inverse thermoreversible methylcellulose-based and recyclable conductive gel for versatile triboelectric nanogenerator with rough interface under complex conditions - Jia Yang; Chenyu Li; Zhenyang Li; Zhiwen Liu; Wenjie He; Yue Xiao; Shuzheng Liu; Gang Qin; Aiguo Zhou; Qiang Chen (Chemical Engineering Journal, 2025)

Humidity-adaptive microcrystalline cellulose triboelectric composite film with engineered microstructures for sensing and energy harvesting - Min Mao; Qiangli Zhao; Jiahao Kang; Qiang Mu; Jie Tao; Xiaoliang Zhao; Xinhai He; Jianwei Li (Chemical Engineering Journal, 2025)

Deciphering the role and mechanism of zero-valent iron on medium-chain fatty acid production from acetate via chain elongation in microbial electro-fermentation - Haifeng Qiang; Zhihong Liu; Zhijun Dong; Dengfei Li; Zhangwei He; Wenzong Liu; Xiuping Yue; Aijuan Zhou (Chemical Engineering Journal, 2025)

Immunogenicity assessment of a swine fever-swine circovirus type 2 duplex vaccine candidate created using the Zera nanoparticle delivery method - Pu Wang; Gang Zhang; Qiang Liu; Lingling Jiang; XiaoXia Niu; Min Fang; Weifeng Gao; Yulong He; Yong Li; Jianhong Shu; Sinong Zhang (Veterinary Immunology and Immunopathology, 2025)

Impact on nonlinear runoff of LID facilities and parameter response in the TVGM model - Pengjun Li; Luwen Zhuang; Kairong Lin; Dunxian She; Qiang Wang; Wei Luo; Jianliang He; Jun Xia (Journal of Hydrology, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Flavor perception and biological activities of bitter compounds in food - Tingting Luo; Yanni He; Lanxin Jiang; Li Yang; Xiaoyan Hou; Guanghui Shen; Qiang Cui; Jie Yu; Jingxuan Ke; Shanbo Chen; Zhiqing Zhang (Food Chemistry, 2025)

LC-MS/MS-based metabolomics and multivariate statistical analysis reveal the mechanism of yeast extracellular proteases on myofibrillar protein degradation, metabolite development and sensory characteristics improvement - Danni Li; Yiqi Liang; Qiang Xia; Daodong Pan; Lihui Du; Jun He; Yangying Sun; Ying Wang; Wei Wang; Jinxuan Cao; Changyu Zhou (Food Microbiology, 2025)

Pillar[5]arene@AuNP-Functionalized, Magnetically-Propelled Helical Micromotors for On-The-Fly Electrochemical Biosensing of p53 DNA Sequence - Zhiyong Ran; Yue Li; Xiankun Lin; Qiang He (Chemical Engineering Journal, 2025)

Dynamic Response of Rock Cut Slopes Under Train Loading: Insights from Uniaxial Wheel Load Tests and 3D Modeling - Weili Zhang; Qiang He; Li Deng; Cheng Qian; Qihai Yao (Geotechnical and Geological Engineering, 2025)

Weighted Gene Co-expression Network Analysis and Machine Learning Validation for Identifying Major Genes Related to Sjogren’s Syndrome - Qiang Luo; Kaiwen Wu; He Li; Han Wang; Chen Wang; Demeng Xia (Biochemical Genetics, 2025)

The characteristics and distributions of alkaline-volcanic lithofacies of Fengcheng Formation in Mahu Sag, Junggar Basin - Zhi-qi Wu; Fu-sheng Yu; Jian Li; Qiang Liu; Xin Liu; Nai-xiang He (Applied Geophysics, 2025)

COP1 Overexpression Attenuates Nociceptive Behaviors and Neuroinflammation in Cancer-Induced Bone Pain by Suppressing c/EBPβ - Dan-Yang Li; Lin Liu; Shao-Jie Gao; Dai-Qiang Liu; Long-Qing Zhang; Jia-Yi Wu; Fan-He Song; Xin-Yi Dai; Ya-Qun Zhou; Wei Mei (Journal of Neuroimmune Pharmacology, 2025)

The characteristics of reservoir spaces and distribution of “sweet spots” in Fengcheng Formation of Mahu Sag, Junggar Basin - Zhi-qi Wu; Fu-sheng Yu; Jian Li; Qiang Liu; Xin Liu; Nai-xiang He (Applied Geophysics, 2025)

Copper-catalyzed C–C bond cleavage coupling with C N bond formation toward mild synthesis of lignin-based benzonitriles - Qi Luo; Shenglong Tian; Qian Qiang; Fei song; Wentao Su; Haiyan He; Qingda An; Changzhi Li (Journal of Environmental Sciences, 2025)

No tillage with straw mulching enhanced radiation use efficiency of wheat via optimizing canopy radiation interception and photosynthetic properties - Pan Li; Wen Yin; Lianhao Zhao; Pingxing Wan; Zhilong Fan; Falong Hu; Yunyou Nan; Yali Sun; Hong Fan; Wei He; Qiang Chai (Field Crops Research, 2025)

Pore space optimization of hybrid ultramicroporous material for exceptional one-step C2H4 purification from C2H2/CO2/C2H4 mixture - Hong-Xiang Nie; Hong-Wei Chen; Ting Wang; Hongliang Huang; Qiang Gao; Mei-Hui Yu; Jian Zhu; Li-Bo Li; Zhenjie Zhang; Ze Chang; Xian-He Bu (Chemical Engineering Journal, 2025)

Constructing efficient PVDF-HFP-based intercalated composite solid electrolytes via competitive solvation structures for rechargeable lithium metal batteries - Yutong Jing; Shen Liu; Cheng Li; Qiang Lv; Daming Liu; Manxing Huo; Bochen Wu; Siyuan Liu; Yuhang Zhang; Mingyu Yin; Zhipeng He; Dianlong Wang; et al. (Chemical Engineering Journal, 2025)

Environmental fate of antibiotic resistance genes in livestock farming - Jiali Sun; Xiaoqi Wang; Yuanjie He; Mengting Han; Mei Li; Siyue Wang; Jia Chen; Qiang Zhang; Baowei Yang (Archives of Microbiology, 2025)

Large-scale genomic and phenomic analyses of modern cultivars empower future rice breeding design - Xiaoding Ma; Hao Wang; Shen Yan; Chuanqing Zhou; Kunneng Zhou; Qiang Zhang; Maomao Li; Yaolong Yang; Danting Li; Peng Song; Cuifeng Tang; Leiyue Geng; et al. (Molecular Plant, 2025)

Effects of triclosan on microalgal-bacterial symbiosis system operating in stable phase: Performances and mechanisms - Qiang Chao; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian (Journal of Water Process Engineering, 2025)

Risk-based environmental assessment of atmospheric impact in the hydrometallurgical recycling of LFP batteries: A comparative analysis of operational scenarios - Yunbin Sun; Zaohong Zhou; Hongjun He; Qiang Li (Journal of Cleaner Production, 2025)

A haplotype-resolved genome assembly of tetraploid Medicago sativa ssp. falcata - Wanying Li; Xuanzhao Li; Wei Li; Haibo Yang; Diandian Guo; Ting Guo; Yingying Meng; Qiang He; Hao Lin; Huilong Du; Lifang Niu (Science China Life Sciences, 2025)

PpBOR1 is critical for the excess borate tolerance of Physcomitrium patens - Ishfaq Ahmad; Xuejia Sun; Yangyang Yu; Fangni Jia; Yizuo Li; Qiang Lv; Yong Hu; Fang Bao; Yikun He (Plant Cell Reports, 2025)

Identification, distribution, and mechanisms of large landslides in the upper reaches of Jinsha River - Weihua Zhao; Fengjiao Wang; Qiang Xu; Jianjun Zhao; Fuling Zhang; Weile Li; Xiujun Dong; Jian Yang; Decun Guo; Wantong He (Bulletin of Engineering Geology and the Environment, 2025)

Context dependencies in the responses of plant biomass and surface soil organic carbon content to nitrogen addition and precipitation change within alpine grasslands - Fawei Zhang; Hongqin Li; Jingbin Zhu; Chunyu Wang; Yunlong He; Juntao Zhu; Qiang Yu; Huakun Zhou; Yingnian Li; Naishen Liang (Agriculture, Ecosystems & Environment, 2025)

Effects of Water Temperature, Light Intensities and Photoperiod on the Survival and Growth of Juvenile Schizothorax irregularis and Diptychus maculates - Zhulan Nie; Huimin Hao; He Zhao; Nianhua Zhao; Li Li; Zhuang Qiang; Syeda Maira Hamid; Jie Wei (Fishes, 2025)
An experimental ecological method was used to study the effects of water temperature, photoperiod, and light intensity on the survival, feeding, and growth of juvenile Schizothorax irregularis and Diptychus maculates. The Box–Benhnken experiment was designed to predict the optimal environmental conditions for juvenile growth. With the maximum specific growth rate at 15 °C and a photoperiod of LD16:8, the results demonstrated that the juvenile S. irregularis had a survival rate of over 85% in water temperatures ranging from 5 to 25 °C. A daily light duration of 15.86 h and a light intensity of 1166.28 lx, with the water temperature maintained at 10.45 °C, allowed the juvenile S. irregularis fish to attain the optimal circumstances for growth and survival. At water temperatures below 25 °C, the juvenile D. maculates exhibited maximum specific growth rates at 10 °C and LD16:8 light period. Additionally, as the light intensity reached 1000 lx, the juvenile fish grew better. Furthermore, the juvenile D. maculates fish achieved theoretically optimal survival and growth circumstances when the water temperature was maintained at 10.87 °C with a light period of 15.0.5 h per day and a light intensity of 1474.68x. The results showed that both fish species may be raised in captivity in highland regions, but precise control over water temperature is required.

Inversion of Rayleigh Surface Wave Dispersion Curves Based on Deep Learning - Bing-kai Zhao; Yan-li Ding; Jia-qiang Song; Pei-yan He; Shao-yuan Bai (Applied Geophysics, 2025)

DNA damage triggers heritable alterations in DNA methylation patterns in Arabidopsis - Jinchao Li; Wenjie Liang; Xin-Qiang He; Weiqiang Qian (Molecular Plant, 2025)

Genomic analysis of Vreelandella sp. F11 reveals its role in alginate utilization - Xin-Xiao Qu; Yu-Qi Zhang; Fei-Yu He; Xi-Ying Zhang; Peng Wang; Fei Xu; Yu-Qiang Zhang; Long-Sheng Zhao; Ping-Yi Li; Fang Zhao (Marine Genomics, 2025)

Impact of eight extruded starchy whole grains on glycemic regulation and fecal microbiota modulation - Fang Fang; Yu-Xin He; Hao-Qiang Wang; Yan-Li Zhang; Ya-dong Zhong; Xiao-Tian Hu; Shao-Ping Nie; Ming-Yong Xie; Jie-Lun Hu (Food Hydrocolloids, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Effect of capsaicin on anaerobic lactic acid production from food waste - Yiming Hu; Tanglong Zhang; Maoli Hu; Jie Chen; Chang Liu; Li Gu; Qiang He; Lin Li (Chemical Engineering Journal, 2025)

Revealing the regulation mechanism of carbon dots on Ni(OH)2 for optimizing methanol electrooxidation activity - Man Zhao; Liwu Qiang; Meng Bai; He Xiao; Li Zhang; Junming Zhang; Tianjun Hu; Baoliang Lv; Shengxiang Wang; Jianfeng Jia (Chemical Engineering Journal, 2025)

Structural design and biomechanical analysis of a combined titanium and polyetheretherketone cage based on PE-PLIF fusion - Lei Ma; Yutang Xie; Kai Zhang; Jing Chen; Yanqin Wang; Liming He; Haoyu Feng; Weiyi Chen; Meng Zhang; Yanru Xue; Xiaogang Wu; Qiang Li (Medical & Biological Engineering & Computing, 2025)

A gap-free complete genome assembly of oat and OatOmics, a multi-omics database - Wei Li; Yu Wang; Jianan Liu; Qiang He; Yue Zhou; Minghao Li; Ningkun Liu; Hanfei Liang; Yange Yun; Zhizhong Gong; Huilong Du (Molecular Plant, 2025)

Analysis of growth physiological changes and metabolome of highland barley seedlings under cadmium (II) stress - Yingyong Luo; Xian Huang; Ajia Sha; Jing He; Xiaodie Chen; Wenqi Xiao; Lianxin Peng; Liang Zou; Bingliang Liu; Qiang Li (Environmental Pollution, 2025)

Regulation of chain conformation and synergistic effect of auxiliary groups towards polyamidoxime for highly efficient uranium extraction from seawater - Hao Peng; Xiaoyu Li; Lina Lv; Tingting Deng; He Chen; Lu Wang; Qiang He; Caiping Dang; Lianggui Bao; Yihao You; Fangting Chi (Chemical Engineering Journal, 2025)

Preparation of CaMgAl hydrotalcite from electrode aluminum-foil industrial wastewater for high-temperature CO2 capture - Tiantian Li; Qiang Wang; Yonghu He; Jinpeng Ma; Xin Wang; Jing Bai; Ahebai Jieensi; Xueqin Li; Zhaomin Li; Feng Yu (Chemical Engineering Journal, 2025)

Current knowledge of vertebral osteomyelitis: a review - Xuanying Zou; Xiaoyan Li; Kang He; Qiang Song; Ruofeng Yin (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Application of green manure combined with synthetic nitrogen fertilizer enhances soil aggregate stability in an arid wheat cropping system - Guocui Wang; Hanting Li; Falong Hu; Wen Yin; Zhilong Fan; Hong Fan; Yali Sun; Wei He; Qiang Chai (Applied Soil Ecology, 2025)

First discovery of dinosaur tracks from the Lower Cretaceous Duoni Formation in eastern Tibet, China - Yangui Li; He Zhao; William J. Foster; Yue Yu; Lida Xing; Qiang Ye; Chuanshang Wang; Huazhou Yao (Cretaceous Research, 2025)

Diversity patterns and community assembly of aquatic macroinvertebrates in permanent and temporary inland saline-alkaline wetlands - Qiang Guan; Yujuan Kang; Fengzhi He; Zhengfei Li; Zhenshan Xue; Haitao Wu (Biodiversity and Conservation, 2025)

Soil legacies of genotypic diversity enhance population resistance to water stress - Zekang Liu; Cai Cheng; Qun Zhang; Xing Tian; Lin Jiang; Kerri M. Crawford; Xiang Liu; Jianquan Liu; Qiang He; Bo Li; Jihua Wu (Ecology, 2025)
While the positive relationship between plant diversity and ecosystem functioning is frequently observed and often attributed to direct plant–plant interactions, it remains unclear whether and how the effects of plant diversity endure through soil legacy effects, particularly at the level of genotypic diversity. We manipulated the genotypic diversity of Scirpus mariqueter and tested its soil legacy effects on a conspecific phytometer under low‐ and high‐water availability conditions. We found that genotypic diversity enhanced phytometer productivity through soil legacies, with stronger effects under low‐water availability conditions, improving its resistance to water stress. Moreover, this effect was attributed to the association between asexual and sexual reproductive strategies by increasing ramet number to ensure plant survival under low‐water availability and promoting sexual reproduction to escape stress. The observed diversity effects were primarily associated with increased levels of microbial biomass in soils trained by populations with diverse genotypes. Our findings highlight the importance of plant genotypic diversity in modulating ecosystem functioning through soil legacies and call for management measures that promote genetic diversity to make ecosystems sustainable in the face of climate change.

Effects of arginine family amino acids supplementation on growth, whole-body amino acid profiles, antioxidant capacity, and gene expression of juvenile largemouth bass (Micropterus salmoides) - Xueyao Luan; Xinyu Li; Jiale He; Hanying Xu; Wenping Feng; Qiang Chen; Tao Han; Jiteng Wang (Aquaculture, 2025)

Improved anaerobic digestion of food waste under ammonia stress by side-stream hydrogen domestication - Yi Wang; Haoyang Li; Keke Ding; Xueyu Zhao; Miao Liu; Linji Xu; Li Gu; Jinze Li; Lin Li; Qiang He; Jianjun Liang (Water Research, 2025)

Enhance Fe(III) reduction in sludge fermentation for vivianite formation using exogenous H2 assisted by activated carbon - Haoyang Li; Yi Wang; Linyan He; Yifei Wang; Miao Liu; Li Gu; Shaowu Liu; Jinze Li; Yushu Yang; Ruizhi Wang; Qiang He (Water Research, 2025)

Characterizing flavor development in low-salt Chinese horse bean-chili paste through integrated metabolomics and metagenomics - Li Jiang; Siwei Shen; Aoteng Zuo; Yuanlong Chi; Yunhao Lu; Qiang He (Food Chemistry, 2025)

The necessity of enhancing the human health risk assessment of 1,3,6,8-tetrabromocarbazole: Based on in vitro experiments, theoretical calculations, and model predictions - Junchao Ma; Mengxi Ren; Jiangyan He; Pengcheng Shi; Dawei Xing; Xiaochao Tang; Qiang Yang; Yunhong Song; Qiang Li; Tingting Zhao; Chao Qin; Xiaoju Chen (Environmental Pollution, 2025)

A strategy for anti-icing and drag reduction in marine applications via in situ gas injection - Duanyi Zhu; Meng Wang; Qiang Liu; Guojun Liu; Xiuzhi He; Rongqi Wang; Lidong Zhang; Zijian Song; Qian Li; Qiang Li; Xiaoqin Zhou (Chemical Engineering Journal, 2025)

Physiological and transcriptomic responses of microalgal-bacterial co-culture reveal nutrient removal and lipid production during biogas slurry treatment - Dan Li; Ruiqing Liu; Ying Chu; Qiang Wang; Meilin He; Changhai Wang (Bioresource Technology, 2025)

Kinetic modeling of sulfonamide degradation by UV/H2O2: Deduction of ROH,UV modeling and application - Xinxin Qin; Xinyue Liu; Yi He; Yichun Zhu; Zuwen Liu; Wentao Li; Mengkai Li; Zhimin Qiang; Junfeng Lian (Chemosphere, 2024)

Biogenic amorphous FeOOH activated additional intracellular electron flow pathways for accelerating reductive dechlorination of tetrachloroethylene - Yang Yu; Ang Li; Sheng-Qiang Fan; He-Ping Zhao (Water Research, 2024)

Hydrochemical characteristics of groundwater and their controlling mechanisms in irrigation and non-irrigation areas - A comparative study in the Guanzhong Plain of China - Qiang He; Peiyue Li; Yuanhang Wang; Xiaodong He; Misbah Fida; Vetrimurugan Elumalai (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Ferrihydrite optimizing Feammox inoculum to enhance ammonia removal from concentrate wastewater through continuous upflow anaerobic sludge blanket (UASB) - Linji Xu; Lin Li; Jianxi Liu; Xingzu Wang; Yanping Zhao; Jujiao Zhao; Li Gu; Qiang He; Xinzhu Wang; Jinhua Zhang (Journal of Environmental Chemical Engineering, 2024)

Structural and gel property changes in chicken myofibrillar protein induced by argon cold plasma-activated water: With a molecular docking perspective - Junqi Li; Wei Rao; Yangying Sun; Changyu Zhou; Qiang Xia; Jun He; Daodong Pan; Lihui Du (Food Research International, 2024)

Urine is better for rare earth elements bimonitoring in long-term exposed population: An exposure-response relationship study - Zhizhou He; Li Liu; Ting Wang; Cailan Zhou; Xuewei Zhang; Nan Wu; Mengmeng Xu; Jianqiong Gao; Bin Li; Yonglan Wang; Qiang Zhi; Chenguang Zhang; et al. (Environmental Research, 2024)

Comprehensive insights into synergistic effects of cotton stalk and polyethylene in hydrothermal liquefaction process - Sheng-Ren Li; Guo-Qiang Zhu; Chao He; Lujiang Xu; Janusz A. Kozinski; Zhen Fang (Chemical Engineering Journal, 2024)

Lignin-derived compounds assisted with Kocuria marina H-2 and Pseudomonas putida B6-2 co-culture enhanced naphthalene biodegradation - Jia-Qi Cui; Zhi-Qiang He; Kai Chen; Samuel Ntakirutimana; Zhi-Hua Liu; He Bai; Bing-Zhi Li; Ying-Jin Yuan (Bioresource Technology, 2024)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Unveiling the overlooked small-sized microbiome in river ecosystems - Fang-Zhou Gao; Li-Xin Hu; You-Sheng Liu; Lu-Kai Qiao; Zi-Yin Chen; Jian-Qiang Su; Liang-Ying He; Hong Bai; Yong-Guan Zhu; Guang-Guo Ying (Water Research, 2024)

Improved identification and monitoring of meteorological, agricultural, and hydrological droughts using the modified nonstationary drought indices in the Yellow River Basin of China - Ben Niu; Yi Li; De Li Liu; Lulu Xie; Lei Wang; Xiaohui Jiang; Hao Feng; Qiang Yu; Jianqiang He; Haixia Lin (Journal of Hydrology, 2024)

Different preferences for inorganic carbon influence CO2 flux under Cyanobacteria or Chlorophyta dominance days - Kai-Kai Deng; Yi-Xuan Li; Peng Yan; Yuan-Chen Huo; Hao Yang; Bin Chen; Qiang He; Gui-Jiao Lin; Jin-Song Guo (Journal of Environmental Management, 2024)

Multi-tracer evidence of hydrology and primary production controls on dissolved organic matter composition and stability in the semi-arid aquatic continuum - Mingyu Shao; Zaihua Liu; Hailong Sun; Haibo He; Qiang Li; Sibo Zeng; Junyao Yan; Yan Fang; Qiufang He; Hailong Liu; Liangxing Shi; Chaowei Lai (Geochimica et Cosmochimica Acta, 2024)

Weakly solvated electrolyte enables the robust solid electrolyte interface on SiOx anodes for lithium-ion battery - Zuojie Xu; Rong Huang; Pengfei Huang; Chaowei He; Shenwen Liu; Haonan Zheng; Wenlong Song; Lu Shi; Weiwei Gao; Dan Li; Hui Huang; Hangjun Ying; et al. (Chemical Engineering Journal, 2024)

Augmented Mitochondrial Transfer Involved in Astrocytic PSPH Attenuates Cognitive Dysfunction in db/db Mice - Hongli Ma; Shuxuan He; Yansong Li; Xin Zhang; Haiqing Chang; Mengyu Du; Chaoying Yan; Shiqiu Jiang; Hui Gao; Jing Zhao; Qiang Wang (Molecular Neurobiology, 2024)

Erratum to: Effects of aeration induced turbulence on colonial morphology and microcystin release of the bloom-forming cyanoabcterium Microcystis - Qiang He; Zhiming Liu; Ming Li (Journal of Oceanology and Limnology, 2024)

Effects of aeration induced turbulence on colonial morphology and microcystin release of the bloom-forming cyanoabcterium Microcystis - Qiang He; Zhiming Liu; Ming Li (Journal of Oceanology and Limnology, 2024)

Single-atom oxide-decorated AuNPs for universal enhancement in SERS detection of pesticide residues - Qi Zhang; Binbin Chen; Qingbian Ma; Zunlong Fang; Shu Li; Xiaoyu He; Yufeng Wang; Xiaohua Qi; Qian Chen; Ting Cai; Lin Zhang; Mingqiang Zou; et al. (Analytica Chimica Acta, 2024)

Overlooked Vital Role of Persistent Algae‐Bacteria Interaction in Ocean Recalcitrant Carbon Sequestration and Its Response to Ocean Warming - Hanshuang Zhao; Zenghu Zhang; Shailesh Nair; Hongmei Li; Chen He; Quan Shi; Qiang Zheng; Ruanhong Cai; Genming Luo; Shucheng Xie; Nianzhi Jiao; Yongyu Zhang (Global Change Biology, 2024)
Long‐term carbon sequestration by the ocean's recalcitrant dissolved organic carbon (RDOC) pool regulates global climate. Algae and bacteria interactively underpin RDOC formation. However, on the long‐term scales, the influence of their persistent interactions close to in situ state on ocean RDOC dynamics and accumulation remains unclear, limiting our understanding of the oceanic RDOC pool formation and future trends under global change. We show that a Synechococcus ‐bacteria interaction model system viable over 720 days gradually accumulated high DOC concentrations up to 84 mg L −1 . Concurrently, the DOC inertness increased with the RDOC ratio reaching > 50%. The identified Synechococcus ‐bacteria‐driven RDOC molecules shared similarity with over half of those from pelagic ocean DOC. Importantly, we provide direct genetic and metabolite evidence that alongside the continuous transformation of algal carbon by bacteria to generate RDOC, Synechococcus itself also directly synthesized and released RDOC molecules, representing a neglected RDOC source with ~0.2–1 Gt y −1 in the ocean. However, we found that although ocean warming (+4°C) can promote algal and bacterial growth and DOC release, it destabilizes and reduces RDOC reservoirs, jeopardizing the ocean's carbon sequestration capacity. This study unveils the previously underestimated yet significant role of algae and long‐term algae‐bacteria interactions in ocean carbon sequestration and its vulnerability to ocean warming.

Predicting rice productivity for ground data-sparse regions: A transferable framework and its application to North Korea - Yu Shi; Linchao Li; Bingyan Wu; Yajie Zhang; Bin Wang; Wenhao Niu; Liang He; Ning Jin; Shufen Pan; Hanqin Tian; Qiang Yu (Science of The Total Environment, 2024)

Contrasting diversity patterns and drivers of aquatic macroinvertebrates in floodplain and non-floodplain wetlands - Qiang Guan; Fengzhi He; Zhengfei Li; Yongjiu Cai; Yujuan Kang; Zhongsheng Zhang; Haitao Wu (Science of The Total Environment, 2024)

Numerical modelling of the spatial distribution of wave overtopping water behind dikes under regular wave action using OpenFOAM - Haitao Zhao; Junwei Ye; Shudi Dong; Yadong Hou; He Xu; Weifang Gu; Qiang Li; Xizeng Zhao (Ocean Engineering, 2024)

Predominant performance of a nitrogen-doped carbon confined NiCo alloy catalyst fabricated by a natural resource encapsulation strategy for tandem catalytic nitroarenes with alcohols - Weizuo Li; Qiang Li; Zhenhao Xiao; Shu Shang; Dafang He; Xin Wang; Haiqun Chen (Fuel, 2024)

The metabolic regulation mechanism of gallic acid on biogenic amines and nitrosamines in reduced-nitrite Chinese fermented sausages: A perspective of metabolomics and metagenomics - Qin Zhou; Li Jiang; Jinpeng Zhu; Yunhao Lu; Qiang He (Food Chemistry, 2024)

Study on synergistic effect of carrier combined with micro-aeration on anaerobic digestion of food waste - Keke Ding; Baocun Wu; Yi Wang; Linji Xu; Miao Liu; Jinjing Xiang; Yongdong Chen; Li Gu; Jinze Li; Lin Li; Qiang He; Shaowu Liu (Chemical Engineering Journal, 2024)

Anchored Ru nanoclusters strategy enhances hydrogen spillover effect for high-efficiency hydrogen storage - Xiao-Qi Zhang; Yi-Qiang Qi; He Liu; Jun-Yu Wang; Li-Ying Xie; Jun-Lian Shi; Feng Wang; Yue-Liang Liu; Zong-Xian Wang; Ai-Jun Guo (Chemical Engineering Journal, 2024)

Graphene/MXene/Cellulose cellulosic paper-based flexible bifunctional sensors utilizing molecular bridge strategy with tunable piezoresistive effect for Temperature-Pressure sensing - Tianxu Zhang; Yunong Zhao; Qiang Long; Xiaowen Zhu; Langyu He; Zhuoyang Li; Xingyu Qian; Xin He; Jiahao Li; Cancan Lv; Yuxing Zha; Yiting Chen; et al. (Chemical Engineering Journal, 2024)

Oxygen-rich 3D hierarchical porous MXene prepared by Zn powder reduction for flexible supercapacitors - Peilong Ji; Li Liu; Qiang Liu; Bingke Li; Shanhao He; Keliang Wu; Xuejun Dong; Zhiyong Liu; Yanlong Tai (Chemical Engineering Journal, 2024)

Sodium disilicate pretreatment enhancing methane production from anaerobic digestion of waste activated sludge - Yu Zhang; Shushan Hu; Jinze Li; Miao Liu; Linji Xu; Lin Li; Qiang He; Li Gu (Chemical Engineering Journal, 2024)

Identification and characterization of QSFS.sau-MC-5A for sterile florets genetically independent of fertile ones per spike in wheat - Jieguang Zhou; Yuanjiang He; Wei Li; Bin Chen; Longxing Su; Yuxin Lan; Lei Yan; Ying Wang; Md Nahibuzzaman Lohani; Yanlin Liu; Huaping Tang; Qiang Xu; et al. (Theoretical and Applied Genetics, 2024)

Calcium regulates the interactions between dissolved organic matter and planktonic bacteria in Erhai Lake, Yunnan Province, China - Fan Xia; Zaihua Liu; Yunling Zhang; Qiang Li; Min Zhao; Haibo He; Qian Bao; Bo Chen; Qiufang He; Chaowei Lai; Xuejun He; Zhen Ma; et al. (Water Research, 2024)

A novel OsGST gene encoding 9glutathione reductase negatively regulates cadmium accumulation in rice - Rui Guo; Su Li; Yong Qiang Gao; Jia Tong He; Hao Yu Wang; Jin Chen; Jiu Huang; Ren Fang Shen; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Endoplasmic reticulum stress response modulator OsbZIP39 regulates cadmium accumulation via activating the expression of defensin-like gene OsCAL2 in rice - Jian Li; Ling-Yan Wang; Huan-Chao Huang; Wu Yang; Guang-Yi Dai; Zhi-Qiang Fang; Jun-Liang Zhao; Kuai-Fei Xia; Xuan Zeng; Meng-Ling He; Nan Yao; Ming-Yong Zhang (Journal of Hazardous Materials, 2024)

In situ desulfurization mechanism of molten salt thermal treatment for waste tires - Qiang Gao; Hongyun Hu; Chan Zou; Yan Ding; Chao He; Xian Li; Hong Yao (Fuel, 2024)

Insights into the impact of metals in waste activated sludge on its anaerobic digestion: From perspectives of physical structure and organic matter composition - Yu Zhang; Shushan Hu; Jinze Li; Yifei Wang; Miao Liu; Haoyang Li; Lin Li; Li Gu; Weiliang Pan; Qiang He (Fuel, 2024)

Improving crop productivity by optimizing straw returning patterns to delay senescence of wheat leaves - Pan Li; Wen Yin; Zhilong Fan; Falong Hu; Lianhao Zhao; Hong Fan; Wei He; Qiang Chai (European Journal of Agronomy, 2024)

Pre-deposited biochar enhanced flux stabilization and pollutant removal in gravity-driven membrane system - Caihong Liu; Qingyang Zuo; Jingjun Bo; Haiqing Chang; Lin Li; Qiang He; Dan Song; Jun Ma (Chemical Engineering Journal, 2024)

Magnesium isotope fractionation during magmatic differentiation in the lower continental crust - Ying Wei; Xiao-Long Huang; Qiang Ma; Fan Yang; Peng-Li He (Chemical Geology, 2024)

Autophagy in Multiple Sclerosis: Phagocytosis and Autophagy of Oligodendrocyte Precursor Cells - Jia-Qi Wang; Qiang Li; Jia-Yi He; Fang Zhou; Zi-Hao Huang; Li-Bin Wang; Yuan Zhang; Xing Li (Molecular Neurobiology, 2024)

Dissolved Organic Matters, an Intermediary of the Microbial Community and Potassium Fertilizers in A. carmichaeli rhizosphere Soil - Fei Xia; Meng Fu; Chen Liu; Yulong Li; Yi Qiang; Ding He; Guoyan Zhang; Langjun Cui (Journal of Soil Science and Plant Nutrition, 2024)

Targeting the Ferroptosis and Endoplasmic Reticulum Stress Signaling Pathways by CBX7 in Myocardial Ischemia/reperfusion Injury - Weipeng Jiang; Zeyu Yan; Xueou Zheng; Shiyi Huang; Yue Hu; Fengjuan Xiong; Bufan He; Yingzhi Wu; Qiang Fu; Zhiliang Li; Baihua Zhou (Cell Biochemistry and Biophysics, 2024)

Inconsistent elevational patterns of soil microbial biomass, diversity, and community structure on four elevational transects from subtropical forests - Ruiqi Wang; Xianjin He; Qiang Zhang; Buhang Li; Zufei Shu; Chengjin Chu (Applied Soil Ecology, 2024)

Overcoming mechanistic limitations of process-based phenological models: A data clustering method for large-scale applications - Jiaojiao Tan; Gang Zhao; Qi Tian; Lei Zheng; Xiaofeng Kang; Qinsi He; Yu Shi; Bin Chen; Dingrong Wu; Ning Yao; Liang He; Amit Kumar Srivastava; et al. (Agricultural and Forest Meteorology, 2024)

The production of bronze weapons in the Chu state: a case study of bronze arrowheads excavated from the Yuwan cemetery in Hubei, China - Ke Zhang; Qiang Li; Bin Bai; Jian He; Haichao Li (Archaeological and Anthropological Sciences, 2024)

Modeling soil water and salt dynamics in cotton-sugarbeet intercropping and their monocultures with biochar application - Xiaofang Wang; Yi Li; Asim Biswas; Honghui Sang; Jianqiang He; De Li Liu; Qiang Yu; Hao Feng; Kadambot H.M. Siddique (Soil and Tillage Research, 2024)

Association between residential greenness and incident delirium: A prospective cohort study in the UK Biobank - Qida He; Mengtong Sun; Yu Wang; Guoxian Li; Hanqing Zhao; Ze Ma; Zhaolong Feng; Tongxing Li; Qiang Han; Na Sun; Linyan Li; Yueping Shen (Science of The Total Environment, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Three new chemical constituents of Senecio raphanifolius - Shu-Wen Huang; Huan He; Zhi-Qiang Li; Yu-Wei Wang; Yuan-Ying Fang; Yu-Lin Feng; Zhi-Feng Li; Qi Wang (Phytochemistry Letters, 2024)

TA and CTAB treatment synergistically enhance activated sludge dewatering by lowering proteins and boosting Zeta potential - Weiliang Pan; Xun Zhang; Rui Deng; Li Gu; Xiuqing Tan; Shanji Yan; Ruihao Zhang; Qiang He (Journal of Environmental Chemical Engineering, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Self-cleaning and multi-active sites amphoteric composite sponges: Efficient removal, selective adsorption and photocatalyst substrates of dyes - Qiang Yang; Jing Guo; Qiang Yao; Sen Zhang; Shi Feng; Fucheng Guan; Zheng Li; Xin Zhang; Yi Xu; Jiahao He (Chemical Engineering Journal, 2024)

A blue light 3D printable hydrogel with water absorption, antibacterial, and hemostatic properties for skin wound healing - Xiu-Chong He; Xiu-Ning Chen; Yi-Hao Liu; Xinyu Zhong; Lei Qiang; Hong-Qin Wang; Fang-Zhou Wang; Jun-Song Wang; Cheng-Hui Li; Peng-Fei Zheng (Chemical Engineering Journal, 2024)

Different regulation strategies of anaerobic digestion by AC/CaO2 and Fe3O4/CaO2: Reactive oxygen species induction, methanogenic performance, and microbial response - Yongli Liu; Linyan He; Miao Liu; Yi Wang; Lin Li; Li Gu; Jinze Li; Shaowu Liu; Qiang He (Bioresource Technology, 2024)

Integrated decision support framework for construction land reduction projects prioritization in China: a multi-criteria decision analysis approach - Lei He; Yuming Zhu; Jiahe Zhou; Xin Zheng; Bingxu Mu; Qiang Li (Environment, Development and Sustainability, 2024)

Effects of uranium mining on the rhizospheric bacterial communities of three local plants on the Qinghai-Tibet Plateau - Yuanmou Tang; Xiaodie Chen; Liming Hou; Jing He; Ajia Sha; Liang Zou; Lianxin Peng; Qiang Li (Environmental Science and Pollution Research, 2024)

Two new alkaloids from the endophytic fungus Schizophyllum sp. HM230 isolated from Vincetoxicum mongolicum Maxim - Zhuang Li; Bing-Wen Zhang; Li Jiang; He Wang; Qing-Yun Ma; Hong-Fei Wang; Jun Zhang; Feng-Li Chen; You-Xing Zhao; Du-Qiang Luo (Natural Product Research, 2024)

Preparation of catalyst for CO2 hydrogenation reaction based on the idea of element sharing and preliminary exploration of catalytic mechanism - He Jia; Tao Du; Yingnan Li; Heming Wang; Qiang Yue; Lifeng Zhou; Yisong Wang (Environmental Science and Pollution Research, 2024)

Development of an effective QSAR-based hazard threshold prediction model for the ecological risk assessment of aromatic hydrocarbon compounds - Xiudi Lv; Mei He; Jiajia Wei; Qiang Li; Fan Nie; Zhiguo Shao; Zhansheng Wang; Lei Tian (Environmental Science and Pollution Research, 2024)

Potential of metallurgical iron-containing solid waste-based catalysts as activator of persulfate for organic pollutants degradation - Yang Wang; Xin Hu; Xingyue Chen; Zhifeng Ren; Yihong Li; Jing Miao; Yibo He; Peng Zhang; Chen Li; Qiang Zhu (Chemosphere, 2024)

A 76-m per pixel global color image dataset and map of Mars by Tianwen-1 - Jianjun Liu; Xin Ren; Wei Yan; Wangli Chen; Xingguo Zeng; Xiaoxia Zhang; Xu Tan; Xingye Gao; Qiang Fu; Dingxin Liu; Lin Guo; Qing Zhang; et al. (Science Bulletin, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Unveiling the aromatic differences of low-salt Chinese horse bean-chili-paste using metabolomics and sensomics approaches - Li jiang; Siwei Shen; Aoteng Zuo; Yuanlong Chi; Yunhao Lu; Qiang He (Food Chemistry, 2024)

High energy-dissipation PDMS polymer-fluid-gels over an ultra-wide temperature range - Qiang Feng; Lu He; Lanlan Wu; Jiang Li; Jie Zhang; Shaoyun Guo (Chemical Engineering Journal, 2024)

Non-targeted facilitation of primary sludge anaerobic fermentation by micro-aeration and the simultaneous nutrients transformations - Caihong Liu; Tanglong Zhang; Lin Li; Shaowu Liu; Jingjun Bo; Mohammed Mouhib; Qiang He (Chemical Engineering Journal, 2024)

Application of 210Pbex dating to establishing chronologies of modern terrestrial sedimentary deposits in estuarine deltas - Jinlin Li; Xinbao Zhang; Xiubin He; Jie Wei; Yong Yuan; Runchuan Zhang; Shengjun Wu; Yuhai Bao; Qiang Tang; Ping Huang (CATENA, 2024)

Carbon-Sulfur isotope and major and trace element variations across the Permian–Triassic boundary on a shallow platform setting (Xiejiacao, South China) - Zijie Zheng; Zhong-Qiang Chen; Stephen E. Grasby; Xue Wang; Dominic Papineau; Ziheng Li; Xiangdong Wang; Lei Zhang; He Zhao; Yuangeng Huang; Xueqian Feng; Lewei Su; et al. (Chemical Geology, 2024)

Overcoming genotypic dependency and bypassing immature embryos in wheat transformation by using morphogenic regulators - Ziru Zhou; Yawen Yang; Guo Ai; Miaomiao Zhao; Baozhu Han; Chunjie Zhao; Yiqian Chen; Yuwei Zhang; Hong Pan; Caixia Lan; Chao He; Qiang Li; et al. (Science China Life Sciences, 2024)

Targeted Therapy of Spinal Cord Injury: Inhibition of Apoptosis Is a Promising Therapeutic Strategy - Wei He; Zhi-qiang Li; Hou-yun Gu; Qi-lin Pan; Fei-xiang Lin (Molecular Neurobiology, 2024)

Recovery of nutrients from fish sludge to enhance the growth of microalga Chlorella sorokiniana CMBB276 - Jie Lian; Yuqing He; Lan Wang; Yang Liu; Kui Wang; Jan Sunde; Céline Rebours; Haokun Liu; Xiaoming Zhu; Danxiang Han; Qiang Hu; Meng Li (Marine Pollution Bulletin, 2024)

Carbon nanotube incorporated quaternized lignin-based loose nanofiltration membrane toward dye/salt separation - Zhenyu He; Na Zhang; Li Zhao; Zhenghua Li; Wanling Cui; Yuangang Zhu; Yi Wang; Huining Deng; Chengrun Si; Wen Bo; Jie Zhou; Shicai Xu; et al. (Journal of Environmental Chemical Engineering, 2024)

Microbial community variation and flavor metabolism in low-salt Chinese horse bean-chili-paste: Insights from bioturbation fermentation - Li jiang; Siwei Shen; Aoteng Zuo; Yuanlong Chi; Yunhao Lu; Qiang He (Food Bioscience, 2024)

Developing Benzodithiophene-Free donor polymer for 19.36% efficiency Green-Solvent-Processable organic solar cells - Ying He; Wenwen Jing; Chentong Liao; Xiaopeng Xu; Yuwei Duan; Ruipeng Li; Liyang Yu; Qiang Peng (Chemical Engineering Journal, 2024)

Nanodosimetric quantity-weighted dose optimization for carbon-ion treatment planning - Jingfen Yang; Xinguo Liu; Hui Zhang; Zhongying Dai; Pengbo He; Yuanyuan Ma; Guosheng Shen; Weiqiang Chen; Qiang Li (Physical and Engineering Sciences in Medicine, 2024)

Calculation and Application of Apparent Resistivity in the Frequency Domain by TFEM - Zhu-Qiang Li; Guo-Qiang Fu; Shao-Quan Tan; Xue-Guo Chen; Tao Guo; Peng Xiang; Yong-Hong Yang; Zhan-Xiang He (Applied Geophysics, 2024)

Influences of removable gas injection methods on the temperature field and gas composition of the underground coal gasification process - Fa-qiang Su; Jun-nan Yang; Xiao-long He; Meng-jia Dai; Akihiro Hamanaka; Yi- he Yu; Wen Li; Jiao-yuan Li (Fuel, 2024)

Long-term dietary exposure to 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47) reduced feeding in common carp (Cyprinus carpio): Via the JAK-STAT signaling pathway - Xin Zhang; Youlian Liu; Huimin Sun; Shuhuang Chen; Peng Tang; Qiang Hu; Mengxuan He; Ni Tang; Zhiqiong Li; Defang Chen (Environmental Pollution, 2024)

A bipolar SMPS network for measuring atmospheric aerosols using natural air ions - Yiran Li; Jin Wu; Hao Wu; Xiaomeng Liu; Qi Zhou; Yiqun Lu; Yuhang Wu; Mengyu Liu; Hengjia Ou; Shixin Mai; Xuehui He; Huaying Song; et al. (Atmospheric Environment, 2024)

Integrated microbiome and metabolome analyses reveal the effects of low pH on intestinal health and homeostasis of crayfish (Procambarus clarkii) - Zhanqi Wang; Jiapeng Li; Pengfei Zhao; Zaihang Yu; Lianlian Yang; Xueyan Ding; He Lv; ShaoKui Yi; Qiang Sheng; Liqin Zhang; Fan Zhou; Hua Wang (Aquatic Toxicology, 2024)

Mechanical Responses of a Porous Red Sandstone to Quasi-Static Cyclic Loads Under Uniaxial Compression - Zhao-Qiang Zheng; Huai-Zhong Liu; Hong-Qiang Xie; Jiang-Da He; Ming-Li Xiao; Li Zhuo (Rock Mechanics and Rock Engineering, 2024)

A phenomenological model of pulsatile blood pressure-affected degradation of polylactic acid (PLA) vascular stent - Shicheng He; Wanling Liu; Lingling Wei; Qiang Chen; Zhiyong Li (Medical & Biological Engineering & Computing, 2024)

Unveiling the landscape predictors of resilient vegetation in coastal wetlands to inform conservation in the face of climate extremes - Fangyan Cheng; Jialin Liu; Junlin Ren; Shuai Ma; Weiwen Ji; Bo Li; Qiang He (Global Change Biology, 2024)
Unveiling spatial variation in vegetation resilience to climate extremes can inform effective conservation planning under climate change. Although many conservation efforts are implemented on landscape scales, they often remain blind to landscape variation in vegetation resilience. We explored the distribution of drought‐resilient vegetation (i.e., vegetation that could withstand and quickly recover from drought) and its predictors across a heterogeneous coastal landscape under long‐term wetland conversion, through a series of high‐resolution satellite image interpretations, spatial analyses, and nonlinear modelling. We found that vegetation varied greatly in drought resilience across the coastal wetland landscape and that drought‐resilient vegetation could be predicted with distances to coastline and tidal channel. Specifically, drought‐resilient vegetation exhibited a nearly bimodal distribution and had a seaward optimum at ~2 km from coastline (corresponding to an inundation frequency of ~30%), a pattern particularly pronounced in areas further away from tidal channels. Furthermore, we found that areas with drought‐resilient vegetation were more likely to be eliminated by wetland conversion. Even in protected areas where wetland conversion was slowed, drought‐resilient vegetation was increasingly lost to wetland conversion at its landward optimum in combination with rapid plant invasions at its seaward optimum. Our study highlights that the distribution of drought‐resilient vegetation can be predicted using landscape features but without incorporating this predictive understanding, conservation efforts may risk failing in the face of climate extremes.

Quenching residual H2O2 from UV/H2O2 with granular activated carbon: A significant impact of bicarbonate - Jinfeng Zeng; Miao Zhang; Xinxin Qin; Yi He; Xinyue Liu; Yichun Zhu; Zuwen Liu; Wentao Li; Huiyu Dong; Zhimin Qiang; Junfeng Lian (Chemosphere, 2024)

Analysis of factors influencing the energy efficiency in Chinese wastewater treatment plants through machine learning and SHapley Additive exPlanations - Jinze Li; Zexuan Du; Junyan Liu; Linji Xu; Li-ping He; Li Gu; Hong Cheng; Qiang He (Science of The Total Environment, 2024)

A food-energy-water-carbon nexus framework informs region-specific optimal strategies for agricultural sustainability - Qinsi He; De Li Liu; Bin Wang; Zikui Wang; Annette Cowie; Aaron Simmons; Zhenci Xu; Linchao Li; Yu Shi; Ke Liu; Matthew Tom Harrison; Cathy Waters; et al. (Resources, Conservation and Recycling, 2024)

Developing a land development compensation model for returned land in tract expropriation: Towards a unified urban-rural land market in China - Jingpeng Guo; Yinghui Zhao; Frank Yonghong Li; Kebiao Mao; Jinfeng He; Qiang He (Land Use Policy, 2024)

Biological effects of perfluoroalkyl substances on running water ecosystems: A case study in Beiluo River, China - Xi Li; Qiang Wang; Qi Li; Yawei Wang; Yulu Tian; Anen He; Yan Chen; Shaocheng Si (Journal of Hazardous Materials, 2024)

Co-foliar application of zinc and nano-silicon to rice helps in reducing cadmium exposure risk: Investigations through in-vitro digestion with human cell line bioavailability assay - Qiang Lin; Yasir Hamid; Honhang Wang; Min Lu; Xuerui Cao; Tong Zou; Zhiqin Chen; Bilal Hussain; Ying Feng; Tingqiang Li; Zhenli He; Xiaoe Yang (Journal of Hazardous Materials, 2024)

Crystal mush rejuvenation in the formation of Triassic dacites in Mengku, SE Tibetan Plateau - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; Zai-Bo Sun; Xiao-Chi Liu; De-Feng He; Wei-Qiang Ji; Fang-Yang Hu; Shao-Hua Zhang; Xiao-Ming Huang (Journal of Asian Earth Sciences, 2024)

Photosynthetic live microorganism-incorporated hydrogels promote diabetic wound healing via self-powering and oxygen production - Yan Wu; Meiyun Li; Ruiying He; Lan Xiao; Sen Liu; Kaiyuan Chen; Huifen Qiang; Keqin Ji; Luxin Li; Yongkui Yin; Xiaohuan Yuan; Meng Li; et al. (Chemical Engineering Journal, 2024)

Genomic data and ecological niche modeling reveal an unusually slow rate of molecular evolution in the Cretaceous Eupteleaceae - Kun-Li Xiang; Sheng-Dan Wu; Lian Lian; Wen-Chuang He; Dan Peng; Huan-Wen Peng; Xiao-Ni Zhang; Hong-Lei Li; Jia-Yu Xue; Hong-Yan Shan; Gui-Xia Xu; Yang Liu; et al. (Science China Life Sciences, 2024)

The impacts of planting patterns combined with irrigation management practices on soil water content, watermelon yield and quality - Xiaolin Qiang; Zhaojun Sun; Xingqiang Li; Siqi Li; Zhao Yu; Jun He; Qian Li; Lei Han (Agroforestry Systems, 2024)

Widespread inversions shape the genetic and phenotypic diversity in rice - Wenchuang He; Huiying He; Qiaoling Yuan; Hai Zhang; Xiaoxia Li; Tianyi Wang; Yingxue Yang; Longbo Yang; Yuting Yang; Xiangpei Liu; Hua Wei; Hong Zhang; et al. (Science Bulletin, 2024)

Differential response of Hg-methylating and MeHg-demethylating microbiomes to dissolved organic matter components in eutrophic lake water - Zhengyu Wu; Zhike Li; Bo Shao; Ji Chen; Xiaomei Cui; Xiaoyu Cui; Xianhua Liu; Ying Xin Zhao; Qiang Pu; Jiang Liu; Wei He; Yiwen Liu; et al. (Journal of Hazardous Materials, 2024)

Iron–doped bismuth oxybromides as visible−light−responsive Fenton catalysts for the degradation of atrazine in aqueous phases - Yong-Li Cai; Yu-Hang Xu; Ji-Zun Xiang; Zhi-Qiang Zhang; Qiu-Xiang He; Ya-Feng Li; Jian Lü (Journal of Environmental Sciences, 2024)

The anisotropy of MODIS LST in urban areas: A perspective from different time scales using model simulations - Xiaoyu He; Dandan Wang; Si Gao; Xue Li; Gaijing Chang; Xiaodong Jia; Qiang Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Molecular insight into the vertical migration and degradation of dissolved organic matter in riparian soil profiles - Chang Liu; Lin Li; Yue Zhi; Junyu Chen; Qingyang Zuo; Qiang He (Environmental Research, 2024)

Revealing the environmental hazard posed by biodegradable microplastics in aquatic ecosystems: An investigation of polylactic acid's effects on Microcystis aeruginosa - Bingran Tang; Lixue Zhang; Muhammad Salam; Bing Yang; Qiang He; Yongchuan Yang; Hong Li (Environmental Pollution, 2024)

Confined MOF pyrolysis within mesoporous SiO2 core–shell nanoreactors for superior activity and stability of electro-Fenton catalysts - Jingwen Wang; Hao Li; Pan Xia; Huanbin Liu; Xi Chen; Zhihong Ye; Qiang He; Ignasi Sirés (Chemical Engineering Journal, 2024)

Constraints of palaeoenvironment on organic matter of Benxi Formation shale and discussion on enrichment mechanism under different facies - Qianyang He; Delu Li; Qiang Sun; Jianwen Gao; Haibin Li; Xinhu Li; Xiaochen Zhao; Shaofei Wang; Gaozhe Ji (Frontiers of Earth Science, 2024)

Combined toxicity of biochar with nanoplastics or silver nanoparticles toward Chlorella vulgaris - Hongye Li; Xiaojun Zhou; Ruixing Huang; Qiang He; Zhengsong Wu; Yuheng Huang; Zhiheng Li; Yu Liu; Xiaoliu Huangfu (Algal Research, 2024)

Source identification of sedimentary organic carbon in coastal wetlands of the western Bohai Sea - Juqin Zhang; Qian Hao; Qiang Li; Xiangwei Zhao; Xiaoli Fu; Weiqi Wang; Ding He; Yuan Li; Zhenqing Zhang; Xiaodong Zhang; Zhaoliang Song (Science of The Total Environment, 2024)

Diversity and composition of microbial communities in Jinsha earthen site under different degree of deterioration - Jing Li; Yanqiu He; Changjie He; Lin Xiao; Ning Wang; Luman Jiang; Juncheng Chen; Ke Liu; Qiang Chen; Yunfu Gu; Menggen Ma; Xiumei Yu; et al. (Environmental Research, 2024)

Elimination method of sliding blockage effect in discrete element simulation of rolling stone based on discrete fracture network and damping joint model - You Zhou; Huai-Zhong Liu; Hong-Qiang Xie; Li Zhuo; Ming-Li Xiao; Jiang-Da He; Jian-Liang Pei; Guo-Wen Xu (Computers and Geotechnics, 2024)

High fat diet-induced downregulation of TRPV2 mediates hepatic steatosis via p21 signalling - Pengfei Wei; Lixuan Li; Chenqiu Ran; Mingyue Jin; Huijuan Zhao; Kelaier Yang; Yu Wang; Huaqiu He; Mengyang Jia; Hongyan Pan; Qiang Li; Jing Guo (Journal of Physiology and Biochemistry, 2024)

Unraveling the factors influencing CO2 emissions from hydroelectric reservoirs in karst and non-karst regions: A comparative analysis - Wanfa Wang; Si-Liang Li; Jun Zhong; Yuanbi Yi; Fujun Yue; Zenglei Han; Qixin Wu; Ding He; Cong-Qiang Liu (Water Research, 2024)

Spatial-temporal variation of soil organic matter decomposition potential in China - Qi Chen; Zeyan Zhou; Sulin Cai; Meiqi Lv; Yinghui Yang; Yunchao Luo; Han Jiang; Run Liu; Tingting Cao; Bei Yao; Yunru Chen; Qiang Li; et al. (Soil and Tillage Research, 2024)

Aerobic methane production by phytoplankton as an important methane source of aquatic ecosystems: Reconsidering the global methane budget - Yufeng Mao; Tong Lin; Hong Li; Ruixu He; Kailai Ye; Weiwei Yu; Qiang He (Science of The Total Environment, 2024)

Controlling mechanism of shale palaeoenvironment on its tensile strength: A case study of Banjiuguan Formation in Micangshan Mountain - Haibin Li; Delu Li; Qianyang He; Qiang Sun; Xiaochen Zhao (Fuel, 2024)

Insights into the mechanism of extracellular proteases from Penicillium on myofibrillar protein hydrolysis and volatile compound evolutions - Zimu Li; Danni Li; Daodong Pan; Qiang Xia; Yangying Sun; Lihui Du; Jun He; Changyu Zhou; Fang Geng; Jinxuan Cao (Food Research International, 2024)

Epoxy resin for solidification/stabilization of soil contaminated with copper (II): Leaching, mechanical, and microstructural characterization - Qiang Ma; Jingjie Lei; Jun He; Zhi Chen; Wentao Li (Environmental Research, 2024)

Indigenous mixotrophic aerobic denitrifiers stimulated by oxygen micro/nanobubble-loaded microporous biochar - Xiaojun Miao; Jiani Xu; Bing Yang; Junxiao Luo; Yue Zhi; Wei Li; Qiang He; Hong Li (Bioresource Technology, 2024)

MiRNA320a Inhibitor-Loaded PLGA-PLL-PEG Nanoparticles Contribute to Bone Regeneration in Trauma-Induced Osteonecrosis Model of the Femoral Head - Ying Zhang; Chuan Li; Qiushi Wei; Qiang Yuan; Wei He; Ning Zhang; Yiping Dong; Zhenhao Jing; Leilei Zhang; Haibin Wang; Xiangyang Cao (Tissue Engineering and Regenerative Medicine, 2024)

Identification and fine-mapping of QYrAS286-2BL conferring adult-plant resistance to stripe rust in cultivated emmer wheat - Yuqin Li; Yanling Hu; Yun Jiang; Qiang Zhou; Yu He; Jingshu He; Xuejiao Chen; Xue Chen; Bo Jiang; Ming Hao; Shunzong Ning; Zhongwei Yuan; et al. (Theoretical and Applied Genetics, 2024)

Plasma membrane-localized hexose transporter OsSWEET1b, affects sugar metabolism and leaf senescence - Qiang Zhang; Changzhao Chen; Rui Guo; Xiaofang Zhu; Xinyu Tao; Mengxing He; Zhiwen Li; Lan Shen; Qing Li; Deyong Ren; Jiang Hu; Li Zhu; et al. (Plant Cell Reports, 2024)

GRACE-based dynamic assessment of hydrological drought trigger thresholds induced by meteorological drought and possible driving mechanisms - Zhiming Han; Shengzhi Huang; Jian Peng; Jianfeng Li; Guoyong Leng; Qiang Huang; Jing Zhao; Fang Yang; Panxing He; Xiaoyu Meng; Zhi Li (Remote Sensing of Environment, 2023)

Advanced treatment and Resource recovery of brewery wastewater by Co-cultivation of filamentous microalga Tribonema aequale and autochthonous Bacteria - Hang Su; Kui Wang; Jie Lian; Lan Wang; Yuqing He; Meng Li; Danxiang Han; Qiang Hu (Journal of Environmental Management, 2023)

Redox mediators stimulated chain elongation process in fluidized cathode electro-fermentation systems for caproate production - Jingwei Ma; Yingxin Feng; Lu Li; Liang Zhu; Qiulai He; Zhou Shi; Shuizhou Ke; Qiang Ke; Quanbao Zhao (Journal of Environmental Management, 2023)

Enhanced biological wastewater treatment supplemented with anaerobic fermentation liquid of primary sludge - Lin Li; Qiqi Liao; Caihong Liu; Tanglong Zhang; Chang Liu; Ziwei Chen; Rui Gao; Qiang He (Journal of Environmental Management, 2023)

Yuexiconcha nov. gen. – A resilifer-bearing palaeotaxodont (Bivalvia, Protobranchia) from the Ordovician of Guangdong, South China - Zhi-jun Niu; Ren-jie Zhang; Paul A. Johnston; Chu-an Li; Zhi-hong Wang; Kun Hu; Fang Song; Yao-yan He; Jin-lan He; Xiao-ming Lin; Wen-qiang Yang (Geobios, 2023)

Thiol-modified hyaluronic acid improves the physical stability of curcumin-zein nanoparticles by forming disulfide bonds with zein - Guangshuai Zhang; Mengdi Qin; Mengran Guo; Mo Li; Di Zhang; Yichi Sun; Bingyang Liu; Zhonggui He; Qiang Fu (Food Chemistry, 2023)

Building information modelling-enabled multi-objective optimization for energy consumption parametric analysis in green buildings design using hybrid machine learning algorithms - Yang Liu; Tiejun Li; Wensheng Xu; Qiang Wang; Hao Huang; Bao-Jie He (Energy and Buildings, 2023)

Gas barrier coating based on cellulose nanocrystals and its preservation effects on mango - Mingxia Li; Zhenxu Shi; Shulin He; Qiang Hu; Ping Cai; Lin Gan; Jin Huang; Yongqiang Zhang (Carbohydrate Polymers, 2023)

Prioritizing agronomic practices and uncertainty assessment under climate change for winter wheat in the loess plateau, China - Tengcong Jiang; Bin Wang; Xiaoning Duan; De Li Liu; Jianqiang He; Liang He; Ning Jin; Hao Feng; Qiang Yu (Agricultural Systems, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Evidence of vertical transmission of fowl adenovirus 8b in ducks - Bingrong Wu; Qimin Xu; Zhenchuan Li; Qianqian Wang; Dalin He; Xiaoning Jiang; Yitong Cui; Qiang Feng; Yi Tang; Youxiang Diao (Veterinary Microbiology, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

Dietary oregano essential oil supplementation alters meat quality, oxidative stability, and fatty acid profiles of beef cattle - Pengjia He; Yu Lei; Ke Zhang; Rui Zhang; Yunpeng Bai; Zeming Li; Li Jia; Jinping Shi; Qiang Cheng; Yannan Ma; Xiaoqiang Zhang; Lishan Liu; et al. (Meat Science, 2023)

Unraveling the microbiotas and key genetic contexts identified on stone heritage using illumina and nanopore sequencing platforms - Qiang Li; Chao Wu; Jintao He; Bingjian Zhang (International Biodeterioration & Biodegradation, 2023)

Simultaneous extraction of C3H8 and C2H6 from ternary C3H8/C2H6/CH4 mixtures in an ultra-microporous metal–organic framework - Lan Lan; Nan Lu; Jia-Cheng Yin; Qiang Gao; Feifan Lang; Ying-Hui Zhang; Hong-Xiang Nie; Na Li; Xian-He Bu (Chemical Engineering Journal, 2023)

Self-assembled monolayers as hole transport layers for efficient thermally evaporated blue perovskite light-emitting diodes - Ben Chen; Runda Guo; Zhiyuan He; Chencheng Peng; Hanrui Su; Liang Sun; Xin Li; Qiang Zhang; Lei Wang (Chemical Engineering Journal, 2023)

Immune-microenvironment modulatory polyurethane-hyaluronic acid hybrid hydrogel scaffolds for diabetic wound treatment - Yuan Feng; Kecen Xiao; Jinlin Chen; Jingjing Lin; Yuanyuan He; Xueling He; Fuyi Cheng; Zhen Li; Jiehua Li; Feng Luo; Hong Tan; Qiang Fu (Carbohydrate Polymers, 2023)

Distinct and shared endothermic strategies in the heat producing tissues of tuna and other teleosts - Baosheng Wu; Xueli Gao; Mingling Hu; Jing Hu; Tianming Lan; Tingfeng Xue; Wenjie Xu; Chenglong Zhu; Yuan Yuan; Jiangmin Zheng; Tao Qin; Peidong Xin; et al. (Science China Life Sciences, 2023)

Promoting or inhibiting: the impact of China’s urban-rural digital divide on regional environmental development - Yuecen Yan; Li Cheng; Qiong Lin; Qiang He (Environmental Science and Pollution Research, 2023)

Labdane and ent-halimane diterpenoids with STAT3-inhibitory activity from Leonurus sibiricus - Chen Wang; Jiao Tian; Chaoge Liu; Yiming He; Jiahang Li; Qiang Zhang; Ting Xiao; Chunfeng Xie; Cheng Yang (Phytochemistry, 2023)

Climate warming may accelerate apple phenology but lead to divergent dynamics in late-spring frost and poor pollination risks in main apple production regions of China - Xiaoya Ru; Jie Zhou; Kaiyuan Gong; Zhihao He; Zhanwu Dai; Meirong Li; Xinxin Feng; Qiang Yu; Hao Feng; Jianqiang He (European Journal of Agronomy, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

Environmental decentralisation, environmental regulation, and agricultural carbon intensity: an empirical study based on Chinese provincial panel data - Qiang He; Xin Deng; Feng Wei; Chuan Li; Zhongcheng Yan; Yanbin Qi (Environment, Development and Sustainability, 2023)

Characterization and mapping of photovoltaic solar power plants by Landsat imagery and random forest: A case study in Gansu Province, China - Xinxin Wang; Xiangming Xiao; Xi Zhang; Hui Ye; Jinwei Dong; Qiang He; Xubang Wang; Jianquan Liu; Bo Li; Jihua Wu (Journal of Cleaner Production, 2023)

Integrating machine learning and environmental variables to constrain uncertainty in crop yield change projections under climate change - Linchao Li; Yan Zhang; Bin Wang; Puyu Feng; Qinsi He; Yu Shi; Ke Liu; Matthew Tom Harrison; De Li Liu; Ning Yao; Yi Li; Jianqiang He; et al. (European Journal of Agronomy, 2023)

NIR-II photo-amplified peroxidase-like activity using biocatalytic copper-based nanoplatform against subcutaneous methicillin-resistant Staphylococcus aureus infection - Danyan Wang; Xiaojun He; Qiang Wang; Pingping Li; Enoch Obeng; Dongyang Zheng; Jianliang Shen; Zi Jin (Chemical Engineering Journal, 2023)

Spartina alterniflora invasion differentially alters microbial residues and their contribution to soil organic C in coastal marsh and mangrove wetlands - Xueli Ding; Weiqi Wang; Jiahui Wen; Tianshu Feng; Josep Peñuelas; Jordi Sardans; Chao Liang; Evgenios Agathokleous; Chun Wang; Zhaoliang Song; Qiang Li; Timothy R. Filley; et al. (CATENA, 2023)

A promising QTL QSns.sau-MC-3D.1 likely superior to WAPO1 for the number of spikelets per spike of wheat shows no adverse effects on yield-related traits - Jieguang Zhou; Wei Li; Yaoyao Yang; Xinlin Xie; Jiajun Liu; Yanling Liu; Huaping Tang; Mei Deng; Qiang Xu; Qiantao Jiang; Guoyue Chen; Pengfei Qi; et al. (Theoretical and Applied Genetics, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Modelling interactions between cowpea cover crops and residue retention in Australian dryland cropping systems under climate change - Qinsi He; De Li Liu; Bin Wang; Annette Cowie; Aaron Simmons; Cathy Waters; Linchao Li; Puyu Feng; Yi Li; Peter de Voil; Alfredo Huete; Qiang Yu (Agriculture, Ecosystems & Environment, 2023)

Revealing cryptic diversity and population divergence in subtropical aphids through DNA barcoding - Qiang Li; Qian Liu; Yuhua Yu; Xiaolan Lin; Xueyou He; Xiaolei Huang (Zoologica Scripta, 2023)
Aphids are worldwide distributed pests, which feed on plant sap and cause serious losses to agricultural and forestry industries. Relatively few comprehensive studies have been conducted on aphid diversity in subtropics, although these regions may harbour hidden aphid diversity due to high plant diversity. In this study, we conducted DNA barcoding analysis for aphids in subtropical regions based on a comprehensive DNA barcode reference library including 5821 sequences and related ecological information (e.g. geography, host plant) of 379 morphospecies. In the reference library, 2140 sequences and related data of 151 morphospecies belonging to 77 genera and 11 subfamilies were newly produced by the current study. The average Kimura 2‐parameter distances within species, genera and subfamilies were 0.92%, 3.55% and 8.3%, respectively. The minimum interspecific distances were greater than the maximum intraspecific distances in 79.8% species, suggesting that barcode gaps existed in most aphid species. Automatic barcode gap discovery, Barcode Index Number, Bayesian Poisson tree processes and generalized mixed Yule‐coalescent revealed 419, 401, 462 and 455 single species‐representing clusters, respectively. A total of 32 morphospecies were assigned to more than one subclade respectively, suggesting geography or host plant‐mediated divergences and the existence of cryptic diversity. This study demonstrates that subtropical regions should have a higher species diversity of aphids, and cryptic species in certain morphospecies indicated in this study need to be investigated based on integrative taxonomic practices in the future. The DNA barcode reference library constructed herein provides a robust baseline data set to support future research in taxonomy, phylogenetics, ecology and evolution of aphids.

Face mask derived micro(nano)plastics and organic compounds potentially induce threat to aquatic ecosystem security revealed by toxicogenomics-based assay - Yan-Jun Liu; He-Yun Yang; Yan-Yun Hu; Zheng-Hao Li; Hao Yin; Yun-Tian He; Keng-Qiang Zhong; Li Yuan; Xing Zheng; Guo-Ping Sheng (Water Research, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

Biodegradation of p-hydroxybenzoic acid in Herbaspirillum aquaticum KLS-1 isolated from tailing soil: Characterization and molecular mechanism - Yi-Xi Li; Wei Lin; Yong-He Han; Yao-Qiang Wang; Tao Wang; Hong Zhang; Yong Zhang; Shan-Shan Wang (Journal of Hazardous Materials, 2023)

Breakup mechanism of the northern South China Sea: Evidence from the deep crustal structure across the continent-ocean transition - Qiang Wang; Minghui Zhao; Jiazheng Zhang; Haoyu Zhang; Jean-Claude Sibuet; Zizheng Li; Enyuan He; Xuelin Qiu; Wen Peng; Guizhong Chen (Gondwana Research, 2023)

Organic matter enrichment and palaeoenvironmental comparison of Alinian fine-grained sedimentary rocks in lake facies - Delu Li; Qianyang He; Haibin Li; Jianwen Gao; Xiaochen Zhao; Qiang Sun; Shaofei Wang; Tao Xue (Gas Science and Engineering, 2023)

Synthetic phylogenetically diverse communities promote denitrification and stability - Min Zhou; Xiaotong Guan; Ting Deng; Ruiwen Hu; Lu Qian; Xueqin Yang; Bo Wu; Juan Li; Qiang He; Longfei Shu; Qingyun Yan; Zhili He (Environmental Research, 2023)

The modified properties of sludge-based biochar with ferric sulfate and its effectiveness in promoting carbon release from particulate organic matter in rural household wastewater - Linji Xu; Lin Li; Wei Lu; Yilu Gu; Huichuan Zhuang; Qiang He; Lei Zhu (Environmental Research, 2023)

Interaction of metabolism-related pathway gene variants with bisphenol A exposure on serum lipid profiles - Heng He; Fuwei Zhang; Shuang Zhou; Shanshan Zhang; Lu Wang; Jiaoyuan Li; Qiang Zeng; Ying Zhu; Jianbo Tian; Jiang Chang; Liming Cheng; Qing Lu; et al. (Environmental Toxicology and Pharmacology, 2023)

Reducing agents enhanced prometon degradation by CuBi2O4/peroxymonosulfate: Development of interfacial electron transport and circulation of Cu+/Cu2+ - Yongzhen Li; Zhenbei Wang; Chen Li; Fei Qi; Pengwei Yan; Yiping Wang; Mengfei He; Zhonglin Chen; Qiang Wang; Yu Wang; Hao Zheng; Amir Ikhlaq; et al. (Chemical Engineering Journal, 2023)

Adsorption behavior of antibiotics with different structures onto vivianite in the presence of dissolved organic matter during the phosphorus recovery process - Wang-Xiao Jia; Wen-Qiang Li; Zhi-Hui Xie; Pu-Can Guo; Zhi-Long Ye; Zhao-Kun Xiong; Chuan-Shu He; Bo Lai (Chemical Engineering Journal, 2023)

Application of 210Pbex in elucidating contemporary sedimentary dynamics in the water-level fluctuation zone of the Three Gorges Reservoir, China - Jinlin Li; Yuhai Bao; Jie Wei; Xiubin He; Qiang Tang; Xinbao Zhang; Shengjun Wu; Ping Huang; Hong Li (CATENA, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Flow regulation controls sediment, carbon, and nutrient dynamics across the elevation gradient in the water level fluctuation zone of the Three Gorges Reservoir, China - Dil Khurram; Qiang Tang; Yuhai Bao; Xiubin He; Jinlin Li (Journal of Soils and Sediments, 2023)

Artificial Intelligence in Sports Medicine: Could GPT-4 Make Human Doctors Obsolete? - Kunming Cheng; Qiang Guo; Yongbin He; Yanqiu Lu; Ruijie Xie; Cheng Li; Haiyang Wu (Annals of Biomedical Engineering, 2023)

Influence of e-waste exposure on DNA damage and DNA methylation in people living near recycling sites - Na Li; Jinhan Wang; Kejun Li; Ping Yang; Yan Wang; Chang Xu; Ningning He; Kaihua Ji; Huijuan Song; Manman Zhang; Liqing Du; Qiang Liu (Environmental Science and Pollution Research, 2023)

Taxonomic and Morpho-Functional Photosynthetic Patterns of 18 Intertidal Macroalgal Species in the Guangdong–Hong Kong–Macao Greater Bay Area, China - Quan He; Linqing Liu; Yujie Qin; Qiang Lin; Guangyan Ni; Binbin Chen; Zengling Ma; Dinghui Zou; Gang Li (Journal of Marine Science and Engineering, 2023)
Macroalgae provide food for microbial, meio- and macro-faunal communities in coastal ecosystems, thus mediating nutrient dynamics and functions in these ecosystems. Because of this vital role, it is important to clarify physiological information about macroalgae as it reflects their growth potential in the field. In this study, we examined the biomass, pigment content, and photosynthetic O2 evolution rate versus irradiance curves of 18 macroalgal species from the intertidal zone of the Guangdong–Hong Kong–Macao Greater Bay Area, China, and investigated their photosynthetic patterns in relation to phyla characteristics, morphology, and growth locations. The results showed that green algae had the highest maximum photosynthetic O2 evolution rate (Pmax), light utilization efficiency (α), and dark respiration (Rd) among the three macroalgal phyla; the sheet-like macroalgal species had the highest Pmax, α, and Rd among the four morphological categories. The macroalgal species in the upper intertidal zone showed higher Pmax and α and lower saturation irradiance (EK) and compensation irradiance (EC) than those species in the lower intertidal location. The PCA results showed that the biomass of sheet-like macroalgal species was positively correlated with factor PC1 (50.34%), and that of finely branched species was negatively correlated with factor PC2 (25.17%). In addition, our results indicate that the light absorption and utilization capabilities of macroalgae could determine whether they could dominate the intertidal zone and that their photosynthetic characteristics could be used as a potential indicator of their biomass distribution in the Greater Bay Area.

Synergistic effects of pyrolysis temperature, iron ion concentration and solid/liquid ratio on the properties and Cr(VI) removal performance of magnetic carbon - Qiang Qu; Ling Qiu; Ming-Zhuo Li; Guo-Tao Sun; He-Yu Chen; Xiao-Hui Guo (Journal of Water Process Engineering, 2023)

Comprehensive investigation on volatile and non-volatile metabolites in low-salt doubanjiang with different fermentation methods - Li Jiang; Yunhao Lu; Yi Ma; Zishan Liu; Qiang He (Food Chemistry, 2023)

Multi-perspective synergistic construction of dual-functional heterostructures for high-temperature Li-S batteries - Yiding Li; Qiang Zhang; Simin Shen; Siqi Wang; Liangliang Shi; Dequan Liu; Yujun Fu; Deyan He (Chemical Engineering Journal, 2023)

The Potential of GPT-4 as an AI-Powered Virtual Assistant for Surgeons Specialized in Joint Arthroplasty - Kunming Cheng; Zhiyong Li; Cheng Li; Ruijie Xie; Qiang Guo; Yongbin He; Haiyang Wu (Annals of Biomedical Engineering, 2023)

Thresholds for triggering the propagation of meteorological drought to hydrological drought in water-limited regions of China - Qiang Liu; Yuting Yang; Liqiao Liang; He Jun; Denghua Yan; Xuan Wang; Chunhui Li; Tao Sun (Science of The Total Environment, 2023)

A Genome-Wide Association Study for Susceptibility to Axial Length in Highly Myopic Eyes - Qiang Lu; Yu Du; Ye Zhang; Yuxi Chen; Hao Li; Wenwen He; Yating Tang; Zhennan Zhao; Yinglei Zhang; Jihong Wu; Xiangjia Zhu; Yi Lu (Phenomics, 2023)

Potential Use of Artificial Intelligence in Infectious Disease: Take ChatGPT as an Example - Kunming Cheng; Zhiyong Li; Yongbin He; Qiang Guo; Yanqiu Lu; Shuqin Gu; Haiyang Wu (Annals of Biomedical Engineering, 2023)

Insights into solid phase denitrification in wastewater tertiary treatment: the role of solid carbon source in carbon biodegradation and heterotrophic denitrification - Ziwei Chen; Qingyang Zuo; Caihong Liu; Lin Li; Katherine Y. Deliz Quiñones; Qiang He (Bioresource Technology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Effect of KMnO4/pH adjustment of extracellular polymeric substances under waste activated sludge on sludge dewatering - Weiliang Pan; Jiaoni Li; Xun Zhang; Shan Liang; Yinghao Kang; Rui Deng; Li Gu; Qiang He (Environmental Science and Pollution Research, 2023)

Acclimation of anaerobic fermentation microbiome with acetate and ethanol for chain elongation and the biochemical response - Lin Li; Chang Liu; Linji Xu; Huichuan Zhuang; Junguo He; Qiang He; Jie Zhang (Chemosphere, 2023)

Cadmium mobility and health risk assessment in the soil-rice-human system using in vitro biaccessibility and in vivo bioavailability assay: Two year field experiment - Qiang Lin; Yasir Hamid; Haijun Yang; Jianfeng Jiang; Anqi Shan; Mei Wang; Bilal Hussain; Ying Feng; Tingqiang Li; Zhenli He; Xiaoe Yang (Science of The Total Environment, 2023)

Calcium isotopic geochemistry of geothermal systems in the tectonically active southeastern Tibetan Plateau - Bei-Bei Chen; Si-Liang Li; Philip A.E. Pogge von Strandmann; Jun Zhong; Ting-Ting Ma; Jian Sun; Wen-Yan He; Cong-Qiang Liu (Science of The Total Environment, 2023)

First evidence and potential sources of novel brominated flame retardants and BDE 209 in the deepest ocean - Jingqian Xie; Gaoxin Zhang; Qiang Wu; Min Luo; Duofu Chen; Yu Zhang; Lisheng He; Yingming Li; Qinghua Zhang; Tian Lin; Guibin Jiang (Journal of Hazardous Materials, 2023)

The diverging epigenomic landscapes of honeybee queens and workers revealed by multiomic sequencing - Yong Zhang; Xu Jiang He; Andrew B. Barron; Zhen Li; Meng Jie Jin; Zi Long Wang; Qiang Huang; Li Zhen Zhang; Xiao Bo Wu; Wei Yu Yan; Zhi Jiang Zeng (Insect Biochemistry and Molecular Biology, 2023)

Classification and sources of extremely severe sandstorms mixed with haze pollution in Beijing - Tianyi Liu; Fengkui Duan; Yongliang Ma; Tao Ma; Qinqin Zhang; Yunzhi Xu; Fan Li; Tao Huang; Takashi Kimoto; Qiang Zhang; Kebin He (Environmental Pollution, 2023)

Numerical analysis and design method of UHPC grouted RC column- footing socket joints - Guangda Zhang; Qiang Han; Kun Xu; Yanchen Song; Jianglong Li; Weili He (Engineering Structures, 2023)

Thermally regenerable FeS/N-doped biochar catalyzed peroxydisulfate oxidative destruction of aqueous triclosan - Kunyun Chen; Chuangfu Song; Zilin Huang; Li Rao; Xin Jin; Guangrong Liu; Feifei He; Qiang Huang (Chemical Engineering Journal, 2023)

Effects of biochar addition towards the treatment of blackwater in anaerobic dynamic membrane bioreactor (AnDMBR): Comparison among room temperature, mesophilic and thermophilic conditions - Weiliang Pan; Honglin Ouyang; Xiuqing Tan; Shanji Yan; Ruihao Zhang; Rui Deng; Li Gu; Qiang He (Bioresource Technology, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Major and stably expressed QTL for traits related to the mature wheat embryo independent of kernel size - Surong Wang; Tianyu Wang; Qijing Xuan; Xiangru Qu; Qiang Xu; Qiantao Jiang; Zhien Pu; Yang Li; Yunfeng Jiang; Guoyue Chen; Mei Deng; Yanling Liu; et al. (Theoretical and Applied Genetics, 2023)

Molecular characterization of organic matter transformation mediated by microorganisms under anoxic/hypoxic conditions - Shicong Xiao; Jiaxin Chen; Yuan Shen; Qi Chen; Yu Wang; Yunyun Li; Chen He; Ruanhong Cai; Quan Shi; Nianzhi Jiao; Qiang Zheng (Science China Earth Sciences, 2023)

Beneficial effects of red and blue light on potato leaf antioxidant capacity and tuber bulking - Wei He; Qiang Chai; Dan Zhang; Wenli Li; Cai Zhao; Wen Yin; Hong Fan; Aizhong Yu; Falong Hu; Zhilong Fan (Physiology and Molecular Biology of Plants, 2023)

Brittle failure modes of underground powerhouses: an insight based on true triaxial compression tests - Ben-Guo He; Qiang Tong; Xia-Ting Feng; Qiang Jiang; Hui Li; Yonghong Li; Zhiguo Li (Bulletin of Engineering Geology and the Environment, 2023)

Hydroquinone triggers pyroptosis and endoplasmic reticulum stress via AhR-regulated oxidative stress in human lymphocytes - Xiaohan Yang; Shuangyan Dong; Chao Li; Ming Li; Caihong Xing; Jin He; Cheng Peng; Hua Shao; Qiang Jia (Toxicology Letters, 2023)

Nitrogen−doped−CQDs/schwertmannites as visible−light−responsive Fenton catalysts for the degradation of chlortetracycline and related cytotoxicity - Yu-Hang Xu; Xiang-Ji Liu; Ji-Zun Xiang; Zhi-Qiang Zhang; Xing-Xing Qiao; Ya-Feng Li; Qiu-Xiang He; Jian Lü (Journal of Cleaner Production, 2023)

Fractal characteristics of rocks and mesoscopic fractures at different loading rates - Yanming Lai; Kang Zhao; Zhiwei He; Xiang Yu; Yajing Yan; Qiang Li; Hai Shao; Xiangwei Zhang; Yun Zhou (Geomechanics for Energy and the Environment, 2023)

Coke formation of heavy oil during thermal cracking: New insights into the effect of olefinic-bond-containing aromatics - Feng Wang; Qiang Wei; Keqi Li; Bernard Wiafe Biney; He Liu; Kun Chen; Zongxian Wang; Aijun Guo (Fuel, 2023)

Effect of granular activated carbon and chloroform on chain elongation with simple substrate ethanol and acetate - Lin Li; Linji Xu; Junguo He; Qiang He; Jie Zhang (Environmental Research, 2023)

Potential of crop straw incorporation for replacing chemical fertilizer and reducing nutrient loss in Sichuan Province, China - Ying Wang; Bang-qiang Liang; Hui Bao; Qian Chen; Ya-lei Cao; Yan-qing He; Liang-zhong Li (Environmental Pollution, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

3D-printed GA/PPy aerogel biocathode enables efficient methane production in microbial electrosynthesis - Yuting He; Jun Li; Liang Zhang; Xun Zhu; Yuan Pang; Qian Fu; Qiang Liao (Chemical Engineering Journal, 2023)

Slope gradient impacts on rill morphological characteristics: Using indoor simulation experiment on loamy clay under certain rainfall intensity - Ji-jun He; Li-ying Sun; Guang-yao Duan; Qiang-guo Cai (CATENA, 2023)

Top-down control of macrofauna: Are waterbirds passengers or drivers in wetlands? - Jianshe Chen; Chunming Li; Changlu Wu; Xuena Sun; Xuesong Feng; Jiayuan Zhao; Zhijun Ma; Jihua Wu; Mark D. Bertness; Bo Li; Qiang He (Biological Conservation, 2023)

2000 years of lake-level fluctuations and human adaptation around China's largest freshwater lake - Huanye Wang; Weiguo Liu; Qin Leng; Lin Yang; Hui Zhao; Jun Yang; Yuwei Chen; Shangbin Xiao; Yunning Cao; Jing Hu; Xiaoke Qiang; Peng Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Investigation of the reaction mechanism regarding thermal treatment of biomass using molten salts: A kinetic study of small molecule gases formation - Jing He; Yuhan Yang; Chan Zou; Qiang Gao; Hongyun Hu; Kai Xu; Xi Li; Hong Yao (Journal of Environmental Chemical Engineering, 2023)

Template-assisted synthesis of ultrathin graphene aerogels as bifunctional oxygen electrocatalysts for water splitting and alkaline/neutral zinc-air batteries - Qiang Li; Zhifang Sun; Chunyang Yin; Yang Chen; Dingjie Pan; Bingzhe Yu; Yi Zhang; Ting He; Shaowei Chen (Chemical Engineering Journal, 2023)

Sematic segmentation of loess landslides with STAPLE mask and fully connected conditional random field - Huajin Li; Yusen He; Qiang Xu; Jiahao Deng; Weile Li; Yong Wei; Jingren Zhou (Landslides, 2023)

Vitamin D deficiency leads to the abnormal activation of the complement system - Huan Li; Xiaomin Xie; Guirong Bai; Dan Qiang; Li Zhang; Huili Liu; Yanting He; Yanpan Tang; Ling Li (Immunologic Research, 2023)
Vitamin D deficiency can damage the human immune system, and the complement system is a key component of the immune system. This study aimed to elucidate the mechanism by which vitamin D affects the immune system by analyzing the changes in the protein expression of the complement system under different vitamin D levels. We selected 40 participants and divided them into three groups according to their serum levels of 25-hydroxyvitamin D (25(OH)VD): group A, 25(OH)VD ≥ 40 ng/mL; group B, 30 ng/mL ≤ 25(OH)VD < 40 ng/mL; and group C, 25(OH)VD < 30 ng/mL. Serum samples were subjected to biochemical analysis, followed by proteomic analysis using high-throughput untargeted proteomic techniques. Vitamin D deficiency increased the levels of fasting blood sugar, fasting serum insulin, and homeostasis model assessment (HOMA) of insulin resistance and decreased the secretion of HOMA of β-cell function, which led to insulin resistance and glucose metabolism disorder. Moreover, vitamin D deficiency resulted in the abnormal expression of 56 differential proteins, among which the expression levels of complement factor B, complement component C9, inducible co-stimulator ligand, and peptidase inhibitor 16 significantly changed with the decrease in vitamin D content. Functional enrichment analysis of these differential proteins showed that they were mainly concentrated in functions and pathways related to insulin secretion and inflammation. In conclusion, vitamin D deficiency not only contributes to insulin resistance and glucose metabolism disorder but also causes abnormal protein expression, resulting in the abnormal activation of the complement system. This study provides a novel theoretical basis for further studies on the relationship between vitamin D and the immune system.

Influence of CO2/HCO3− on Microbial Communities in Two Karst Caves with High CO2 - Jiyu Chen; Qiang Li; Qiufang He; Heinz C. Schröder; Zujun Lu; Daoxian Yuan (Journal of Earth Science, 2023)

Sedimentary geochemistry mediated by a specific hydrological regime in the water level fluctuation zone of the Three Gorges Reservoir, China - Dil Khurram; Yuhai Bao; Qiang Tang; Xiubin He; Jinlin Li; Jean de D. Nambajimana; Gratien Nsabimana (Environmental Science and Pollution Research, 2023)

Identification of mercury species in coal combustion by-products from power plants using thermal desorption-atomic fluorescence spectrometry on-line coupling system - Kai-Qiang He; Xiao-Ru Zhang; Yuan-Peng Li; Xue-Lei Duan; Yan Li; Yang-Hong Jiang; Xiao-Dong Yuan; Ke-Gang Zhang; Chun-Gang Yuan (Chemosphere, 2023)

Migration and diffusion of unsteady-state flow of volatile organic compounds on activated carbon adsorption beds under reverse ventilation - Tao Liu; Ning Qiang; Jiao He; Haichao Miao; Zhaohai Li; Yiqi Cao; Tianzhe Shi; Shumin Chen (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Analysis of iron in-use stocks: Evidence from the provincial and municipal levels in China - Qiang Yue; Xicui Chai; Feng Zhao; Junhao He; Yun Li; Heming Wang (Resources Policy, 2023)

Enhanced photocatalytic performance for water purification via oxygen-injected SnS2 nanosheets - Kexin Lv; Hengcheng Wan; Qiang He; Yi Li (Process Safety and Environmental Protection, 2023)

Evolution mechanism of soil hydrothermal parameters under freeze–thaw cycles: Regulatory significance of straw and biochar - Ze He; Renjie Hou; Qiang Fu; Tianxiao Li; Shoujie Zhang; Anshuang Su (Journal of Cleaner Production, 2023)

Review on recent progress in on-line monitoring technology for atmospheric pollution source emissions in China - Huanqin Wang; Jitong Zhou; Xue Li; Qiang Ling; Hongyuan Wei; Lei Gao; Ying He; Ming Zhu; Xiao Xiao; Youjiang Liu; Shan Li; Chilai Chen; et al. (Journal of Environmental Sciences, 2023)

Unravelling the regulation mechanism of nanoflower shaped Na3V2(PO4)3 in methanol–water system for high performance sodium ion batteries - Shiqi Sun; Yanjun Chen; Qiang Bai; Zhen Tian; Que Huang; Changcheng Liu; Shengnan He; Yaxiong Yang; Yanzhong Wang; Li Guo (Chemical Engineering Journal, 2023)

Molten salt-induction of geometrically deformed ruthenium single atom catalysts with high performance for aerobic oxidation of alcohols - Xiuli Dong; Yufei Jia; Mingyang Zhang; Siqi Ji; Leipeng Leng; J. Hugh Horton; Chang Xu; Cheng He; Qiang Tan; Jiangwei Zhang; Zhijun Li (Chemical Engineering Journal, 2023)

L-cysteine boosted Fe(III)-activated peracetic acid system for sulfamethoxazole degradation: Role of L-cysteine and mechanism - Yinhao Dai; Hui Cao; Chengdu Qi; Yijie Zhao; Yanni Wen; Chenmin Xu; Qiang Zhong; Dunyu Sun; Shuohua Zhou; Bing Yang; Shaogui Yang; Huan He; et al. (Chemical Engineering Journal, 2023)

Recovery of nutrients from aquaculture wastewater: Effects of light quality on the growth, biochemical composition, and nutrient removal of Chlorella sorokiniana - Yuqing He; Jie Lian; Lan Wang; Lu Tan; Fahad Khan; Yanhua Li; Hongxia Wang; Céline Rebours; Danxiang Han; Qiang Hu (Algal Research, 2023)

OsPPR11 encoding P-type PPR protein that affects group II intron splicing and chloroplast development - Qiang Zhang; Changzhao Chen; Yaliang Wang; Mengxing He; Zhiwen Li; Lan Shen; Qing Li; Li Zhu; Deyong Ren; Jiang Hu; Zhenyu Gao; Guangheng Zhang; et al. (Plant Cell Reports, 2022)

Isolation and identification of two Beauveria bassiana strains from silkworm, Bombyx mori - Yiling Zhang; Xu Yang; Jiao Zhang; Mingzhen Ma; Ping He; Yu Li; Qiang Wang; Xudong Tang; Zhongyuan Shen (Folia Microbiologica, 2022)

Climate change increased the compound extreme precipitation-flood events in a representative watershed of the Yangtze River Delta, China - Yuxiu He; Qiang Wang; Youpeng Xu; Ziyi Li; Jia Yuan; Miao Lu; Zhixin Lin (Stochastic Environmental Research and Risk Assessment, 2022)

The green paradox puzzle: fiscal decentralisation, environmental regulation, and agricultural carbon intensity in China - Qiang He; Xin Deng; Chuan Li; Zhongcheng Yan; Fangxia Kong; Yanbin Qi (Environmental Science and Pollution Research, 2022)

Temporal-spatial variation, source forensics of PAHs and their derivatives in sediment from Songhua River, Northeastern China - Rashid Mohammed; Zi-Feng Zhang; Ying-Hua Hu; Chao Jiang; Zhi-Qiang He; Wen-Juan Wang; Yi-Fan Li (Environmental Geochemistry and Health, 2022)

Saturated permeability of compacted loess based on low-field nuclear magnetic resonance (NMR) - Jialiang Liu; Qiang Xu; Pinliang Li; Pan He; Chuanhao Pu; Kuanyao Zhao; Dalei Peng; Zhuo Wang (Bulletin of Engineering Geology and the Environment, 2022)

Increased microbial and substrate complexity result in higher molecular diversity of the dissolved organic matter pool - Qi Chen; Christian Lønborg; Feng Chen; Michael Gonsior; Yunyun Li; Ruanhong Cai; Chen He; Jiaxin Chen; Yu Wang; Quan Shi; Nianzhi Jiao; Qiang Zheng (Limnology and Oceanography, 2022)
Marine dissolved organic matter (DOM) represents one of the largest reduced carbon pools on Earth. Diverse microbial metabolic activities play important roles in shaping this pool. However, the links between changing DOM substrates and microbial communities and its influence on the microbial produced DOM remain poorly understood. In this study, we investigated how the addition of substrates with different complexity (glucose, laminarin, and Synechococcus ‐derived DOM) impacted the production of new DOM by an individual opportunist Alteromonas strain and a coastal natural microbial community. Our experiments reveal that the microbial complexity was more important than the substrate in shaping the molecular composition of DOM. Furthermore, our results showed that the DOM composition played a larger role in shaping the microbial compositions than the concentrations of DOM and inorganic nutrients. Combined our network analysis revealed that complex substrates resulted in higher molecular diversity of the microbial produced DOM, sustained a higher microbial diversity, and maintained a more diverse association between microbial communities and DOM molecules. Overall, the present study indicate that the microbial diversity contributes to DOM molecular diversity and vice versa, highlighting the importance of microbial–substrate interactions in shaping the marine DOM pool.

Model tests on horizontal load-bearing and deformation resistance capacities of pile-bucket foundation in soft seabed soil - Ben He; Zhi-ying Yuan; Zhen-qiang Jiang; Ding-yu Ni; Li Shi; Zong-hao Yuan; Hong-lei Sun (Marine Georesources & Geotechnology, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

VGLUT3 neurons in median raphe control the efficacy of spatial memory retrieval via ETV4 regulation of VGLUT3 transcription - Aodi He; Chen Zhang; Xiao Ke; Yao Yi; Quntao Yu; Tongmei Zhang; Hongyan Yu; Huiyun Du; Hao Li; Qing Tian; Ling-Qiang Zhu; Youming Lu (Science China Life Sciences, 2022)

Evaluating the Response of a Tunnel Subjected to Strike-Slip Fault Rupture in Conjunction with Model Test and Hybrid Discrete–Continuous Numerical Modeling - Cui Zhen; Li Jian-he; Fu Xing-wei; Sheng Qian; Zhou Guang-xin; Ma Ya-li-na; Wang Tian-qiang (Rock Mechanics and Rock Engineering, 2022)

Stress conditions induced circRNAs profile of extracellular vesicles in brain microvascular endothelial cells - Xiao-Li Min; Hecun Zou; Jianghong Yan; Qiang Lyu; Xiang He; Fei-Fei Shang (Metabolic Brain Disease, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Stability evaluation for steep bank slope with microseismic monitoring in Three Gorges Reservoir area - Qing-ming Xie; Kui Long; Zi-mu Li; Li-chuan Chen; Hong Liu; Hong Xu; Fei He; Dan Liang; Xue-kun Xiang; Qiang Ma (Journal of Mountain Science, 2022)

Re-evaluation of the identities of Glossadelphus borneensis and its associated synonyms, G. attenuatus and G. nitidus - Zhao-Qin Yi; Si He; Jun-Jie Wang; Li-Qiang Mu; Yu Jia (Brittonia, 2022)

Possible implication of miR-142-3p in coronary microembolization induced myocardial injury via ATXN1L/HDAC3/NOL3 axis - Yuli Xu; Xiangwei Lv; Ruping Cai; Yanling Ren; Shirong He; Wei Zhang; Quanzhong Li; Xiheng Yang; Rixin Dai; Riming Wei; Qiang Su (Journal of Molecular Medicine, 2022)

Modification of phreatic line calculation model for landslide accumulation in the Three Gorges Reservoir area - He Yang; Minggao Tang; Qiang Xu; Xianxuan Xiao; Huajin Li (Bulletin of Engineering Geology and the Environment, 2022)

Phenotypic plasticity of light use favors a plant invader in nitrogen‐enriched ecosystems - Xiao Xu; Chenhao Zhou; Qiang He; Shiyun Qiu; Yan Zhang; Ji Yang; Bo Li; Ming Nie (Ecology, 2022)
Eutrophication is believed to promote plant invasion, resulting in high growth performances of invasive plants and, therefore, the great potential for growth‐induced intraspecific competition for light. Current hypotheses predict how eutrophication promotes plant invasion but fail to explain how great invasiveness is maintained under eutrophic conditions. In diverse native communities, co‐occurring plants of varying sizes can avoid light competition by exploiting light complementarily; however, whether this mechanism applies to intraspecific competition in invasive plant populations remains unknown. Using a 2‐year field nitrogen (N)‐enrichment experiment on one of the global invasive plants, Spartina alterniflora , we found that the plasticity of light use reduced intraspecific competition and increased biomass production in S. alterniflora . This plasticity effect was enhanced when S. alterniflora had no nutrient limitations. In the N‐enrichment treatments, the height difference among S. alterniflora ramets increased as light intensity decreased under the canopy. Compared with ambient N, under N enrichment, shorter individuals increased their light‐use efficiency and specific leaf area in response to the reduced light intensity under the canopy. However, such ecophysiological plasticity was not found for taller individuals. Our findings revealed that the light‐use plasticity of short individuals can be envisaged as a novel mechanism by which an invasive plant alleviates intraspecific competition and increases its invasiveness, challenging the prevailing perspective that the invasiveness of exotic plants is constrained by intraspecific competition.

Consolidation behavior and microstructure properties of cement-treated dredged soil during the stress curing - Xingxing He; Yijun Chen; Yuan Li; Dongdong Guo; Qiang Xue; Shiquan Wang; Ping Wang; Yong Wan; Lei Liu (Marine Georesources & Geotechnology, 2022)

Cassiterite oxygen isotopes in magmatic-hydrothermal systems: in situ microanalysis, fractionation factor, and applications - Yang Li; Sheng He; Rong-Qing Zhang; Xian-Wu Bi; Lian-Jun Feng; Guo-Qiang Tang; Wen-Zhong Wang; Fang Huang; Xian-Hua Li (Mineralium Deposita, 2022)

MicroRNA-136-5p protects cardiomyocytes from coronary microembolization through the inhibition of pyroptosis - Ruping Cai; Yuli Xu; Yanling Ren; Shirong He; Jing Zheng; Binghui Kong; Quanzhong Li; Xiheng Yang; Rixin Dai; Riming Wei; Qiang Su (Apoptosis, 2022)

Detection and segmentation of loess landslides via satellite images: a two-phase framework - Huajin Li; Yusen He; Qiang Xu; Jiahao Deng; Weile Li; Yong Wei (Landslides, 2022)

Establishment of Galectin-3 Time-resolved Fluoroimmunoassay and its Application in Idiopathic Membranous Nephropathy - Xiaomei Yu; Lingli Chen; Bo Lin; Li Zhang; Xue Yang; Xiaobin Liu; Pengguo Xia; Yueming Liu; Shaoxiong Zheng; Xiumei Zhou; Yigang Wang; Yuan Qin; et al. (Journal of Fluorescence, 2022)

Aconitine linoleate, a natural lipo-diterpenoid alkaloid, stimulates anti-proliferative activity reversing doxorubicin resistance in MCF-7/ADR breast cancer cells as a selective topoisomerase IIα inhibitor - Shangxian Luan; Yingying Gao; Xiaoxia Liang; Li Zhang; Qiang Wu; Yunkai Hu; Lizi Yin; Changliang He; Shixi Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Influences of aeration induced turbulence on growth and competition of Microcystis and Scenedesmus in the presence of sediments with varying particle sizes - Qiang He; Yiyao Wang; Ming Li (Journal of Oceanology and Limnology, 2022)

Long noncoding RNA XIST modulates microRNA-135/CREB1 axis to influence osteogenic differentiation of osteoblast-like cells in mice with tibial fracture healing - Ying Zhang; Qiang Yuan; Qiushi Wei; Peifeng Li; Zhikun Zhuang; Jitian Li; Youwen Liu; Leilei Zhang; Zhinan Hong; Wei He; Haibin Wang; Wuyin Li (Human Cell, 2022)

Correction to: Enhanced adsorption of phosphorus in soil by lanthanum-modified biochar: improving phosphorus retention and storage capacity - Di Zhao; Yuan Luo; Yi-yang Feng; Qiu-ping He; Li-sheng Zhang; Ke-qiang Zhang; Feng Wang (Environmental Science and Pollution Research, 2021)

Enhanced adsorption of phosphorus in soil by lanthanum-modified biochar: improving phosphorus retention and storage capacity - Di Zhao; Yuan Luo; Yi-yang Feng; Qiu-ping He; Li-sheng Zhang; Ke-qiang Zhang; Feng Wang (Environmental Science and Pollution Research, 2021)

Pyramiding the antimicrobial PR1aCB and AATCB genes in ‘Tarocco’ blood orange (Citrus sinensis Osbeck) to enhance citrus canker resistance - Aihong Peng; Jingyun Zhang; Xiuping Zou; Yongrui He; Lanzhen Xu; Tiangang Lei; Lixiao Yao; Qiang Li; Shanchun Chen (Transgenic Research, 2021)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

High-resolution genome-wide association study and genomic prediction for disease resistance and cold tolerance in wheat - Yunlong Pang; Yuye Wu; Chunxia Liu; Wenhui Li; Paul St. Amand; Amy Bernardo; Danfeng Wang; Lei Dong; Xiufang Yuan; Huirui Zhang; Meng Zhao; Linzhi Li; et al. (Theoretical and Applied Genetics, 2021)

Biopolymer-based flocculants: a review of recent technologies - Xincheng Jiang; Yisen Li; Xiaohui Tang; Junyi Jiang; Qiang He; Zikang Xiong; Huaili Zheng (Environmental Science and Pollution Research, 2021)

Sporadic hand, foot, and mouth disease cases associated with non-C4 enterovirus 71 strains in Xiamen, China, from 2009 to 2018 - Mengyuan Chen; Shuizhen He; Qiang Yan; Jianmei Zhang; Caiyu Li; Xiaosong Su; Shiyin Zhang; Tingdong Li; Shengxiang Ge; Min Chen; Jun Zhang; Ningshao Xia (Archives of Virology, 2021)

Fluorescence characteristics of dissolved organic matter in several independent water bodies: possible sources and land-use effects - Qiang He; Li Gao; Zilin Wang; Yuanjiang Tang; Baozhu Pan; Ming Li (Environmental Science and Pollution Research, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Spatial and environmental factors contributing to phytoplankton biogeography and biodiversity in mountain ponds across a large geographic area - Chao Chang; Li Gao; Jing Wei; Ning Ma; Qiang He; Baozhu Pan; Ming Li (Aquatic Ecology, 2021)

Influence of major water conservation projects on river channels and shorelines in the middle and lower reaches of the Yangtze River - Yue-hua Jiang; He-qin Cheng; Quan-ping Zhou; Yun Li; Guo-qiang Yang; Yang Jin; Shi-jia Mei; Xuan Gu; Hong Zhang (Arabian Journal of Geosciences, 2021)

Effects of Spray Parameters on the Effective Spray Width of Single-Rotor Drone in Sugarcane Plant Protection - Ping Zhang; Wei Zhang; Hai-Tian Sun; Feng-Guang He; Hai-Ba Fu; Li-Qiang Qi; Li-Juan Yu; Li-Yu Jin; Bo Zhang; Jian-Sheng Liu (Sugar Tech, 2021)

Habitat‐dependent impacts of exotic plant invasions on benthic food webs in a coastal wetland - Sikai Wang; Qiang He; Youzheng Zhang; Qiang Sheng; Bo Li; Jihua Wu (Limnology and Oceanography, 2021)
Exotic plants with wide ecological niches often invade multiple types of habitats, leading to homogenization of ecosystem structure and functions. How exotic plant invasions affect the structure and functions of benthic food webs in different habitats is poorly understood. We tested how Spartina alterniflora invasions affected benthic food webs in four contrasting types of habitat ( Scirpus mariqueter marshes, Phragmites australis marshes, unvegetated tidal creeks, and bare tidal flats) in the Yangtze estuary. We examined distribution pattern of benthic macroinvertebrates, and documented the differences in basal resources of benthic food web by stable isotope analyses of δ 13 C and δ 15 N in different habitats. Our results showed that in unvegetated habitats, conversion of tidal creeks and bare tidal flats to exotic marshes following Spartina invasions significantly altered the functional composition of benthic food webs, which was driven partially by bottom‐up processes related to a consumer dietary shift from benthic organic matter to detritus (trophic effect) and by alteration in species composition related to habitat changes (nontrophic effect). In vegetated native habitats, while the replacement of native plants by Spartina consistently led to a shift in consumer diet from benthic organic matter to detritus, it did not significantly alter the functional composition of benthic food webs. These data suggested the relative importance of trophic and nontrophic effects of plant invasions on benthic food webs could vary with habitat structure (e.g., the presence of native vegetation). Our study provides new insights into the mechanisms underlying homogenization of ecosystem structure and functions by exotic plant invasions.

Effects of iron and humic acid on competition between Microcystis aeruginosa and Scenedesmus obliquus revealed by HPLC analysis of pigments - Miaomiao Zhao; Qiang He; Chongtai Chen; Yaqi Tian; Jing Wei; Pengfei Duan; Haiming Wu; Ming Li (Journal of Oceanology and Limnology, 2021)

QTL mapping for foxtail millet plant height in multi-environment using an ultra-high density bin map - Qiang He; Hui Zhi; Sha Tang; Lu Xing; Suying Wang; Haigang Wang; Aiying Zhang; Yuhui Li; Ming Gao; Haijin Zhang; Guoqiu Chen; Shutao Dai; et al. (Theoretical and Applied Genetics, 2021)

Injectable collagen scaffold promotes swine myocardial infarction recovery by long-term local retention of transplanted human umbilical cord mesenchymal stem cells - Qiang Wang; Xiaojun He; Bin Wang; Jun Pan; Chunying Shi; Jie Li; Liudi Wang; Yannan Zhao; Jianwu Dai; Dongjin Wang (Science China Life Sciences, 2021)

Highly enriched N‐containing organic molecules of Synechococcus lysates and their rapid transformation by heterotrophic bacteria - Qiang Zheng; Wenxin Lin; Yu Wang; Yunyun Li; Chen He; Yuan Shen; Weidong Guo; Quan Shi; Nianzhi Jiao (Limnology and Oceanography, 2021)
Phytoplankton are major contributors of labile dissolved organic matter to marine euphotic zone ecosystems. Viral‐mediated phytoplankton lysis releases a considerable amount of bioavailable cellular contents and facilitates localized heterotrophic bacterial growth. The rapid turnover times of this labile organic matter renders it difficult to trace their transformation within natural environments. In the present study, we used a model phototroph‐heterotroph coculture system to investigate the organic molecular variation during cyanophage‐induced Synechococcus lysis and post‐lysis periods using fluorescence spectroscopy and ultrahigh resolution mass spectrometry analyses. Approximately 80% of the Synechococcus lysates were respired to carbon dioxide within 2 days coupled to rapid regeneration of inorganic nutrients. Five fluorescent dissolved organic matter components were detected in the incubations including four humic‐like and one protein‐like components, and their abundances varied markedly with the succession of the viral lysis process. Viral lysis promoted the transformation of Synechococcus biomass to dissolved organic matter, and heterotrophic bacterial metabolism facilitated the transformation of organic molecules from relatively high (avg. ~ 430 Da) to low (avg. ~ 360 Da) molecular weight, corresponding to variation in their bioavailability. The Synechococcus ‐derived organic matter was highly enriched in N‐containing organic molecules. Identified metabolites within the cultures primarily comprised amino acids or oligopeptides and other low‐molecular‐weight organic acids, carbohydrates, nucleotides, lipids, biogenic amines, and porphyrins. Among these, oligopeptides, nucleotides, and lipid compounds significantly increased with viral lysis. These results provide insight into biogeochemical cycling mediated by viral shunts in oceans, thus deepening our understanding of microbial food webs at the molecular level.

Rapid and highly efficient genomic engineering with a novel iEditing device for programming versatile extracellular electron transfer of electroactive bacteria - Yang‐Yang Fan; Qiang Tang; Yang Li; Feng‐He Li; Jing‐Hang Wu; Wen‐Wei Li; Han‐Qing Yu (Environmental Microbiology, 2021)
Summary The advances in synthetic biology bring exciting new opportunities to reprogram microorganisms with novel functionalities for environmental applications. For real‐world applications, a genetic tool that enables genetic engineering in a stably genomic inherited manner is greatly desired. In this work, we design a novel genetic device for rapid and efficient genome engineering based on the i ntron‐encoded homing‐endonuclease empowered genome editing (iEditing). The iEditing device enables rapid and efficient genome engineering in Shewanella oneidensis MR‐1, the representative strain of the electroactive bacteria group. Moreover, combining with the Red or RecET recombination system, the genome‐editing efficiency was greatly improved, up to approximately 100%. Significantly, the iEditing device itself is eliminated simultaneously when genome editing occurs, thereby requiring no follow‐up to remove the encoding system. Then, we develop a new extracellular electron transfer (EET) engineering strategy by programming the parallel EET systems to enhance versatile EET. The engineered strains exhibit sufficiently enhanced electron output and pollutant reduction ability. Furthermore, this device has demonstrated its great potential to be extended for genome editing in other important microbes. This work provides a useful and efficient tool for the rapid generation of synthetic microorganisms for various environmental applications.

Identification of the interactions and feedbacks among watershed water-energy balance dynamics, hydro-meteorological factors, and underlying surface characteristics - Xiaoting Wei; Shengzhi Huang; Qiang Huang; Guoyong Leng; Hao Wang; Li He; Jing Zhao; Dong Liu (Stochastic Environmental Research and Risk Assessment, 2021)

Freeze tolerance and the underlying metabolite responses in the Xizang plateau frog, Nanorana parkeri - Yonggang Niu; Wangjie Cao; Jinzhou Wang; Jie He; Kenneth B. Storey; Li Ding; Xiaolong Tang; Qiang Chen (Journal of Comparative Physiology B, 2021)

OsPFA-DSP2 Encodes a Functional Tyrosine-Specific Phosphatase, and Negatively Regulates the Responses to Xanthomonas Oryzae pv. Oryzae in Overexpressing Rice Plants - Hanjie He; Meng Li; Wenkai Sun; Qiang He; Huafeng Deng; Wende Yan (Tropical Plant Biology, 2020)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Analyzing adaptation strategies for maize production under future climate change in Guanzhong Plain, China - Qaisar Saddique; Huanjie Cai; Jiatun Xu; Ali Ajaz; Jianqiang He; Qiang Yu; Yunfei Wang; Hui Chen; Muhammad Imran Khan; De Li Liu; Liang He (Mitigation and Adaptation Strategies for Global Change, 2020)

Genomewide analysis of the CIII peroxidase family in sweet orange (Citrus sinensis) and expression profiles induced by Xanthomonas citri subsp. citri and hormones - Qiang Li; Wanfu Dou; Jingjing Qi; Xiujuan Qin; Shanchun Chen; Yongrui He (Journal of Genetics, 2020)

Activation of the bitter taste sensor TRPM5 prevents high salt-induced cardiovascular dysfunction - Hao Wu; Yuanting Cui; Chengkang He; Peng Gao; Qiang Li; Hexuan Zhang; Yanli Jiang; Yingru Hu; Xiao Wei; Zongshi Lu; Tianyi Ma; Daoyan Liu; et al. (Science China Life Sciences, 2020)

Development and current state of seawater shrimp farming, with an emphasis on integrated multi‐trophic pond aquaculture farms, in China – a review - Zhi‐Qiang Chang; Amir Neori; Yu‐Ying He; Ji‐Tao Li; Ling Qiao; Steven Ian Preston; Ping Liu; Jian Li (Reviews in Aquaculture, 2020)
Shrimp farming has been the fastest‐growing sector in seawater aquaculture and has contributed to improving the farmers income and the utilization efficiency of aquaculture resources in China. The shrimp industry has deployed ever‐improved and innovated methods, from extensive farming to semi‐intensive and intensive farming. Various high‐density intensive culture models, such as high‐land, greenhouse and indoor industrialized culture models, have been used for shrimp pond farming in the coastal area. However, efficiency, environmental and social considerations have led to an increasing adoption of the environmentally‐friendly culture model called integrated multi‐trophic aquaculture (IMTA). This has occurred most rapidly along the northern and central coasts of China. The deployed IMTA culture models reviewed here are shrimp + crab, shrimp + fish, shrimp + sea cucumber, shrimp + jellyfish + clam, shrimp + crab + clam, shrimp + crab + clam + fish and the ridgetail white shrimp polyculture in saline alkaline water, which have been tailored to local conditions and organisms' characteristics. Suitable organism varieties and the maintenance of suitable eco‐friendly water quality have been key to success. The eco‐friendly IMTA culture models described here fully exploit the pond culture resources, to increase production with minimal additional feed and labor inputs, while reducing effluent emissions and treatment cost. The performance of shrimp IMTA models is compared to shrimp monoculture models regarding the economics. An equally important outcome of this publication is making generally accessible the findings from a vast Chinese scientific literature on shrimp culture that has hitherto been unavailable in English.

Chemical composition of Erycibe schmidtii and antiproliferative activity of scopoletin on immature dendritic cells - Wang Ren; Yantang Wang; Qinhui He; Yue Zhou; Chunxin Li; Wenling Wang; Xiao Leng; Ting Zeng; Qiang Zou; Limei Li (Natural Product Research, 2020)

Dynamic response and mechanical deformation properties of the soil cutting slope under train cyclic loads - Qiang Xie; Zhi-hui Wu; Chun-bo He; Jie Dong; Zhi-lin Cao; Li Liang (Arabian Journal of Geosciences, 2020)

Modeling leaf senescence of deciduous tree species in Europe - Qiang Liu; Shilong Piao; Matteo Campioli; Mengdi Gao; Yongshuo H. Fu; Kai Wang; Yue He; Xiangyi Li; Ivan A. Janssens (Global Change Biology, 2020)
Autumnal leaf senescence signals the end of photosynthetic activities in temperate deciduous trees and consequently exerts a strong control on various ecological processes. Predicting leaf senescence dates (LSD) with high accuracy is thus a prerequisite for better understanding the climate–ecosystem interactions. However, modeling LSD at large spatial and temporal scales is challenging. In this study, first, we used 19972 site‐year records (848 sites and four deciduous tree species) from the PAN European Phenology network to calibrate and evaluate six leaf senescence models during the period 1980–2013. Second, we extended the spatial analysis by repeating the procedure across Europe using satellite‐derived end of growing season and a forest map. Overall, we found that models that considered photoperiod and temperature interactions outperformed models using simple temperature or photoperiod thresholds for Betula pendula , Fagus sylvatica and Quercus robur . On the contrary, no model displayed reasonable predictions for Aesculus hippocastanum . This inter‐model comparison indicates that, contrary to expectation, photoperiod does not significantly modulate the accumulation of cooling degree days (CDD). On the other hand, considering the carryover effect of leaf unfolding date could promote the models’ predictability. The CDD models generally matched the observed LSD at species level and its interannual variation, but were limited in explaining the inter‐site variations, indicating that other environmental cues need to be considered in future model development. The discrepancies remaining between model simulations and observations highlight the need of manipulation studies to elucidate the mechanisms behind the leaf senescence process and to make current models more realistic.

Colletotrichum fructicola STE50 is required for vegetative growth, asexual reproduction, appressorium formation, pathogenicity and the response to external stress - Yan-ying Chen; Jun-ang Liu; Shi-qiang Jiang; He Li; Guo-ying Zhou (Journal of Plant Pathology, 2020)

Parametric study of integrity on the mechanical properties of transversely isotropic rock mass using DEM - Jiu-yang Huan; Ming-ming He; Zhi-qiang Zhang; Ning Li (Bulletin of Engineering Geology and the Environment, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Epidural Spinal Cord Stimulation Promotes Motor Functional Recovery by Enhancing Oligodendrocyte Survival and Differentiation and by Protecting Myelin after Spinal Cord Injury in Rats - Gang Li; Zhong-Kai Fan; Guang-Fei Gu; Zhi-Qiang Jia; Qiang-Qiang Zhang; Jun-Yu Dai; Shi-Sheng He (Neuroscience Bulletin, 2020)

Nanodosimetric understanding to the dependence of the relationship between dose-averaged lineal energy on nanoscale and LET on ion species - Tianyuan Dai; Hui Zhang; Xinguo Liu; Zhongying Dai; Pengbo He; Yuanyuan Ma; Guosheng Shen; Weiqiang Chen; Qiang Li (Physical and Engineering Sciences in Medicine, 2020)

Modeling and predicting reservoir landslide displacement with deep belief network and EWMA control charts: a case study in Three Gorges Reservoir - Huajin Li; Qiang Xu; Yusen He; Xuanmei Fan; Songlin Li (Landslides, 2020)

Genome-Wide Association Study of Cerebral Microbleeds on MRI - Hong-Qi Li; Wen-Jie Cai; Xiao-He Hou; Mei Cui; Lan Tan; Jin-Tai Yu; Qiang Dong (Neurotoxicity Research, 2020)

Interannual variability of South China Sea winter circulation: response to Luzon Strait transport and El Niño wind - Qiang Wang; Lili Zeng; Yeqiang Shu; Qinyan Liu; Tingting Zu; Jian Li; Ju Chen; Yunkai He; Dongxiao Wang (Climate Dynamics, 2020)

A revisit of the interannual variation of the South China Sea upper layer circulation in summer: correlation between the eastward jet and northward branch - Tingting Zu; Dongxiao Wang; Qiang Wang; Mingting Li; Jun Wei; Bingxu Geng; Yunkai He; Ju Chen (Climate Dynamics, 2020)

Successful early warning and emergency response of a disastrous rockslide in Guizhou province, China - Xuanmei Fan; Qiang Xu; Jie Liu; Srikrishnan Siva Subramanian; Chaoyang He; Xing Zhu; Li Zhou (Landslides, 2019)

Improved protocol for the transformation of adult Citrus sinensis Osbeck ‘Tarocco’ blood orange tissues - Aihong Peng; Xiuping Zou; Lanzhen Xu; Yongrui He; Tiangang Lei; Lixiao Yao; Qiang Li; Shanchun Chen (In Vitro Cellular & Developmental Biology - Plant, 2019)

Long-term pollutant removal performance and mitigation of rainwater quality deterioration with ceramsite and Cyperus alternifolius in mountainous cities of China - Hongxiang Chai; Zi Chen; Zhiyu Shao; Siping Deng; Liang Li; Yu Xiang; Li Li; Xuebin Hu; Qiang He (Environmental Science and Pollution Research, 2019)

Determination of the Dynamic Propagation Toughness of Marble Based on a Fractal Propagation Model and an Experimental–Numerical–Analytical Method - Yiqiang Lu; Mingzhong Gao; Sheng Zhang; Qiang Liu; Zhiqiang He; Cong Li (Rock Mechanics and Rock Engineering, 2019)

Influence of Different Propulsion Speeds on the Characteristics of Mine Pressure in the Fully Mechanized Caving Face During Rotary Stage - Liang Li; Xue He; Yong-qiang Chen; Ya-chun Li; Chen-hao Shi; Yu-ping Zhu (Geotechnical and Geological Engineering, 2019)

Fractal characterization of sediment particle size distribution in the water-level fluctuation zone of the Three Gorges Reservoir, China - Jin-lin Li; Yu-hai Bao; Jie Wei; Xiu-bin He; Qiang Tang; Jean de Dieu Nambajimana (Journal of Mountain Science, 2019)

DNA methylation and mRNA expression of COL6A3 in antler mesenchyme of female and male reindeer - Jian-Cheng Zhai; Ruo-Bing Han; Sheng-Nan Wang; Qiang-Hui Wang; Yan-Ling Xia; Wei-Shi Liu; Ya-Jie Yin; He-Ping Li (Genes & Genomics, 2019)

Nitrous oxide emission mitigation during low–carbon source wastewater treatment: effect of external carbon source supply strategy - Hongxiang Chai; Siping Deng; Xiaoyuan Zhou; Chuanrong Su; Yu Xiang; Yan Yang; Zhiyu Shao; Li Gu; Xuan Xu; Fangying Ji; Qiang He (Environmental Science and Pollution Research, 2019)

Proteomics analysis of HSV-1-induced alterations in mouse brain microvascular endothelial cells - Hui Liu; Chu-Xin Huang; Qiang He; Dong Li; Min-Hua Luo; Fei Zhao; Wei Lu (Journal of NeuroVirology, 2019)

The enhancement roles of sulfate on the adsorption of sodium dodecylsulfate by calcium-based layered double hydroxide: microstructure and thermal behaviors - Ping Zhang; Mingxue Xiang; Peng Li; Sida Ouyang; Tao He; Qiang Deng (Environmental Science and Pollution Research, 2019)

Alternative respiration pathway is involved in the response of highland barley to salt stress - Qiang He; Xiaomin Wang; Li He; Lei Yang; Shengwang Wang; Yurong Bi (Plant Cell Reports, 2019)

Comparison of data-driven models of loess landslide runout distance estimation - Qiang Xu; Huajin Li; Yusen He; Fangzhou Liu; Dalei Peng (Bulletin of Engineering Geology and the Environment, 2019)

Formation, extracellular polymeric substances, and structural stability of aerobic granules enhanced by granular activated carbon - Zixuan Liang; Qianqian Tu; Xiaoxuan Su; Xiangyu Yang; Junyu Chen; Yi Chen; Hong Li; Caihong Liu; Qiang He (Environmental Science and Pollution Research, 2019)

Pollutant removal performance of an integrated system that combines a baffled vertical-flow wetland and a scenic water body - Hongxiang Chai; Wenqian Li; Zhiyu Shao; Liang Li; Qiang He (Environmental Science and Pollution Research, 2019)

A half-type ABC transporter FeSTAR1 regulates Al resistance possibly via UDP-glucose-based hemicellulose metabolism and Al binding - Jia Meng Xu; He Qiang Lou; Jian Feng Jin; Wei Wei Chen; Jiang Xue Wan; Wei Fan; Jian Li Yang (Plant and Soil, 2018)

LeSPL-CNR negatively regulates Cd acquisition through repressing nitrate reductase-mediated nitric oxide production in tomato - Wei Wei Chen; Jian Feng Jin; He Qiang Lou; Li Liu; Leon V. Kochian; Jian Li Yang (Planta, 2018)

Prediction of landslide displacement with an ensemble-based extreme learning machine and copula models - Huajin Li; Qiang Xu; Yusen He; Jiahao Deng (Landslides, 2018)

Differential responses of canopy nutrients to experimental drought along a natural aridity gradient - Wentao Luo; Xiaoan Zuo; Wang Ma; Chong Xu; Ang Li; Qiang Yu; Alan K. Knapp; Roberto Tognetti; Feike A. Dijkstra; Mai‐He Li; Guodong Han; Zhengwen Wang; et al. (Ecology, 2018)
The allocation and stoichiometry of plant nutrients in leaves reflect fundamental ecosystem processes, biotic interactions, and environmental drivers such as water availability. Climate change will lead to increases in drought severity and frequency, but how canopy nutrients will respond to drought, and how these responses may vary with community composition along aridity gradients is poorly understood. We experimentally addressed this issue by reducing precipitation amounts by 66% during two consecutive growing seasons at three sites located along a natural aridity gradient. This allowed us to assess drought effects on canopy nitrogen (N) and phosphorus (P) concentrations in arid and semiarid grasslands of northern China. Along the aridity gradient, canopy nutrient concentrations were positively related to aridity, with this pattern was driven primarily by species turnover (i.e., an increase in the relative biomass of N‐ and P‐rich species with increasing aridity). In contrast, drought imposed experimentally increased N but decreased P concentrations in plant canopies. These changes were driven by the combined effects of species turnover and intraspecific variation in leaf nutrient concentrations. In addition, the sensitivity of canopy N and P concentrations to drought varied across the three sites. Canopy nutrient concentrations were less affected by drought at drier than wetter sites, because of the opposing effects of species turnover and intraspecific variation, as well as greater drought tolerance for nutrient‐rich species. These contrasting effects of long‐term aridity vs. short‐term drought on canopy nutrient concentrations, as well as differing sensitivities among sites in the same grassland biome, highlight the challenge of predicting ecosystem responses to future climate change.

Effects of Wolbachia infection on the postmating response in Drosophila melanogaster - Zhen He; Hua-Bao Zhang; Shi-Tian Li; Wen-Juan Yu; John Biwot; Xiao-Qiang Yu; Yu Peng; Yu-Feng Wang (Behavioral Ecology and Sociobiology, 2018)

Multi-model ensemble projections of future extreme heat stress on rice across southern China - Liang He; James Cleverly; Bin Wang; Ning Jin; Chunrong Mi; De Li Liu; Qiang Yu (Theoretical and Applied Climatology, 2018)

Different susceptibility to porcine reproductive and respiratory syndrome virus infection among Chinese native pig breeds - Chunhua Meng; Lei Su; Yinxia Li; Qianming Zhu; Jingxin Li; Huili Wang; Qiang He; Chunling Wang; Wei Wang; Shaoxian Cao (Archives of Virology, 2018)

Joint structural and physiological control on the interannual variation in productivity in a temperate grassland: A data‐model comparison - Zhongmin Hu; Hao Shi; Kaili Cheng; Ying‐Ping Wang; Shilong Piao; Yue Li; Li Zhang; Jianyang Xia; Lei Zhou; Wenping Yuan; Steve Running; Longhui Li; et al. (Global Change Biology, 2018)
Given the important contributions of semiarid region to global land carbon cycle, accurate modeling of the interannual variability (IAV) of terrestrial gross primary productivity (GPP) is important but remains challenging. By decomposing GPP into leaf area index (LAI) and photosynthesis per leaf area (i.e., GPP_leaf), we investigated the IAV of GPP and the mechanisms responsible in a temperate grassland of northwestern China. We further assessed six ecosystem models for their capabilities in reproducing the observed IAV of GPP in a temperate grassland from 2004 to 2011 in China. We observed that the responses to LAI and GPP_leaf to soil water significantly contributed to IAV of GPP at the grassland ecosystem. Two of six models with prescribed LAI simulated of the observed IAV of GPP quite well, but still underestimated the variance of GPP_leaf, therefore the variance of GPP. In comparison, simulated pattern by the other four models with prognostic LAI differed significantly from the observed IAV of GPP. Only some models with prognostic LAI can capture the observed sharp decline of GPP in drought years. Further analysis indicated that accurately representing the responses of GPP_leaf and leaf stomatal conductance to soil moisture are critical for the models to reproduce the observed IAV of GPP_leaf. Our framework also identified that the contributions of LAI and GPP_leaf to the observed IAV of GPP were relatively independent. We conclude that our framework of decomposing GPP into LAI and GPP_leaf has a significant potential for facilitating future model intercomparison, benchmarking and optimization should be adopted for future data‐model comparisons.

Suitable flow pattern increases the removal efficiency of nitrogen in gravity sewers: a suitable anoxic and aerobic environment in biofilms - Qiang He; Feixian Yin; Hong Li; Yinliang Wang; Jingwei Xu; Hainan Ai (Environmental Science and Pollution Research, 2018)

Study of Phosphorus Removal by Using Sponge Iron Adsorption - Rui Xue; Jian Xu; Li Gu; Longhui Pan; Qiang He (Water, Air, & Soil Pollution, 2018)

The ileal FGF15/19 to hepatic FGFR4 axis regulates liver regeneration after partial hepatectomy in mice - Qiang Li; Qiang Zhao; Chuanzhao Zhang; Peng Zhang; Anbin Hu; Longjuan Zhang; Paul M. Schroder; Yi Ma; Zhiyong Guo; Xiaofeng Zhu; Xiaoshun He (Journal of Physiology and Biochemistry, 2018)

In Vitro-In Vivo Predictive Dissolution-Permeation-Absorption Dynamics of Highly Permeable Drug Extended-Release Tablets via Drug Dissolution/Absorption Simulating System and pH Alteration - Zi-qiang Li; Shuang Tian; Hui Gu; Zeng-guang Wu; Makafui Nyagblordzro; Guo Feng; Xin He (AAPS PharmSciTech, 2018)

Mapping deep targets based on integrated 3D MT-gravity interpretation: a case study - Yanling Shi; Zhanxiang He; Zuzhi Hu; Qiang Wei; Dechun Li; Cuixian Meng; Liansheng Ji; Sheng Zhang (Studia Geophysica et Geodaetica, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Administration of fentanyl via a slow intravenous fluid line compared with rapid bolus alleviates fentanyl-induced cough during general anesthesia induction - Min-qiang Liu; Feng-xian Li; Ya-kun Han; Jun-yong He; Hao-wen Shi; Li Liu; Ren-liang He (Journal of Zhejiang University-SCIENCE B, 2017)

MiR-181b Antagonizes Atherosclerotic Plaque Vulnerability Through Modulating Macrophage Polarization by Directly Targeting Notch1 - Tian-Hui An; Quan-Wei He; Yuan-Peng Xia; Sheng-Cai Chen; Suraj Baral; Ling Mao; Hui-Juan Jin; Ya-Nan Li; Meng-Die Wang; Jian-Guo Chen; Ling-Qiang Zhu; Bo Hu (Molecular Neurobiology, 2017)

Erratum to: The role of particle size of glyburide crystals in improving its oral absorption - Wenqian Yang; Yongjun Wang; Qiang Fu; Zhibin Guo; Bingjun Sun; Wen Liu; Yaxuan Liu; Simeng Mu; Mengran Guo; Jingru Li; Xiaohui Pu; Zhonggui He (Drug Delivery and Translational Research, 2017)

Occurrence and Distribution of Organophosphate Esters in Surface Soil and Street Dust from Chongqing, China: Implications for Human Exposure - Ming-Jing He; Ting Yang; Zhi-Hao Yang; Qi Li; Shi-Qiang Wei (Archives of Environmental Contamination and Toxicology, 2017)

Full genome analysis of swine genotype 3 hepatitis E virus isolated from eastern China - Jiang-bing Shuai; Lu-huan Li; Ai-yun Li; Yong-qiang He; Xiao-feng Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

The role of particle size of glyburide crystals in improving its oral absorption - Yongjun Wang; Wenqian Yang; Qiang Fu; Zhibin Guo; Bingjun Sun; Wen Liu; Yaxuan Liu; Simeng Mu; Mengran Guo; Jingru Li; Xiaohui Pu; Zhonggui He (Drug Delivery and Translational Research, 2017)

The promoting effect of soil carbonic anhydrase on the limestone dissolution rate in SW China - Qiang Li; Yuanyuan He; Zhongyi Li (Carbonates and Evaporites, 2017)

Diversity of Eukaryotic Algae in Propylene Oxide Saponification Wastewater Activated Sludge - Rong He; Xiangyu Fan; Pengfei Gu; Yan Ji; Junyu Shen; Ruirui Li; Yumei Li; Qiang Li (Water Conservation Science and Engineering, 2017)

An UDP-Glucosyltransferase Gene from Barley Confers Disease Resistance to Fusarium Head Blight - Li-Ping Xing; Li-Qiang He; Jin Xiao; Qi-Guang Chen; Ming-Hao Li; Yi Shang; Yan-Fei Zhu; Pei-Du Chen; Ai-Zhong Cao; Xiu-E Wang (Plant Molecular Biology Reporter, 2017)

Ecotoxicological bioassays of sediment leachates in a river bed flanked by decommissioned pesticide plants in Nantong City, East China - Yan Zhou; Fenghe Wang; Jinzhong Wan; Jian He; Qun Li; Qiang Chen; Jay Gao; Yusuo Lin; Shengtian Zhang (Environmental Science and Pollution Research, 2017)

Model Establishment for Ponding in Coal Mining Subsidence Areas and its Prediction: Case Study of Northern Jining, China - Fanxuan Zeng; Kan Wu; Qiang He; Xinpeng Diao; Liang Li (Geotechnical and Geological Engineering, 2017)

Effect of flow rate on growth and oxygen consumption of biofilm in gravity sewer - Jingwei Xu; Muzhi Li; Qiang He; Xingfu Sun; Xiangren Zhou; Zhenping Su; Hainan Ai (Environmental Science and Pollution Research, 2017)

Autoantibody to MOG suggests two distinct clinical subtypes of NMOSD - Yaping Yan; Yujing Li; Ying Fu; Li Yang; Lei Su; Kaibin Shi; Minshu Li; Qiang Liu; Aimee Borazanci; Yaou Liu; Yong He; Jeffrey L. Bennett; et al. (Science China Life Sciences, 2016)

A comparative study of strontium-substituted hydroxyapatite coating on implant’s osseointegration for osteopenic rats - Zhou-Shan Tao; Bing-Li Bai; Xing-Wen He; Wei Liu; Hang Li; Qiang Zhou; Tao Sun; Zheng-Liang Huang; Kai-kai Tu; Yang-Xun Lv; Wei Cui; Lei Yang (Medical & Biological Engineering & Computing, 2016)

Levels of five metals in male hair from urban and rural areas of Chongqing, China - Ming-Jing He; Shi-Qiang Wei; Yu-Xin Sun; Ting Yang; Qi Li; Deng-Xiang Wang (Environmental Science and Pollution Research, 2016)

Two-dimensional landslide dynamic simulation based on a velocity-weakening friction law - Wei Liu; Siming He; Xinpo Li; Qiang Xu (Landslides, 2016)

Soil nitrate–N residue, loss and accumulation affected by soil surface management and precipitation in a winter wheat-summer fallow system on dryland - Gang He; Zhaohui Wang; Fucui Li; Jian Dai; Xiaolong Ma; Qiang Li; Cheng Xue; Hanbing Cao; Sen Wang; Hui Liu; Laichao Luo; Ming Huang; et al. (Nutrient Cycling in Agroecosystems, 2016)

Cnga2 Knockout Mice Display Alzheimer’s-Like Behavior Abnormities and Pathological Changes - Ao-Ji Xie; En-Jie Liu; He-Zhou Huang; Yu Hu; Ke Li; Youming Lu; Jian-Zhi Wang; Ling-Qiang Zhu (Molecular Neurobiology, 2016)

Generation of regulatory dendritic cells after treatment with paeoniflorin - Dan Chen; Yingxi Li; Xiaodong Wang; Keqiu Li; Yaqing Jing; Jinghua He; Zhaoyan Qiang; Jingzhi Tong; Ke Sun; Wen Ding; Yi Kang; Guang Li (Immunologic Research, 2016)

Erratum to: Identification of pummelo cultivars by using Vis/NIR spectra and pattern recognition methods - Xun-lan Li; Shi-lai Yi; Shao-lan He; Qiang Lv; Rang-jin Xie; Yong-qiang Zheng; Lie Deng (Precision Agriculture, 2016)

Identification of pummelo cultivars by using Vis/NIR spectra and pattern recognition methods - Xun-lan Li; Shi-lai Yi; Shao-lan He; Qiang Lv; Rang-jin Xie; Yong-qiang Zheng; Lie Deng (Precision Agriculture, 2016)

Geo-engineered buffer capacity of two-layered absorbing system under the impact of rock avalanches based on Discrete Element Method - Yu-zhang Bi; Si-ming He; Xin-po Li; Yong Wu; Qiang Xu; Chao-jun Ouyang; Li-Jun Su; Hao Wang (Journal of Mountain Science, 2016)

Human cytomegalovirus UL49 encodes an early, virion-associated protein essential for virus growth in human foreskin fibroblasts - Feng Zhu; Jian Yuan; Hong-Jian Li; Zhi-Feng Zeng; Zhi-Wen Luo; Shi-Qian Li; Chi-Qiang He; Xue-Fang Jia; Xin Zhang; Hui Zuo; Yi-Min Liu; Martin Chang; et al. (Archives of Virology, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Agricultural vulnerability over the Chinese Loess Plateau in response to climate change: Exposure, sensitivity, and adaptive capacity - Xueling Li; Joshua Philp; Roger Cremades; Anna Roberts; Liang He; Longhui Li; Qiang Yu (Ambio, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

The characteristics of rill development and their effects on runoff and sediment yield under different slope gradients - Ji-jun He; Li-ying Sun; Hui-li Gong; Qiang-guo Cai; Li-Juan Jia (Journal of Mountain Science, 2016)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Olfactory Deprivation Hastens Alzheimer-Like Pathologies in a Human Tau-Overexpressed Mouse Model via Activation of cdk5 - Ke Li; Fang-Fang Liu; Chun-Xue He; He-Zhou Huang; Ao-Ji Xie; Fan Hu; Dan Liu; Jian-Zhi Wang; Ling-Qiang Zhu (Molecular Neurobiology, 2016)

Efficient Conversion of Spermatogonial Stem Cells to Phenotypic and Functional Dopaminergic Neurons via the PI3K/Akt and P21/Smurf2/Nolz1 Pathway - Hao Yang; Yang Liu; Yanan Hai; Ying Guo; Shi Yang; Zheng Li; Wei-Qiang Gao; Zuping He (Molecular Neurobiology, 2015)

Fate of nitrogen from green manure, straw, and fertilizer applied to wheat under different summer fallow management strategies in dryland - Fucui Li; Zhaohui Wang; Jian Dai; Qiang Li; Xiang Wang; Cheng Xue; Hui Liu; Gang He (Biology and Fertility of Soils, 2015)

A newly isolated Haloalkaliphilic bacterium from middle–late Eocene halite formed in salt lakes in China - Fan-Wei Meng; Xiu-Qiang Wang; Pei Ni; Gunther Kletetschka; Chun-He Yang; Yin-Ping Li; Yong-Hua Yang (Carbonates and Evaporites, 2015)

A FOXM1 related long non-coding RNA contributes to gastric cancer cell migration - Hui Cai; Jingde Chen; Bin He; Qiang Li; Yandong Li; Yong Gao (Molecular and Cellular Biochemistry, 2015)

Age, petrogenesis and tectonic significance of the ferrobasalts in the Chagangnuoer iron deposit, western Tianshan - Ning-Bo Li; He-Cai Niu; Xing-Chun Zhang; Qiao-Song Zeng; Qiang Shan; Cong-Ying Li; Shuang Yan; Wu-Bin Yang (International Geology Review, 2015)

Lower Cambrian polychaete from China sheds light on early annelid evolution - Jianni Liu; Qiang Ou; Jian Han; Jinshu Li; Yichen Wu; Guoxiang Jiao; Tongjiang He (The Science of Nature, 2015)

Exceptionally preserved caddisfly larval cases (Insecta) from the lower Cretaceous of the Liupanshan basin, Western China - Xin He; Zhong-Qiang Chen; Zongsheng Lu; Jun Li; Wei Hu; Shengfu Li; Zhitao Xu (Journal of Earth Science, 2015)

Protective effects of hydroxysafflor yellow A (HSYA) on alcohol-induced liver injury in rats - Yanhao He; Qiang Liu; Yanxiang Li; Xiaofeng Yang; Weirong Wang; Tingting Li; Wei Zhang; Yuexin Cui; Chaoyun Wang; Rong Lin (Journal of Physiology and Biochemistry, 2015)

Oral cavity contains distinct niches with dynamic microbial communities - Xin Xu; Jinzhi He; Jing Xue; Yan Wang; Kun Li; Keke Zhang; Qiang Guo; Xianghong Liu; Yuan Zhou; Lei Cheng; Mingyun Li; Yuqing Li; et al. (Environmental Microbiology, 2015)
Summary Microbes colonize human oral surfaces within hours after delivery. During postnatal development, physiological changes, such as the eruption of primary teeth and replacement of the primary dentition with permanent dentition, greatly alter the microbial habitats, which, in return, may lead to community composition shifts at different phases in people's lives. By profiling saliva, supragingival and mucosal plaque samples from healthy volunteers at different ages and dentition stages, we observed that the oral cavity is a highly heterogeneous ecological system containing distinct niches with significantly different microbial communities. More importantly, the phylogenetic microbial structure varies with ageing. In addition, only a few taxa were present across the whole populations, indicating a core oral microbiome should be defined based on age and oral niches.

Antimicrobial and allelopathic metabolites produced by Penicillium brasilianum - Hao-Yu Tang; Qiang Zhang; He Li; Jin-Ming Gao (Natural Product Research, 2015)

Isolation and characterization of ZmERF1 encoding ethylene responsive factor-like protein 1 in popcorn (Zea mays L.) - Qingling Shi; Yongbin Dong; Dahe Qiao; Qilei Wang; Zhiyan Ma; Feifei Zhang; Qiang Zhou; He Xu; Fei Deng; Yuling Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Spatiotemporal variation of meteorological droughts based on the daily comprehensive drought index in the Haihe River basin, China - Jun He; Xiao-Hua Yang; Jian-Qiang Li; Ju-Liang Jin; Yi-Ming Wei; Xiao-Juan Chen (Natural Hazards, 2015)

Production of transgenic dairy goat expressing human α-lactalbumin by somatic cell nuclear transfer - Xiujing Feng; Shaoxian Cao; Huili Wang; Chunhua Meng; Jingxin Li; Jin Jiang; Yong Qian; Lei Su; Qiang He; Qingxiao Zhang (Transgenic Research, 2015)

Arbuscular mycorrhiza mediates glomalin-related soil protein production and soil enzyme activities in the rhizosphere of trifoliate orange grown under different P levels - Qiang-Sheng Wu; Yan Li; Ying-Ning Zou; Xin-Hua He (Mycorrhiza, 2015)

ICE1 demethylation drives the range expansion of a plant invader through cold tolerance divergence - H. J. Xie; H. Li; D. Liu; W. M. Dai; J. Y. He; S. Lin; H. Duan; L. L. Liu; S. G. Chen; X. L. Song; B. E. Valverde; S. Qiang (Molecular Ecology, 2015)
Cold tolerance adaption is a crucial determinant for the establishment and expansion of invasive alien plants into new cold environments; however, its evolutionary mechanism is poorly understood. Crofton weed ( Ageratina adenophora ), a highly invasive alien plant, is continuously spreading across subtropical areas in China, north‐eastward from the first colonized south‐western tropical regions, through cold tolerance evolution. Close relations between the cold tolerance levels of 34 populations, represented by 147 accessions, and the latitude, extreme lowest temperature, coldest month average temperature, and invasion period have provided direct insight into its cold tolerance divergence. A comparative study of the CBF pathway, associated with the cold tolerance enhancement of cold‐susceptible CBF 1 ‐transgenic plant, among four geographically distinct crofton weed populations revealed that the CBF pathway plays a key role in the observed cold tolerance divergence. Four epialleles of the cold response regulator ICE 1 ranged from 66 to 50 methylated cytosines, representing a 4.4% to 3.3% methylation rate and significantly corresponding to the lowest to highest cold tolerance levels among these different populations. The significant negative relation between the transcription levels of the primary CBF pathway members, except for CBF 2 , and the methylation levels among the four populations firstly demonstrates that the demethylation‐upregulated transcription level of CBF pathway is responsible for this evolution. These facts, combined with the cold tolerance variation and methylation found among three native and two other introduced populations, indicate that the ICE 1‐ demethylated upregulation of cold tolerance may be the underlying evolutionary mechanism allowing crofton weed to expand northward in China.

Differential behavioral responses of zebrafish larvae to yohimbine treatment - Qiang Li; Jia Lin; Yinglan Zhang; Xiuyun Liu; Xiao Qian Chen; Ming-Qing Xu; Lin He; Sheng Li; Ning Guo (Psychopharmacology, 2015)

l-arginine stimulates CAT-1-mediated arginine uptake and regulation of inducible nitric oxide synthase for the growth of chick intestinal epithelial cells - Chao Yuan; Xiaoyun Zhang; Qiang He; Junming Li; Jianjun Lu; Xiaoting Zou (Molecular and Cellular Biochemistry, 2015)

Two-phase integrated sludge thickening and digestion (TISTD) reactor microbial diversity and community structure succession rules - He Qiang; Sun Xingfu; Gu Li; Ai Hainan (World Journal of Microbiology and Biotechnology, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

Risk assessment of the city water resources system based on Pansystems Observation-Control Model of Periphery - Qiang Fu; Fanli Gong; Qiuxiang Jiang; Tianxiao Li; Kun Cheng; He Dong; Xiaosong Ma (Natural Hazards, 2014)

Geochemistry of magmatic and hydrothermal zircon from the highly evolved Baerzhe alkaline granite: implications for Zr–REE–Nb mineralization - Wu-Bin Yang; He-Cai Niu; Qiang Shan; Wei-Dong Sun; Hong Zhang; Ning-Bo Li; Yu-Hang Jiang; Xue-Yuan Yu (Mineralium Deposita, 2014)

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

Prevalence of hepatitis B virus and hepatitis C virus in patients with human immunodeficiency virus infection in central China - Xi Chen; Jian-Mei He; Li-Sha Ding; Guo-Qiang Zhang; Xiao-Bai Zou; Jun Zheng (Archives of Virology, 2013)

Detection of African swine fever virus-like sequences in ponds in the Mississippi Delta through metagenomic sequencing - Xiu-Feng Wan; J. Lamar Barnett; Fred Cunningham; Si Chen; Guohua Yang; Shannon Nash; Li-Ping Long; Lorelei Ford; Sherry Blackmon; Yan Zhang; Larry Hanson; Qiang He (Virus Genes, 2013)

Cambium reactivation independent of bud unfolding involves de novo IAA biosynthesis in cambium regions in Populus tomentosa Carr. - Wan-Feng Li; Qi Ding; Ke-Ming Cui; Xin-Qiang He (Acta Physiologiae Plantarum, 2013)

Expansivity and compressibility of strontium fluorapatite and barium fluorapatite determined by in situ X-ray diffraction at high-T/P conditions: significance of the M-site cations - Qiang He; Xi Liu; Baosheng Li; Liwei Deng; Zhiqiang Chen; Xiaoyang Liu; Hejing Wang (Physics and Chemistry of Minerals, 2013)

Seismic deformation and seismic resistance analysis of Shapai Roller Compacted Concrete Arch Dam based on field monitoring and dynamic finite element method - Li Zhuo; Jiang-da He; Hong-qiang Xie (Journal of Mountain Science, 2013)

Optimization of Cultivating Conditions for Triterpenoids Production from Antrodia cinnmomea - Yuan-Chuan He; Kai-Ze He; Qiang Pu; Jing Li; Zong-Jie Zhao (Indian Journal of Microbiology, 2012)

Disrupted Iron Metabolism and Ensuing Oxidative Stress may Mediate Cognitive Dysfunction Induced by Chronic Cerebral Hypoperfusion - Yunxia Li; Yusheng He; Qiang Guan; Wuchao Liu; Hongjie Han; Zhiyu Nie (Biological Trace Element Research, 2012)

Molecular cloning and expression analysis of common carp Cyprinus carpio tumor necrosis factor-α - Xiao Zhao; Duo Duan; Xiangru Feng; Yilong Chen; Zhen Sun; Shengmei Jia; Jiangshuai He; Bin Wang; Wei Li; Junhui Zhang; Wendong Wang; Zhenguo Yang; et al. (Fisheries Science, 2012)

Isolation and characterization of sixteen microsatellite loci of a blind cavefish, Triplophysa xiangxiensis - Yanhong Yao; Deng Qiang Wang; Li He; Lai Ning Yu (Conservation Genetics Resources, 2012)

Monocyte to macrophage differentiation-associated (MMD) positively regulates ERK and Akt activation and TNF-α and NO production in macrophages - Qiang Liu; Jin Zheng; Dan-Dan Yin; Jie Xiang; Fei He; Yao-Chun Wang; Liang Liang; Hong-Yan Qin; Li Liu; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2012)

Solid solutions between lead fluorapatite and lead fluorvanadate apatite: compressibility determined by using a diamond-anvil cell coupled with synchrotron X-ray diffraction - Qiang He; Xi Liu; Xiaomin Hu; Liwei Deng; Zhiqiang Chen; Baosheng Li; Yingwei Fei (Physics and Chemistry of Minerals, 2012)

Effects of applied urea and straw on various nitrogen fractions in two Chinese paddy soils with differing clay mineralogy - Shao-Jun Qiu; Pei-Qin Peng; Ling Li; Ping He; Qiang Liu; Jin-Shui Wu; Peter Christie; Xiao-Tang Ju (Biology and Fertility of Soils, 2012)

The effect of down regulation of calcineurin Aα by lentiviral vector-mediated RNAi on the biological behavior of small-cell lung cancer and its bone metastasis - Ning-Qiang Ma; Li-Li Liu; Jie Min; Jun-Wei Wang; Wei-Feng Jiang; Yan Liu; Yan-Guo Feng; Hai-Chuan Su; Ying-Ming Feng; He-Long Zhang (Clinical & Experimental Metastasis, 2011)

Human cytomegalovirus RL13 gene transcripts in a clinical strain - Mali Li; Yanping Ma; Yaohua Ji; Rong He; Ying Qi; Zhengrong Sun; Ning Wang; Shuang Gao; Qiang Ruan (Virus Genes, 2011)

Solid solution between lead fluorapatite and lead fluorvanadate apatite: mixing behavior, Raman feature and thermal expansivity - Qiang He; Xi Liu; Xiaomin Hu; Sicheng Li; Hejing Wang (Physics and Chemistry of Minerals, 2011)

Equation of state of CAS phase to pressure of the uppermost lower mantle at ambient temperature - Xi Liu; Qiang He; LiWei Deng; ShuangMeng Zhai; XiaoMin Hu; BaoSheng Li; LiFei Zhang; ZhiQiang Chen; Qiong Liu (Science China Earth Sciences, 2011)

Age-related changes in the anatomical characteristics of Peyer's patches in small intestine of Bactrian camels (Camelus bactrianus) - Shan-Shan Qi; Wen-Hui Wang; Qiang Gao; Xiao-Hong Xu; Wan-Hong He; Ying-Pai Zhaxi; Li-Feng Tai (Tropical Animal Health and Production, 2011)

Erratum to: Overexpression of transcription factor ZmPTF1 improves low phosphate tolerance of maize by regulating carbon metabolism and root growth - Zhaoxia Li; Qiang Gao; Yazheng Liu; Chunmei He; Xinrui Zhang; Juren Zhang (Planta, 2011)

Overexpression of transcription factor ZmPTF1 improves low phosphate tolerance of maize by regulating carbon metabolism and root growth - Zhaoxia Li; Qiang Gao; Yazheng Liu; Chunmei He; Xinrui Zhang; Juren Zhang (Planta, 2011)

Enzymatic saccharification of pretreated corn stover in a fed-batch membrane bioreactor - Mingjia Zhang; Rongxin Su; Qiang Li; Wei Qi; Zhimin He (BioEnergy Research, 2011)

Systematic analysis of gene expression level with tissue-specificity, function and protein subcellular localization in human transcriptome - Qiang Li; Xianghua Liu; Quanyuan He; Lei Hu; Yichen Ling; Yanhua Wu; Xianmei Yang; Long Yu (Molecular Biology Reports, 2011)

Effects of elevated carbon dioxide and/or ozone on endogenous plant hormones in the leaves of Ginkgo biloba - XueMei Li; LiHong Zhang; YueYing Li; LianJu Ma; Qiang Chen; Lan Lan Wang; XingYuan He (Acta Physiologiae Plantarum, 2011)

Groundwater environmental capacity and its evaluation index - Li Ting Xing; Qiang Wu; Chun He Ye; Nan Ye (Environmental Monitoring and Assessment, 2010)

Transcription pattern of UL131A-128 mRNA in clinical strains of human cytomegalovirus - Zhengrong Sun; Gaowei Ren; Yanping Ma; Ning Wang; Yaohua Ji; Ying Qi; Mali Li; Rong He; Qiang Ruan (Journal of Biosciences, 2010)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

Notch signaling maintains proliferation and survival of the HL60 human promyelocytic leukemia cell line and promotes the phosphorylation of the Rb protein - Guo-Hui Li; Yu-Zhen Fan; Xiao-Wei Liu; Bing-Fang Zhang; Dan-Dan Yin; Fei He; Si-Yong Huang; Zhi-Jie Kang; Heng Xu; Qiang Liu; Yan-Lan Wu; Xiao-Li Niu; et al. (Molecular and Cellular Biochemistry, 2010)

Cloning, characterization and expression analysis of a CXCR1-like gene from mandarin fish Siniperca chuatsi - Chao Chen; Zhongsheng Li; Zhicheng Zhou; Zhixin Yin; Siu-Ming Chan; Xiao-Qiang Yu; Shaoping Weng; Jianguo He (Fish Physiology and Biochemistry, 2009)

Establishment of cell lines using a doxycycline-inducible gene expression system to regulate expression of hepatitis B virus X protein - Hong Tang; Li Liu; Feng-Jun Liu; En-Qiang Chen; Seishi Murakami; Yong Lin; Fang He; Tao-You Zhou; Fei-Jun Huang (Archives of Virology, 2009)

Ectopic overexpression of AtHDG11 in tall fescue resulted in enhanced tolerance to drought and salt stress - Ya-Jun Cao; Qiang Wei; Yang Liao; He-Ling Song; Xian Li; Cheng-Bin Xiang; Ben-Ke Kuai (Plant Cell Reports, 2009)

Gastric carcinoma with osteoclast-like giant cells: a case report and review of the literature - Li-duan Zheng; Xiu-ping Yang; Hua-xiong Pan; Xiu Nie; Jun He; Qing Lv; Qiang-song Tong (Journal of Zhejiang University-SCIENCE B, 2009)

Notch signaling regulates the FOXP3 promoter through RBP-J- and Hes1-dependent mechanisms - Hai-Feng Ou-Yang; Hong-Wei Zhang; Chang-Gui Wu; Ping Zhang; Jian Zhang; Jun-Chang Li; Li-Hong Hou; Fei He; Xin-Yu Ti; Li-Qiang Song; Su-Zhen Zhang; Lei Feng; et al. (Molecular and Cellular Biochemistry, 2009)

Involvement of ERK and AKT signaling in the growth effect of arginine vasopressin on adult rat cardiac fibroblast and the modulation by simvastatin - Yan-Ping He; Lian-You Zhao; Qiang-Sun Zheng; Shao-Wei Liu; Xiao-Yan Zhao; Xiao-Long Lu; Xiao-Lin Niu; Xia Li (Molecular and Cellular Biochemistry, 2008)

Microbial activity and community diversity in a variable charge soil as affected by cadmium exposure levels and time - Jia-li Shentu; Zhen-li He; Xiao-e Yang; Ting-qiang Li (Journal of Zhejiang University-SCIENCE B, 2008)

Renalase gene is a novel susceptibility gene for essential hypertension: a two-stage association study in northern Han Chinese population - Qi Zhao; Zhongjie Fan; Jiang He; Shufeng Chen; Hongfan Li; Penghua Zhang; Laiyuan Wang; Dongsheng Hu; Jianfeng Huang; Boqin Qiang; Dongfeng Gu (Journal of Molecular Medicine, 2007)

Quantification of the Impact of Land-Use Changes on Ecosystem Services: A Case Study in Pingbian County, China - Ren-Qiang Li; Ming Dong; Jian-Yong Cui; Li -Li Zhang; Qing-Guo Cui; Wei-Ming He (Environmental Monitoring and Assessment, 2007)

The distribution and economic losses of alien species invasion to China - Haigen Xu; Hui Ding; Mingyan Li; Sheng Qiang; Jianying Guo; Zhengmin Han; Zongguo Huang; Hongying Sun; Shunping He; Hairong Wu; Fanghao Wan (Biological Invasions, 2006)

A novel, ultra-large xylanolytic complex (xylanosome) secreted by Streptomyces olivaceoviridis - Zheng-Qiang Jiang; Wei Deng; Li-Te Li; Chang-He Ding; Isao Kusakabe; Sze-Sze Tan (Biotechnology Letters, 2004)

Variations of stomatal density and carbon isotope values of Picea crassifolia at different altitudes in the Qilian Mountains - Wei-ya Qiang; Xun-ling Wang; Tuo Chen; Hu-yuan Feng; Li-zhe An; Yuan-qin He; Gang Wang (Trees, 2003)